Exploration of shared gene signatures and molecular mechanisms between psoriasis and COVID-19: evidence from transcriptome data - Rong-Jing Dong; Lu-Hui Yang; Yu-Ye Li; You-Wang Lu (Mammalian Genome, 2026)

Correction to: Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Effects of straw management practices on soil organic carbon fraction dynamics and greenhouse gas emissions in a double-season rice cropping system - Chaoyun Ying; Yue Li; Xuechi Rong; Kailou Liu; Yongfu Li; Xianting Wang; Guanjun Li; Cuiyan Wu; Tida Ge; Shuang Wang (Soil Ecology Letters, 2026)

RETRACTED ARTICLE: Molecular mechanisms of flower color variation in Impatiens uliginosa: insights from transcriptome sequencing and functional analysis of the IuMYB1 gene in anthocyanin biosynthesis and pigmentation - Baiyang He; Yuteng Xue; Shanman Li; Xue Hu; Xiaoli Lou; Jiwei Wang; Huang Deng; Shunming Zhang; Chao Luo; Yuhong Rong (Physiology and Molecular Biology of Plants, 2026)

Poricoic acid A administered during DSS exposure attenuates acute colitis in mice and is accompanied by barrier-associated changes and endpoint fecal microbiota shifts - Mei Wang; Kunkun Zhang; Danli Wang; Mingtao Cao; Rong Yong; Xiangqian Li; Wenyi Chen; Chengcheng Peng; Jiale Chang; Lu Fang; Feiyang Zhou; Yuyue Wan; et al. (Journal of Natural Medicines, 2026)

Endothelial cell heterogeneity drives angiogenesis in endometriosis: mechanisms and emerging organoid-based models - Jingjing Xu; Yadan Tan; Ziteng Huang; Xiran Wang; Lihong Song; Jinshan Xing; Rong Li; Jingyan Yi (Apoptosis, 2026)

Assessing cognitive impairment in epilepsy using Arterial spin-labeled (ASL) perfusion imaging - Qiuyan Chen; Jie Zhang; Rong Chen; Yameng Qin; Xu Wang; Qiang Liu; Zheng Yin; Ping Yang; Feng Rao; Longnan Wang; Mengyun Li; Yanzi Jin; et al. (Brain Imaging and Behavior, 2026)

Phosphorus limitation and manganese toxicity induced by high nitrogen inputs suppress plant biomass - Jiapu Li; Xuebin Yan; Jordi Sardans; Josep Peñuelas; Shiting Hong; Peng Wang; Pinwei Zhang; Rong Song; Yanwen Zhao; Yong Li; Hui Guo (Plant and Soil, 2026)

Assessing impacts of vertical mixing parameterizations on ENSO simulation in a ROMS-based hybrid coupled model - Yinnan Li; Yang Yu; Maonan Chen; Chuan Gao; Hongna Wang; Liu Yang; Rong-Hua Zhang (Journal of Oceanology and Limnology, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Rapid Determination of Tight Rock Permeability Using Early-Time Transient Pulse-Decay Data - Minghao Yi; Chaoqi Yang; Liang Wang; Rong Zhang; Kaizhong Zhang; Shuqing Li (Rock Mechanics and Rock Engineering, 2026)

Identification of CAMTA transcription factors and functional analysis of OsCAMTA4 in rice blast and salt stress - Zixiang Li; Zhensheng Qiao; Zhichao Wang; Rong Huang; Junxing Tan; Quchen Zhou; Xiangyu Huang; Feng Sheng; Xuezhu Du (Planta, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Refractory Dermatophytosis Caused by Trichophyton indotineae: A Case Series Highlighting Antifungal Resistance and Management Challenges - Yubo Ma; Rong Yan; Yakun Shao; Chunying Xiao; Tianshuo Zhao; Xingyu Li; Gang Wang; Chunying Li; Yinggai Song; Meng Fu; Yanyang Guo (Mycopathologia, 2026)

Role of the immune microenvironment in bone regeneration and progress in immune-modulating bone nanobiomaterials - Rong’an Li; Jiakang Yang; Wenjun Duan; Kexin Yang; Katong Lo; Qianming Chen; Baixiang Wang (Journal of Zhejiang University-SCIENCE B, 2026)

Comparative effects of digestion residue-derived and corn straw biochar on free-living diazotrophs in nitrogen-deficient calcareous purple soil - Junwen Zhao; Yuting Chen; Haiyan Zhang; Yulan Chen; Bing Li; Muhammad Bilal Khan; Yingjie Wu; Xiaoyan Tang; Huanxiu Li; Rong Huang; Qiang Xu; Qiquan Li; et al. (Biology and Fertility of Soils, 2026)

Kinetic Characteristics and Migration Behavior of Fractal-Based Sub-Diffusion of Coal Reservoir Gas under Anomalous Spatio-Temporal Conditions - Zhenyang Wang; Shuo Zhang; Congmeng Hao; Lu Bai; Rong Zhang; Guanhua Ni; Zhen Liu; Zhao Li; Jiaxuan Liu (Natural Resources Research, 2026)

Histamine regulation in shaping spindle refractoriness: a computational modeling study - Bo Wang; Qiang Li; Wen-Hua Wang; Wan-Rong Zan; Yi-Ming Li; Jiang-Ling Song; Rui Zhang (Journal of Computational Neuroscience, 2026)

Pentoxifylline targets TLR4/MyD88/NF-κB signaling to ameliorate neuroinflammation and metabolic dysfunction in a rat model of chronic hypoperfusion-induced vascular cognitive impairment - Xiaohan Wang; Bingchuan Xie; Xiaoyang Yuan; Jiaying Rong; Xiaojing Lv; Qingying Ma; Li Shen; Bing Han (Metabolic Brain Disease, 2026)

Temporin-GHaR6R Peptide Ameliorates Experimental Autoimmune Encephalomyelitis by Suppressing Microglial M1 Polarization and Mitochondrial Dynamics Dysfunction - Da-Qi Zhang; Hui-Min Xu; Jing Lu; Yu-Sheng Huang; Xiao-Li Feng; Li-Jun Chen; Wen-Jie Zhao; Rong Wang; Yingxia Zhang; Qifu Li (Probiotics and Antimicrobial Proteins, 2026)

Inhibitory effect of gut microbiota-fermented trisaccharide GuFGa (Glc-Fuc-Gal) on Campylobacter jejuni: insights from transcriptomic and metabolomic analyses - Xinmiao Ren; Shuang Li; Changyun Wang; Francesco Secundo; Ningyang Li; Mengshi Xiao; Min Yang; Rong Li; Qing Kong; Han Sun; Xiaodan Fu; Haijin Mou (Marine Life Science & Technology, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Discovery of pyrrolo[2,3-d]pyrimidine derivatives with inhibitory effect on liver cancer stem cell - Xuecong Zhang; Xuechun Chen; Liwei Wang; Yiyuan Chang; Jiaxin Li; Jijian Yang; Dongxuan Ni; Ruihan Zhang; Rong Liu; Weilie Xiao (Medicinal Chemistry Research, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Dysregulated KIF2A correlates with p53 expression pattern in breast cancer - Yun Hao; Si-Qin Ma; Ting Xu; Jia-Qi Wu; Rong Ma; Ya-Wen Wang; Jian-Li Wang (Molecular and Cellular Biochemistry, 2026)

Improving spatial resolutions of unmanned aerial vehicle hyperspectral images to predict grain yield and protein content in rice - Zhonglin Wang; Rong Hu; Mingming Hu; Huilai Yin; Tao Liu; Yufei Xie; Yangming Ma; Feng Yang; Feijie Li; Zhiyuan Yang; Yongjian Sun; Jun Ma (Precision Agriculture, 2026)

Genome-wide Identification and Expression Analysis of the ABF Gene Family in Achnatherum splendens - Shan Yin; Mingsu Chen; Ming Hu; XiaoYing Li; Jingru Wang; Jiahuan Niu; Zhangqi Song; Huan Yang; Hongbing Li; Rong Li (Plant Molecular Biology Reporter, 2026)

Mineralogical tracers for magmatic and hydrothermal controls on Nb-Ta-Li mineralization: a case study from the Hailuoling granite system, Southern China - Qifei Shi; Bin Wu; Xin Gui; Qian Ren; Guanglai Li; Rong Yin; Qingfei Wang (Mineralium Deposita, 2026)

Archaeal and Bacterial Communities and Their Relations with Hydrochemistry in Gongzhu Co, a Carbon-Poor, Nutrient-Rich Basin Lake of the Qinghai–Xizang Plateau - Minhaoxue Zou; Yujie Tao; Bohan Shi; Rong Xu; Rong Wang; Yongzhen Li; Rui Han; Derui Zhu (Current Microbiology, 2026)

Biological characterization of an avian leukosis virus subgroup J isolate from yunnan indigenous black-bone chickens and generation of its full-length infectious clone - Hongya Yan; Guojun Wang; Rong Zhao; Ke Li; Zhengju Yuan; Wengui Li; Aiguo Xin (Archives of Virology, 2026)

Protein foundation models: a comprehensive survey - Hao Xu; Liangjie Li; Sangyu Pan; Peng Cheng; Yuxiang Wang; Zhen Rong; Feng Liu; Xingxu Huang; Shengqi Wang; Wenjie Shu (Science China Life Sciences, 2026)

Genetic basis of pedicellate spikelet masculinization in maize revealed by an advanced maize–teosinte population - Ruifan Bao; Xueying Wang; Junle Wu; Ting Liang; Xiya Hu; Pengxu Meng; Hang Mi; Peng Li; Sijia Yang; Zhiqin Liu; Siyu Lei; Jinyu Yang; et al. (Planta, 2026)

Higher aridity in alpine grasslands discourages soil organic carbon accumulation by microorganisms - Jia Li; Xia Wang; Ya Rong Zhang; Ya Zhen Li; Meng Han Yuan; Yun Fei Zhao; Wen Hui Duan; Jie Yi Xia; Zi Yang Niu (Plant and Soil, 2026)

Nitrogen enrichment boosts subsoil carbon sequestration by enhancing microbial straw utilization - Zheng-Rong Kan; Muhan Li; Xinyue Wang; Yixuan Luo; Ahmad Latif Virk; Gong Wu; Haishui Yang; Feng-Min Li (Plant and Soil, 2026)

Human MAITregs possess diverse TCR repertoires and are functionally supported by glycolysis - Maoyu Tang; Xinying Li; Xudong Yang; Changfeng Zhao; Yuwei Zhang; Sanwei Chen; Zhenghui Ye; Liujin Hou; Yusheng Chen; Rong Lv; Hongchuan Zhao; Xiaowen Cheng; et al. (Science China Life Sciences, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Design, synthesis, characterization and exploration of anti-HBV activity of matrine-adenine hybrids - Meng-Fan Xie; Zhou-Fei Zheng; Jing-Lei Wang; Rong-Tao Li; Zhi-Jun Zhang (Molecular Diversity, 2026)

Grass carp TMEM33 promotes GCRV replication by targeting MAVS for degradation and suppressing host antiviral immune response - Qian Wang; Zichao Peng; Rong Deng; Yongming Li; Zuoyan Zhu; Yaping Wang; Libo He; Jing Lu (Marine Life Science & Technology, 2026)

Efficacy and Safety of Temozolomide for the Treatment of Advanced or Recurrent Ependymoma: A Meta-Analysis - Rong Zhang; Binyan Liu; Zhuang Kang; Shenglan Li; Yingfan Sun; Jiachen Wang; Xin Yang; Shuo Yin; Feng Chen; Wenbin Li (Journal of Pharmaceutical Innovation, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Chronic Excessive Exposure to Fluoride Impairs the Intestinal Mucosal Barrier to Cause Inflammatory Response and Microbiome Dysbiosis in Rats - Jia-Rong Zhang; Yi-Wen Li; Hong-Xuan Chen; Yi Luo; Ru-Ming Liu; Jian-Bin Wang; Ning-Ning Liu; Jian-Hui Xiao (Biological Trace Element Research, 2026)

Chronic heat stress attenuates innate immunity and increases susceptibility to Aeromonas hydrophila in Siberian sturgeon (Acipenser baerii) - Xiaowen Wang; Huijuan Li; Rong Zhang; Lili Liu; Wei Wang; Hua Zhu (Aquaculture International, 2026)

Comprehensive genomic analysis of the maize ACP gene family reveals ZmACP1-mediated salt stress tolerance in Arabidopsis - Yunhao Wu; Junyu Chen; Hanqiu Ge; Xing Rong; Yuchen Wang; Meiwang Zhang; Zhigang Li; Yingrui Xi; Junfeng Tang; Junyi Li; Ping Li; Baohua Wang; et al. (Plant Cell Reports, 2026)

Tropical instability waves and their relationships with large-scale oceanic thermal conditions, revealed in ROMS-based hybrid coupled model of the tropical Pacific - Yinnan Li; Yang Yu; Chuan Gao; Hongna Wang; Rong-Hua Zhang (Journal of Oceanology and Limnology, 2026)

Total flavonoids from Carthamus tinctorius L. inhibit the liver fibrosis progression via Hippo/YAP pathway - Xiaomei Bao; Xiaolu Zhao; Haisheng Wang; Hongwei Yuan; Rong Jin; Mingqi Li; Yinghe Wang; Yuehong Ma (Journal of Natural Medicines, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Aquaporin-1 stabilizes β-catenin to promote NLRP3 inflammasome-mediated pyroptosis in rheumatoid arthritis - Meng-yuan Zhou; Zi-yao Gao; Jing Sun; Wen-cai Long; Juan Zhou; Wen-jing Fang; Xue-chun Wang; Sheng-dong Wu; Rong Li (Apoptosis, 2026)

Ca2+-Independent Exocytosis Favors Axonal Release through Enlarged Fusion Pores in Sensory Neurons - Rong Huang; Xingyu Du; Qihui Wu; Yuan Wang; Yuqi Hang; Xi Wu; Yiman Li; Jie Li; Zhongjun Qiao; Yinglin Li; Lili Yin; Xiaoxuan Sun; et al. (Neuroscience Bulletin, 2026)

Failure Behavior and Energy Evolution of Granite Containing Pre-existing Fissures Characterized by AE and DIC - Run-ze Zhang; Chuan-xin Rong; Bin Wang; Hua-qiao Xu; Yan-zhe Li; Yang Wang (Applied Geophysics, 2026)

Hydrogeophysical Imaging and Joint Interpretation of Rainfall Infiltration on an Embanked Slope in the Mid-Lower Yangtze Hilly Region - Rong-wen Guo; Chen-yang Li; Zhuo Liu; Deng-kang Wang; Ming Yu (Applied Geophysics, 2026)

Butyrate supplementation in sows promotes offspring embryonic muscle development by upregulating HDAC-mediated H3K27ac levels and myogenic gene expression - Hao Zuo; Chen Li; Xiaoyu Niu; Zhibo Ma; Zhifeng Wu; Zeyang Gao; Liqian Sun; Yiming Jia; Mingfei Zhu; Litong Wang; Rong Zheng; Bo Zuo (Science China Life Sciences, 2026)

Adsorption of Oxytetracycline Hydrochloride by Oxidatively Modified Biochar Particles: Performance and Mechanism - Rong Chen; Jianlin Zhou; Lingling Wang; Weiyin Liu; Zeyu Dai; Zhang Chen; Guoliang Chen; Zhixian Li (Water, Air, & Soil Pollution, 2026)

Incorporating Ecoregions and Freeze–Thaw Effects Effectively Improves the Accuracy of Machine Learning Models for Baseflow Prediction in Seasonally Frozen Regions - Tingting Deng; Hang Lyu; Rong Zhong; Yunting Zou; Jianan Wang; Yu Li; Yue Guo (Water Resources Management, 2026)

Unveiling the genetic architecture of stripe rust resistance in wheat: a region-specific GWAS in Xinjiang, China - Feifei Zhang; Rong Wang; Wenjuan Jiao; Wanlong He; Yuzhe Zhang; Na Sun; Bin Bai; Kemei Li; Yukun Cheng; Hongwei Geng (Theoretical and Applied Genetics, 2026)

Plant-soil feedback driven by root-associated fungal communities accelerates the secondary succession of bare saline-alkaline grassland patches - Xiaona Zheng; Yuhong Yin; Dan Yang; Jingjuan Bi; Wenlong He; Siya Li; Xiao Liang; Jigui Chen; Rong Wang; Zhiying Guo; Xing Li; Tao Zhang; et al. (Plant and Soil, 2026)

Heterologous expression of Pinus massoniana VNS2 enhances secondary cell wall deposition in poplar - Yating Tian; Kang Wang; Hao Rong; Meng Xu; Zhouxian Ni; Li-an Xu (Plant Cell Reports, 2026)

Advances in natural products with anti-skin photoaging: mechanisms, phytochemical diversity, and therapeutic potential - Yi Luo; Xiao-Cui Liu; Yu-Jie Li; Yu-Jia Wang; Ming-Hua Qiu; Xing-Rong Peng (Phytochemistry Reviews, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Novel 2-aminothiazole derivatives incorporating 9-alkyl purine moiety: design, synthesis, crystal structure, and bioactivity evaluation - Song Bai; Suran Wan; Miao Li; Rong Wu; Shouying Tang; Fang Wang; Lijun Chen; Xiaokang Lv; Xian Wei; Shuang Feng; Miaohe Zhang (Molecular Diversity, 2026)

Trace element zoning and temperature variation in sphalerite from the giant Nannihu porphyry-skarn-epithermal polymetallic system, central China - Chang Wang; Zhan-Ke Li; Ioan Sanislav; Yi Zheng; Xiao-Ming Li; Rong-Zhen Zhang; Jia Hu; Jun Zhang (Mineralium Deposita, 2026)

Cadmium accumulation and toxic effects on wheat under foliar and soil exposure to the simulated atmospheric deposition of cadmium - Mengling Huang; Xiuting Rong; Yuansong Ding; Xianlong Gao; Min Li; Xiaozhi Wang; Hailong Liu (Environmental Geochemistry and Health, 2026)

Mass Balance-Based Inventory of Heavy Metal Inputs and Outputs of Agricultural Soils in a Rice–Wheat Rotation Area, China: A Two-Year Field Experiment - Hailong Liu; Xiuting Rong; Haotian Wang; Hu Wang; Huan Zhao; Ruizhi Xia; Xiaozhi Wang; Min Li (Water, Air, & Soil Pollution, 2026)

Investigating the Therapeutic Efficacy of Quality-Controlled, miR-146a-5p-Enriched Small Extracellular Vesicles Derived From MSCs Against Idiopathic Pulmonary Fibrosis - Xin Wang; Lingjiao Meng; Qiuhong Wang; Ruixue Rong; Yu Zhang; Xiaohui Zhao; Chen Liang; Huizhen Guo; Li Deng; Zengqi Tan; Feng Guan; Yi Tan (Stem Cell Reviews and Reports, 2026)
Small extracellular vesicles derived from umbilical cord mesenchymal stem cells (UC-sEvs) may be used for the treatment of idiopathic pulmonary fibrosis (IPF) because of their ability to control inflammation and inhibit fibrosis. However, the lack of clarity regarding the treatment mechanism of IPF and the corresponding quality standards limit the clinical application of these small extracellular vesicles. Here, we established a good manufacturing practice (GMP) grade process for isolating UC-sEvs, and RNA-seq was performed to screen for potential therapeutic cargo in the product to confirm the therapeutic effect of nebulized UC-sEv agents against IPF. Functionally, UC-sEvs inhibited the pulmonary inflammatory response by regulating macrophage function, thereby suppressing the bleomycin toxicity-induced progression of fibrosis. Mechanistically, miR-146a-5p enrichment in UC-sEvs may be involved in alleviating bleomycin-induced IPF by targeting TRAF6/IRAK1 to negatively regulate inflammation. The proposed quality control strategy ensures the stability of the product across three batches, with RNA-seq analysis revealing highly similar miRNA expression profiles. The feasibility of using miR-146a-5p as a key therapeutic molecule has been validated. Finally, on the basis of the results of pharmacodynamics and key therapeutic molecule studies, we provided a detailed quality control standard for IPF therapy by nebulizing UC-sEv. These findings help understand how sEvs impact IPF and the possible consequences of their therapeutic usage and offer a quality standard reference. Graphical Abstract

Comprehensive virome analysis of soybean agroecosystems in China reveals geographic patterns and interfacial virus spillovers - Mengjia Xu; Ruixiang Cheng; Rong Yan; Hao Ai; Sijing Qiao; Pengbo Li; Jin Zhang; Tianyu Hu; Xiaoli Chang; Huawei Yang; Wenwu Ye; Ming Ding; et al. (Science China Life Sciences, 2026)

Screening of Fecal Bacteroides Strains and Discovery of Bacteroides eggerthii S13-F8 with Protective Effects Against Chemotherapy-Induced Diarrhea - Yi Zhao; Zhengqun Dai; Yanmei Lang; Rui Li; Hongyu Zheng; Jiajia Mi; Xiu He; Jin Liu; Rong Xiang; Xueran Mei; Yang Liu; Yantang Wang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Phytochemistry, pharmacology and bibliometrics insight of the genus Callicarpa L.: an extensive review encompassing the years from approximately 2010 to 2024 - Wang Jiang; Si-Rong Huang; Wen-Jie Ma; Yi-Qiu Yi; Ping Li; Zhong-Hui Ma; Zhi-Wei Su (Phytochemistry Reviews, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

Astrocyte-Derived CXCL10 Induces Neuronal Tau Hyperphosphorylation and Cognitive Impairments in Sepsis - Cuiping Guo; Hang Ruan; Wensheng Li; Yi Liu; Abdoul Razak Yacoubou Mahaman; Qian Guo; You Zhou; Rong Liu; Jianzhi Wang; Chenliang Zhou; Xiaochuan Wang; Shusheng Li (Neuroscience Bulletin, 2026)

Total Saponins of Panax Notoginseng Leaves Modulate the "Microglial-NLRP3/Caspase-1" Axis associated with Gut Microbial/SCFAs Alterations: Correlative Insights into Cognitive Improvement in Senescence - Lan Sun; Jiarong Du; Yuan Xu; Shanshan Wang; Yao Zhang; Rong Yuan; You Lv; Longyan Ding; Yanling Jin; Yu Ren; Xiaoman LV; Jiali Yuan; et al. (Molecular Neurobiology, 2026)

Quercetin Alleviates Postoperative Cognitive Dysfunction of Aged Mice by Regulating Microglial Polarization through Inducing miR-379-5p RNA Modification - Shu Rong Li; Long Wang; Yi Wei Li; Yi Xiao Li; Ren Wei Li; Zhi Fang Zhuo; Qing Hua Wu (Molecular Neurobiology, 2026)

Transcriptomics and Experiments Verified that Astaxanthin Reduces the Apoptosis of Nerve Cells in Ischemic Stroke by Inhibiting the Toll-like Receptor Signaling Pathway - Shan Gao; Jinjian Li; Yuetong Zhao; Zhen Wei; Chunshu Rong; Kuiyang Zuo; Xu Wang; Dexi Zhao (Molecular Neurobiology, 2026)

Echinacoside Improves Memory Function and Bone Mineral Density in the Aged SAMP8 Mouse Model - Rong Zhou; Ge Tian; Jing Yu; Rui Wang; Ning Peng; Xingzhi Guo; Rui Li (Molecular Neurobiology, 2026)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

Cholesterol and 24S-OHC Induce Neuronal Apoptosis and Necroptosis, but Not Ferroptosis Despite Elevated Iron Levels - Yinghui Li; Tingbin Xu; Jiahua Yang; Rong Liu; Yan Qu; Jun Wang (Molecular Neurobiology, 2025)

Comprehensive study of W06A7.4 and TMEM144 mediated pathways in aging: insights from Caenorhabditis elegans to human - Li Fang Wang; Xiaorong Liu; Sisi Li; Rong Li; Ran Li; Fengxia Yan; Xi Jing (Molecular Genetics and Genomics, 2025)

Trio‐WES and functional validation reveals a novel splice site variant of SLC26A3 in a case with congenital chloride diarrhea and a systematic review of SLC26A3 mutations in China - Ruixue Zhang; Hongping Li; Rong Qiang; XinRu Gao; Jinzhen Guo; Guoqiang Chen; Qin Nan; Limei Zhong; Lin Wang (Molecular Genetics and Genomics, 2025)

Novel multi-component synergistic bioink that balances biocompatibility and mechanical strength for cartilage regeneration - Zijun Ma; Wendan Jia; Xiaoyuan Wang; Rong Cheng; Lu Han; Meng Li; Xiaoning Yang; Shengbo Sang (Journal of Zhejiang University-SCIENCE B, 2025)

Utilization of river and lake dredged sediments for growing medium Preparation and its effect on the growth of alfalfa and bermudagrass: Germination, growth, and feasibility analysis - Rong Zhang; Xiangling Zhang; Bi Wu; Chen Wang; Jing Bai; Xuhao Li; Lingwei Kong; Zhouying Xu; Shilong Cao; Xinlu Xiao (Journal of Soils and Sediments, 2025)

Co-application Nitrogen and Potassium Fertilizer Enhances Nutrient Uptake and Quality of Hylocereus Undulatus by Changing Soil Properties in Karst Regions - Ting Chen; Shuhua Lu; Yanfang Tan; Bin Wang; Fang Lu; Jianxing Li; Fuzhao Huang; Rong Huang (Journal of Soil Science and Plant Nutrition, 2025)

Erosion rates of yardang landforms downstream of the Peacock River, NW China - Bai Youliang; Bo Li; Jinhong Rong; Hui Chen; Jinming Zheng; Jianshe Liu; Tan Bao; Jiangnan Jin; Chuan Wang (Journal of Sedimentary Environments, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Silencing aquaporin 1 inhibits autophagy to exert anti-rheumatoid arthritis effects in TNF-α-induced fibroblast-like synoviocytes and adjuvant-induced arthritis rats - Man-yu Zhang; Meng-qing Wang; Yan Huang; Sheng-long Gu; Meng-yuan Zhou; Ze-shan Xu; Ling-ling Li; Min Lv; Li Cai; Rong Li (Inflammation Research, 2025)

Lithospermic acid targeting heat shock protein 90 attenuates LPS-induced inflammatory response via NF-кB signalling pathway in BV2 microglial cells - Jie Guo; Chen-guang Li; Feng-yi Mai; Jing-rong Liang; Ze-hao Chen; Jiao Luo; Ming-chao Zhou; Yu-long Wang; Wen-tao Yang (Immunologic Research, 2025)

Acute systemic inflammation induces region-specific morphological remodeling of astrocytes and microglia concurrent with depression-like behavior - An-Qi Zhang; Meng-Meng Zhang; Ling-Jie Li; Mei-Xue Yuan; Rong-Yu Liu; Peng Chen; Chen-Wei Wang; Yu Wang; Jiang-Ning Zhou; Qing-Hong Shan; Xin-Ya Qin (Histochemistry and Cell Biology, 2025)

WISP2/CCN5 revealed as a potential diagnostic biomarker for endometriosis based on machine learning and single-cell transcriptomic analysis - Sheng Dou; Shaohua Ling; Weihua Nong; Bixiao Wei; Yuehua Huang; Guangjing Li; Rong Wang; Haimei Qin (Functional & Integrative Genomics, 2025)

Knockout of the Agrobacterium ILVC gene generates a valine-isoleucine auxotrophic strain for plant transformation - Yanhui Yang; Jun Lu; Tianrui Xue; Zhenli Cao; Mingjie Li; Zhongyi Zhang; Rong Wang; Tongyu Wu (Transgenic Research, 2025)

A method for detecting transgenic rapeseed using pollen collected by Apis mellifera L - Rong Yuan; Miao Wang; Zhen Li; Meiyan Hong; Li Su; Gang Wu; Xinhua Zeng (Transgenic Research, 2025)

Achnatherum inebrians tolerance to salt stress is linked with the changes of rhizosphere microbiome and root exudates - Ronggui Liu; Chao Wang; Jie Jin; Xiaoshan Zhu; Lanlan Chen; Yang Yang; Rong Zheng; Kamran Malik; Jianfeng Wang; Chunjie Li (Soil Ecology Letters, 2025)

Correction to: Antler stem cells as a novel stem cell source for reducing liver fibrosis - Xiaoli Rong; Yanyan Yang; Guokun Zhang; Haiying Zhang; Chunyi Li; Yimin Wang (Cell and Tissue Research, 2025)

High-Resolution Three-Pressure Prediction of Lianggaoshan Formation in LT1 Well block of Eastern Sichuan Risk Exploration Area - Yu-wei Wang; Ke-zhen Wan; Rong-rong Zhao; Wen-hao Li; Yang Lin; Hao Long; Hu Zhao (Applied Geophysics, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Layered manure enhances root development via soil hydrothermal optimization in ridge tillage - Bo Kang; Xun Yan; Yingjie Zhang; Rong Huang; Youlin Luo; Qiang Xu; Lihong Han; Changquan Wang; Bing Li (Plant and Soil, 2025)

Establishment of regeneration and CRISPR/Cas9-mediated genetic transformation systems in Impatiens walleriana - Huang Deng; Yulu Wu; Shanman Li; Baiyang He; Yuteng Xue; Shunming Zhang; Xue Hu; Yu Zhou; Jiwei Wang; Yuhang Wang; Songtao He; Yuhong Rong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

The potential role of hydrogen sulfide-autophagy axis in diseases - Ti Chu; Yan-Wen Wang; Lei Cao; Xue-Li Wang; Yong-Qi Fan; Yu-Hang Chen; Yi Zhang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Journal of Physiology and Biochemistry, 2025)

Climatological characteristics of tropical cyclones simulated in the global-regional integrated forecasting system (GRIST) model - Xi Cheng; Xinyao Rong; Yi Zhang; Yuqing Wang; Jian Li; Jing Xu (Climate Dynamics, 2025)

Protective effects of melatonin pretreatment on oxidative damage and immune system impairment in Eriocheir sinensis exposed to ammonia-N stress: insights from the intestine-hepatopancreas axis - Rui Wang; Hui Peng; Dapeng Li; Rong Tang (Aquaculture International, 2025)

Gut microbiota-metabolite dynamics in Sebastes schlegelii following Vibrio harveyi infection - Yindong Gu; Yongxiang Yu; Chunyuan Wang; Yingeng Wang; Zhiqi Zhang; Xiaojun Rong; Meijie Liao; Lei Qin; Bin Li; Zheng Zhang (Aquaculture International, 2025)

Nanozyme-Facilitated In-Situ Fluorogenic Ratiometric Nanosensor for Ultrasensitive and Selective Dopamine Detection - Siqi Zhou; Chen Ruan; Yuxian Hou; Lina Zou; Rong Wang; Gaiping Li (Journal of Fluorescence, 2025)

Research on quantitative monitoring of new meteorological-agricultural compound drought characteristics - Yang Yu; Lei Zhou; Wenliang Wang; Rong Tian; Jingxin Zhang; Senmiao Hu; Qingzhu Zhang; Yalan Li (Theoretical and Applied Climatology, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Characterization of the Complexity of Pore Structure in Coal and Its Relationship with Gas Desorption - Zhenyang Wang; Jiaxuan Liu; Shuhan Li; Liang Wang; Guanhua Ni; Congmeng Hao; Rong Zhang (Natural Resources Research, 2025)

Identification and Functional Analysis of Trehalose Synthesis Genes in Foxtail Millet: Insights into Low-Temperature Stress Response - Yueyue Wang; Yajun Li; Yidan Luo; Yuhua Xu; Bo Zhao; Rong Sun; Juan Zhao; Xukai Li; Yijuan Zhang; Yuanhuai Han; Hongying Li; Hui Zhang (Journal of Plant Growth Regulation, 2025)

Comparative analysis of multiple machine learning models: identifying impact factors in biochar heavy metal adsorption mechanisms - Zixin Zeng; Yingdong Wu; Wenjie Li; Lei Han; Huangshiyu Zhao; Rong Teng; Han Yuan; Ziang Wang; Sijia Li (Environmental Geochemistry and Health, 2025)

STL-GT: graph-structured learning based transformer for GNSS positioning enhancement in urban environments - Zhenni Li; Xin Li; Qianming Wang; Rong Yuan; Xuesong Tan; Maodeng Li; Marios M. Polycarpou; Shengli Xie (GPS Solutions, 2025)

Longitudinal analysis of metabolic liver disease induced by high-starch diets in largemouth bass (Micropterus salmoides) - Xixuan Huang; Xuemei Ouyang; Li Wang; Kun Xue; Haodong Yu; Chenlei Liao; Feifei Chen; Keming Rong; Xuezhen Zhang (Aquaculture International, 2025)

Unraveling the diversity of bile acid modifications by integrative mass spectrometry approaches - Nan Xing; Yu-Fei Wang; Xue Ding; Hong-Li Tan; Yi-Fang Li; Guo-Xiang Sun; Rong-Rong He; Wan-Yang Sun (Science China Life Sciences, 2025)

Cloning and Bioinformatics Analysis of the StGRAS46 Gene in Potato - Shulin Wang; GuoHong Weng; Rong Zhang; Wei Li; YongJie Bai; YaHui Zhang; JianWu Li (Potato Research, 2025)

Potential genetic characteristics of Bacillus velezensis LZUR632 enhance the resistance of Achnatherum inebrians to Cd stress by altering rhizosphere microbial community composition and functional genes - Jie Jin; Chao Wang; Ronggui Liu; Rong Zheng; Maohua Deng; Jianfeng Wang; Chunjie Li (Plant and Soil, 2025)

A synergistic water-saving strategy combining stage-specific irrigation and application of exogenous thiamine enhances drought resistance of Xinjiang cotton - Fuxiang Zhao; Linjie Xia; Simin Sun; Hang Li; Yuxuan Rong; Yuxin Wang; Xuwen Wang; Xianhui Kong; Longfu Zhu; Xianlong Zhang; Yu Yu; Xiyan Yang (Plant and Soil, 2025)

Six new combinations in Prunus sensu lato (Rosaceae) from east Asia - Meng Li; Jia-Ning Zhou; Xian-Rong Wang; Xian-Gui Yi; Muhammad Idrees (Kew Bulletin, 2025)

Seismic response analysis of the Yellow River terrace based on the spectral ratio method - Xingyu Ma; Lanmin Wang; Rong Xu; Qi Li (Earth Science Informatics, 2025)

Molecular characterization of a novel chrysovirus isolated from the phytopathogenic fungus Fusarium commune - Wen Xin Huang; Li E Yang; Yan Bin Huang; Tao Sha Xu; Jie Zhong; Ya Rong Wang; Yan Song Xiao (Archives of Virology, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Improvement of soil quality, microbial community structure and function with the application of microbial agent in continuous cropping of Pinellia ternata - Rong Deng; Yuan Zhao; Lin Chen; Siqi Li; Linwei Jiang; Xiaomei Wang; Tao Yang; Xueping Tian; Jun Huang (Plant and Soil, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Enhancement of Ca2+ Signal Strength in Astrocytes in the Lateral Septum Improves Cognitive Disorders in Mice After Hemorrhagic Shock and Resuscitation - Wen-Guang Li; Lan-Xin Li; Rong-Xin Song; Xu-Peng Wang; Shi-Yan Jia; Xiao-Yi Ma; Jing-Yu Zhang; Gang-Feng Yin; Xiao-Ming Li; Li-Min Zhang (Neuroscience Bulletin, 2025)

IFN-γ2 enhances proliferation and differentiation of muscle cells: a novel target of natural grass feeding mode improving muscle quality in grass carp (Ctenopharyngodon idella) - Huijie Chen; Yin Wang; Jieya Liu; Qiushi Yang; Jiamin Lu; Tingting Xu; Rong Tang; Dapeng Li (Fish Physiology and Biochemistry, 2025)

Machine learning-based design, screening, and activity validation of topoisomerase I inhibitors - Ya-Kun Zhang; Jian-Bo Tong; Jia-Le Li; Rong Wang; Yan-Rong Zeng (Molecular Diversity, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Fine mapping and functional validation reveal two incomplete dominant genes controlling photoperiod-sensitive flowering in Gossypium hirsutum - Langjing Hua; Chao Xu; Xiao Liu; Zhicheng Wang; Tengyu Li; Yuefen Cao; Xin Hu; Yurong Jiang; Junkang Rong (Theoretical and Applied Genetics, 2025)

The effect of soil microbial functional groups, abiotic and biotic factors on plant functional groups: insights from a tropical rainforest in Southwest China - Yanxuan Chen; Xiaobo Huang; Rong Tang; Rui Zhang; Cong Li; Tongli Wang; Jianrong Su; Shuaifeng Li (Plant and Soil, 2025)

Plant and microbial β diversities are better predictors of ecosystem functioning than their α diversities, but aridity weakens these associations - Lu Zhang; Shilong Lei; Rong Qian; Raúl Ochoa-Hueso; Xiangtao Wang; Jie Wang; Lirong Liao; Guobin Liu; Qiang Li; Chao Zhang (Plant and Soil, 2025)

A hybrid coupled model for the tropical Pacific constructed by integrating ROMS with a statistical atmospheric model - Rong-Hua Zhang; Wenzhe Zhang; Yang Yu; Yinnan Li; Feng Tian; Chuan Gao; Hongna Wang (Journal of Oceanology and Limnology, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Glymphatic Impairment Associated with Neurocognitive Dysfunction in Moyamoya Disease - Chaofan Zeng; Yuanren Zhai; Peicong Ge; Chenglong Liu; Xiaofan Yu; Wei Liu; Junsheng Li; Qiheng He; Xingju Liu; Xun Ye; Qian Zhang; Rong Wang; et al. (Translational Stroke Research, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

Recent advances and future research directions in the study of land-atmosphere interaction in northern China since the beginning of the 21st century - Qiang Zhang; Rong Wang; Ping Yue; Hongyu Li; Sheng Wang; Jian Zeng; Liang Zhang; Zesu Yang; Suping Wang; Jie Zhang; Liang Qiao; Hongli Zhang; et al. (Science China Earth Sciences, 2025)

Transcriptome and Metabolome Combine to Analyze the Mechanism of Leaf Coloration Formation in Aeonium arboreum ‘Pink Sybil’ - Suhua Li; Rong Zhao; Haozhang Han; Lihua Zhang; Fang Wang; Nan Zhang; Rong Dong (Plant Molecular Biology Reporter, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Identification and validation of mitochondrial endoplasmic reticulum membrane-related genes in atherosclerosis - Li-Rong Wang; Chun-Xi Zhang; Lv-Bo Tian; Jie Huang; Li-Jun Jia; Hao Tao; Neng-Wei Yu; Bing-Hu Li (Mammalian Genome, 2025)

The impact of YTHDF2-mediated NCOA4 methylation on myocardial ferroptosis - Xiaoqi Shao; Mengxian Sun; Ruonan Wang; Mingyang Leng; Hongtao Diao; Xu Li; Dongwei Wang; Kaili Wu; Liang Wang; Wen Lv; Xianglu Rong; Yue Zhang (Apoptosis, 2025)

Gut microbiota and serum metabolomics unveil the role of Phellinus ribis polysaccharides in improving Alzheimer's disease symptoms in senescence-accelerated mice - Zhiyuan Zhang; Shuai Wang; Rong Rong; Guoying Zhang; Zheng Li; Yuanyuan Li; Rongxiang Wang; Yuhong Liu; Kejian Li (Metabolic Brain Disease, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

ADAMDEC1 promotes cervical squamous cell carcinoma by enhancing the JAK/STAT signaling pathway through modulation of TYMP - Beibei Wang; Qingsong Zhang; Lihua Wang; Huiwen Su; Li Zhou; Rong Zhang; Qiangkun Wan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Recent advances in the role of gasotransmitters in necroptosis - Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Ti Chu; Yan-Wen Wang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Integrating spatial transcriptomics and single-nucleus RNA-seq revealed the specific inhibitory effects of TGF-β on intramuscular fat deposition - Xiaoyu Wang; Chuchu Chen; Chenggan Li; Xiaochang Chen; Rong Xu; Meilin Chen; Yongpeng Li; Yihao Liu; Xiaohong Liu; Yaosheng Chen; Delin Mo (Science China Life Sciences, 2025)

Ventral Hippocampal CA1 GADD45B Regulates Susceptibility to Social Stress by Influencing NMDA Receptor-Mediated Synaptic Plasticity - Mengbing Huang; Jian Bao; Xiaoqing Tao; Yifan Niu; Kaiwei Li; Ji Wang; Xiaokang Gong; Rong Yang; Yuran Gui; Hongyan Zhou; Yiyuan Xia; Youhua Yang; et al. (Neuroscience Bulletin, 2025)

Transcutaneous Auricular Vagus Stimulation Attenuates LPS-Induced Depression-Like Behavior by Regulating Central α7nAChR/JAK2 Signaling - Junying Wang; Yu Wang; Yu Chen; Jinling Zhang; Yue Zhang; Shaoyuan Li; Haohan Zhu; Xingke Song; Liwei Hou; Lei Wang; Yifei Wang; Zixuan Zhang; et al. (Molecular Neurobiology, 2025)

Inhibition of STRA6 suppresses NSCLC growth via blocking STAT3/SREBP-1c axis-mediated lipogenesis - Yue Zhou; Rong Zhou; Ning Wang; Tingfeng Zhao; Pan Qiu; Chenzi Gao; Meijia Chang; Ning Lin; Xu Zhang; John Zhong Li; Qian Wang (Molecular and Cellular Biochemistry, 2025)

Hereditary non-spherocytic hemolytic anemia with GPI mutations successfully treated with allogeneic hematopoietic stem cell transplantation: a first report of two cases - Huimin Li; Jiali Wang; Liucheng Rong; Jian Li; Yao Xue; Yongjun Fang; Yaping Wang (Journal of Molecular Medicine, 2025)

Leukemia inhibitory factor promotes growth and maintains stemness in giant panda MSCs - Feiping Li; Yuliang Liu; Mengshi Zhang; Shenfei Wang; Xianbiao Hu; Xiangyu Liu; Rong Hou; Kailai Cai (In Vitro Cellular & Developmental Biology - Animal, 2025)

Late Quaternary slip rate of the Northern Margin Fault of the Huaizhuo Basin in the North China Block and its seismological implications - Lu-wei Li; Zhong-yuan Yu; Chun-miao Qiu; Wen-xuan Wang; Qian Zhao; Rong-ying Zheng; Yan-Lin Yang (Applied Geophysics, 2025)

α-asarone activates mitophagy to relieve diabetic encephalopathy via inhibiting apoptosis and oxidative stress - Xiao-dan Yan; Rong-hua Fan; Yu Wang; Xiao-xu Duan; Xuan Wei; Lin-sen Li; Qing Yu (Metabolic Brain Disease, 2025)

Advancing treatment strategies against MRSA: unveiling the potency of tubuloside A in targeting sortase A and mitigating pathogenicity - Yangming Xu; Yanhe Luan; Rong Wang; Zhengjie Su; Li Wang; Yinghui Liu; Guangzhi Jiang; Bingmei Wang (World Journal of Microbiology and Biotechnology, 2025)

Different contributions of microbial and plant residues to soil organic carbon accumulation during planted forest and abandoned farmland restoration, Loess Plateau, China - Hongjian Hao; Rong Wang; Shicai Li; Duo Pian; Ning Peng; Ahejiang Sailike; Zhouchang Yu; Jiayi Shi; Xingbo Wang; Zihan Wang; Wei Zhang (Plant and Soil, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Influence of Influent Load on Nitrification/Denitrification with MBBR for Oil Shale Retorting Wastewater Treatment: Performance and Microbial Community Structure - Rong-xin Zhang; Yi Liu; Dian-nan Huang; Li Zhang; Xing-guan Ma; Peng-fei Yu; Chuang Liu; Yong-yong Wang (Water, Air, & Soil Pollution, 2025)

Comparison of molecular testing methods for diagnosing non-tuberculous mycobacterial infections - Leilei Wang; Yu Chen; Qingqing Wang; Jue Pan; Rong Bao; Wenting Jin; Yumeng Yao; Tingting Fang; Na Li; Sichun Luan; Xiaoyu Yin; Le Qin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Evaluation of metagenomic next-generation sequencing (mNGS) combined with quantitative PCR: cutting-edge methods for rapid diagnosis of non-invasive fungal rhinosinusitis - Xiao Liu; Shaoqin Zhou; Rong Yan; Caifeng Xia; Ruoning Xue; Zhe Wan; Ruoyu Li; Sybren de Hoog; Sarah A. Ahmed; Quangui Wang; Yinggai Song (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Pseudomonas chlororaphis ZH2: Evaluation of the Biocontrol Potential of Continuous Cropping Obstacles on the Basis of Genome Analysis, Autotoxic Substance Degradation and In Vitro Antifungal Activity - Rong Xiao; Chunfen Zhang; Shu Deng; Ciqiong Niu; Quan Li; Junjie Sun; Juantao Liu; Jianping Wang (Current Microbiology, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Correction: Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

p-Smad3 differentially regulates the cytological behavior of osteoclasts before and after osteoblasts maturation - Jiapeng Ye; Zhen Hua; Jirimutu Xiao; Yang Shao; Shaoshuo Li; Heng Yin; Mao Wu; Yi Rong; Bowen Hong; Yang Guo; Yong Ma; Jianwei Wang (Molecular Biology Reports, 2024)

Single-cell transcriptome analysis of the mouse lungs during the injury and recovery periods after lipopolysaccharide administration - Hou-Ping Wang; Jian He; Jian-Rong He; Dan-Dan Li; He Huang; Bing Chen (Inflammation Research, 2024)

Active tectonic deformation and its seismic–geological significance of boundary faults of the Daxing Uplift and Langgu–Dachang Depression, Beijing Plain, China - Rong-Ying Zheng; Zhong-Yuan Yu; Bai-Xu Chen; Lu-Wei Li; Yi-Cheng Wang (Applied Geophysics, 2024)

Methylobacterium nigriterrae sp. nov., isolated from black soil - Le-Bin Chen; Yu-Ting OuYang; Lan Liu; Pin-Jiao Jin; Rong-Rong Huang; Wen-Yi Pan; Ying Wang; Jia-Ying Xing; Ting-Ting She; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

White matter lesions contribute to motor and non-motor disorders in Parkinson’s disease: a critical review - Yue-Qi Jiang; Qiu-Zhu Chen; Yang Yang; Cai-Xia Zang; Jing-Wei Ma; Jin-Rong Wang; Yi-Rong Dong; Ning Zhou; Xing Yang; Fang-Fang Li; Xiu-Qi Bao; Dan Zhang (GeroScience, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

Influenza A Virus PB1-F2 Induces Affective Disorder by Interfering Synaptic Plasticity in Hippocampal Dentate Gyrus - Saiying Wang; Haijun Zhang; Rui Liu; Peijun Han; Qi Yang; Caiyan Cheng; Yue Chen; Zheng Rong; Chang Su; Fei Li; Gaofei Wei; Minggao Zhao; et al. (Molecular Neurobiology, 2024)

Label-Free Detection of Programmed Death-Ligand 1 for Prognosis Using a Truncated Aptamer and SYBR Green I - Ling Li; Zheng-Ling Li; Wei Wang; Xin-Xin Long; Ping Liu; Guo-Tian Wang; Shi-Qing Sun; Rong-Lian Du (Journal of Fluorescence, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Role of NF-κB signaling pathway in H2O2-induced oxidative stress of hiPSCs - Jian Qin; Jie Yang; Jun Li; Dipeng Zhao; Jie An; Zhuhui Zhai; Hejie Wang; Junling Li; Minmin Dou; Rong Du (In Vitro Cellular & Developmental Biology - Animal, 2024)

Investigating protistan predators and bacteria within soil microbiomes in agricultural ecosystems under organic and chemical fertilizer applications - Chen Liu; Zeyuan Zhou; Shuo Sun; Qi Zhang; Shiqi Sun; Xinnan Hang; Mohammadhossein Ravanbakhsh; Zhong Wei; Rong Li; Shimei Wang; Wu Xiong; George A. Kowalchuk; et al. (Biology and Fertility of Soils, 2024)
Organic farming can enhance biodiversity and soil health and is a sustainable alternative to conventional farming. Yet, soil protists especially protistan predators, have received inadequate attention, and their contributions to the sustainability of organic farming remained underexplored. In this study, we examined soil microbial communities from 379 samples, including both organic and chemically fertilized soils from China. Our findings revealed higher bacterial diversity and increases in plant-beneficial bacteria in organically farmed soils. Notably, organic farming systems facilitated dynamic predator-prey interactions, which may be disrupted by the application of chemical fertilizers. Additionally, organic farming enriched protistan predators, enhancing the relative abundance of functional PGPR, thus improving soil health. We further conducted a case study highlighting the critical role of organic matter in sustaining protistan predator populations and their interactions with bacteria. We propose the crucial contributions of organic inputs for supporting protistan predators and the interplay of predator-prey, ultimately enhancing soil functions and promoting agricultural sustainability.

Glutamine deprivation in glioblastoma stem cells triggers autophagic SIRT3 degradation to epigenetically restrict CD133 expression and stemness - Zhengcao Xing; Xianguo Jiang; Yalan Chen; Tiange Wang; Xiaohe Li; Xiangyun Wei; Qiuju Fan; Jie Yang; Hongmei Wu; Jinke Cheng; Rong Cai (Apoptosis, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

MicroRNA dynamics in irisin-mediated signaling pathways within adipose tissue - Ming-Yun Ho; Kai-Pin Chiu; Ming-Lung Tsai; Jih-Kai Yeh; Yi-Chun Huang; Yan-Rong Li; Horng-Dar Wang; I-Chang Hsieh; Ming-Shien Wen; Chao-Yung Wang (Journal of Biosciences, 2024)

Cloning and functional identification of anthocyanin synthesis-regulating transcription factor AaMYB4 in Aeonium arboreum Webb & Berthel ‘Halloween’ - Rong Zhao; Su-Hua Li; Hao-Zhang Han; Li-Hua Zhang; Fang Wang; Nan Zhang (Brazilian Journal of Botany, 2024)

TBC1D1 is an energy-responsive polarization regulator of macrophages via governing ROS production in obesity - Qi Wang; Ping Rong; Wen Zhang; Xinyu Yang; Liang Chen; Ye Cao; Minjun Liu; Weikuan Feng; Qian Ouyang; Qiaoli Chen; Hailong Li; Hui Liang; et al. (Science China Life Sciences, 2024)

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

The romantic history of signaling pathway discovery in cell death: an updated review - Lei-Yun Wang; Xing-Jian Liu; Qiu-Qi Li; Ying Zhu; Hui-Li Ren; Jia-Nan Song; Jun Zeng; Jie Mei; Hui-Xiang Tian; Ding-Chao Rong; Shao-Hui Zhang (Molecular and Cellular Biochemistry, 2024)

Soil Organic Matter and Amorphous Oxides Determine the Surface Electrochemical Properties of Purple Soil Under Long-Term Inorganic and Organic Fertilization - Jun Xie; Rong Huang; Dongxun Wu; Wencai Dai; Zhengxin Deng; Yue Li; Xiaojun Shi; Yueqiang Zhang; Zifang Wang; Ming Gao (Journal of Soil Science and Plant Nutrition, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Empagliflozin attenuates doxorubicin-impaired cardiac contractility by suppressing reactive oxygen species in isolated myocytes - Rong Lin; Xiaodong Peng; Yukun Li; Xuesi Wang; Xinmeng Liu; Xingze Jia; Chengjun Zhang; Nian Liu; Jianzeng Dong (Molecular and Cellular Biochemistry, 2024)

Investigation of New Integrated Drought Monitoring Model Taking into Account the Effects of Climate Anomalies - Lei Zhou; Wenliang Wang; Congcong He; Siyu Wang; Yalan Li; Rong Tian; Cheng Du (Journal of the Indian Society of Remote Sensing, 2024)

Identification of the Galactinol Synthase (GolS) Family in Medicago truncatula and Expression Analysis Under Abiotic Stress and Phytohormone Treatment - Hua Li; Ying Di Gao; Li Qing Kang; Hong Yang Yu; Li Ming Zeng; Yi Hua Wang; Rong Rong Chen; Jian Bo Song (Journal of Plant Growth Regulation, 2024)

Mass cytometry revealed the circulating immune cell landscape across different Suzuki stages of Moyamoya disease - Chenglong Liu; Peicong Ge; Bojian Zhang; Liujia Chan; Yuheng Pang; Chuming Tao; Junsheng Li; Qiheng He; Wei Liu; Siqi Mou; Zhiyao Zheng; Zhikang Zhao; et al. (Immunologic Research, 2024)
Moyamoya disease (MMD) is a cerebrovascular disorder marked by progressive arterial narrowing, categorized into six stages known as Suzuki stages based on angiographic features. Growing evidence indicates a pivotal role of systemic immune and inflammatory responses in the initiation and advancement of MMD. This study employs high-dimensional mass cytometry to reveal the immunophenotypic characteristics of peripheral blood immune cells (PBMCs) at various Suzuki stages, offering insights into the progression of MMD. PBMC samples from eight patients with early-stage MMD (Suzuki stages II and III) and eight patients with later-stage MMD (Suzuki stages IV, V, and VI) were analyzed using high-dimensional mass cytometry to evaluate the frequency and phenotype of immune cell subtypes. We identified 15 cell clusters and found that the immunological features of early-stage MMD and later-stage MMD are composed of cluster variations. In this study, we confirmed that, compared to later-stage MMD, the early-stage MMD group exhibits an increase in non-classical monocytes. As the Suzuki stage level increases, the proportions of plasmacytoid DCs and monocyte-derived DCs decrease. Furthermore, T cells, monocytes, DCs, and PMN-MDSCs in the early-stage MMD group show activation of the canonical NF-κB signaling pathway. We summarized and compared the similarities and differences between early-stage MMD patients and later-stage MMD patients. There is a potential role of circulating immune dysfunction and inflammatory responses in the onset and development of MMD.

Deubiquitinating enzyme OTUD4 stabilizes RBM47 to induce ATF3 transcription: a novel mechanism underlying the restrained malignant properties of ccRCC cells - Ziyao Li; Ye Tian; Huafeng Zong; Xuelei Wang; Dongyang Li; Adili Keranmu; Shiyong Xin; Bowen Ye; Rong Bai; Weihua Chen; Guosheng Yang; Lin Ye; et al. (Apoptosis, 2024)

Examining the Potential of ChatGPT on Biomedical Information Retrieval: Fact-Checking Drug-Disease Associations - Zhenxiang Gao; Lingyao Li; Siyuan Ma; Qinyong Wang; Libby Hemphill; Rong Xu (Annals of Biomedical Engineering, 2024)

Multiple scenario land use simulation based on a coupled MOGA-PLUS model: a case of the Yellow River Basin - Guanghui Li; Yinghui Chang; Pengyan Zhang; Qianxu Wang; Zhuo Chen; Xinyue Zhang; Guangrui Xing; Rong Lu; Mengfan Li; Lei Gu (Environmental Science and Pollution Research, 2024)

Fibroblast-localized lncRNA CFIRL promotes cardiac fibrosis and dysfunction in dilated cardiomyopathy - Shuai Yuan; Xudong Zhang; Jiabing Zhan; Rong Xie; Jiahui Fan; Beibei Dai; Yanru Zhao; Zhongwei Yin; Qian Liu; Dao Wen Wang; Huaping Li; Chen Chen (Science China Life Sciences, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Viperin inhibits interferon-γ production to promote Mycobacterium tuberculosis survival by disrupting TBK1-IKKε-IRF3-axis and JAK-STAT signaling - Yao Liang; Yun Liang; Qi Wang; Qianna Li; Yingqi Huang; Rong Li; Xiaoxin Pan; Linmiao Lie; Hui Xu; Zhenyu Han; Honglin Liu; Qian Wen; et al. (Inflammation Research, 2024)
Objectives and design As an interferon-inducible protein, Viperin has broad-spectrum antiviral effects and regulation of host immune responses. We aim to investigate how Viperin regulates interferon-γ (IFN-γ) production in macrophages to control Mycobacterium tuberculosis (Mtb) infection. Methods We use Viperin deficient bone-marrow-derived macrophage (BMDM) to investigate the effects and machines of Viperin on Mtb infection. Results Viperin inhibited IFN-γ production in macrophages and in the lung of mice to promote Mtb survival. Further insight into the mechanisms of Viperin-mediated regulation of IFN-γ production revealed the role of TANK-binding kinase 1 (TBK1), the TAK1-dependent inhibition of NF-kappa B kinase-epsilon (IKKε), and interferon regulatory factor 3 (IRF3). Inhibition of the TBK1-IKKε-IRF3 axis restored IFN-γ production reduced by Viperin knockout in BMDM and suppressed intracellular Mtb survival. Moreover, Viperin deficiency activated the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway, which promoted IFN-γ production and inhibited Mtb infection in BMDM. Additionally, a combination of the anti-TB drug INH treatment in the absence of Viperin resulted in further IFN-γ production and anti-TB effect. Conclusions This study highlights the involvement of TBK1-IKKε-IRF3 axis and JAK-STAT signaling pathways in Viperin-suppressed IFN-γ production in Mtb infected macrophages, and identifies a novel mechanism of Viperin on negatively regulating host immune response to Mtb infection.

A Novel FD3 Framework for Carbon Emissions Prediction - Houtian He; Tongyan Liu; Qianqian Li; Jiaru Yang; Rong-Long Wang; Shangce Gao (Environmental Modeling & Assessment, 2024)

Dynamic causal modeling analysis reveals the modulation of motor cortex and integration in superior temporal gyrus during multisensory speech perception - Ting Zou; Liyuan Li; Xinju Huang; Chijun Deng; Xuyang Wang; Qing Gao; Huafu Chen; Rong Li (Cognitive Neurodynamics, 2024)
The processing of speech information from various sensory modalities is crucial for human communication. Both left posterior superior temporal gyrus (pSTG) and motor cortex importantly involve in the multisensory speech perception. However, the dynamic integration of primary sensory regions to pSTG and the motor cortex remain unclear. Here, we implemented a behavioral experiment of classical McGurk effect paradigm and acquired the task functional magnetic resonance imaging (fMRI) data during synchronized audiovisual syllabic perception from 63 normal adults. We conducted dynamic causal modeling (DCM) analysis to explore the cross-modal interactions among the left pSTG, left precentral gyrus (PrG), left middle superior temporal gyrus (mSTG), and left fusiform gyrus (FuG). Bayesian model selection favored a winning model that included modulations of connections to PrG (mSTG → PrG, FuG → PrG), from PrG (PrG → mSTG, PrG → FuG), and to pSTG (mSTG → pSTG, FuG → pSTG). Moreover, the coupling strength of the above connections correlated with behavioral McGurk susceptibility. In addition, significant differences were found in the coupling strength of these connections between strong and weak McGurk perceivers. Strong perceivers modulated less inhibitory visual influence, allowed less excitatory auditory information flowing into PrG, but integrated more audiovisual information in pSTG. Taken together, our findings show that the PrG and pSTG interact dynamically with primary cortices during audiovisual speech, and support the motor cortex plays a specifically functional role in modulating the gain and salience between auditory and visual modalities.

CYTOR-NFAT1 feedback loop regulates epithelial-mesenchymal transition of retinal pigment epithelial cells - Rong Zhang; Lin Wang; Yang Li; Yan Liu; Kui Dong; Yajing Pei; Junmei Zhao; Gang Liu; Jing Li; Xiaodan Zhang; Tong Cui; Yan Gao; et al. (Human Cell, 2024)

Ceria nanoparticles: biomedical applications and toxicity - Xiaoxuan Fu; Peng Li; Xi Chen; Yuanyuan Ma; Rong Wang; Wenxuan Ji; Jiakuo Gu; Bowen Sheng; Yizhou Wang; Zhuhong Zhang (Journal of Zhejiang University-SCIENCE B, 2024)

Ginsenoside Rg1 Alleviates Sepsis-Induced Acute Lung Injury by Reducing FBXO3 Stability in an m6A-Dependent Manner to Activate PGC-1α/Nrf2 Signaling Pathway - Rong Liu; Qiang Wang; Yao Li; Ruixue Wan; Ping Yang; Dexing Yang; Jiefu Tang; Jiafei Lu (The AAPS Journal, 2024)

Fine mapping and candidate gene analysis of qSRC3 controlling the silk color in maize (Zea mays L.) - Xueying Wang; Yang Zhou; Chong You; Jinchang Yang; Zhengjie Chen; Dengguo Tang; Jixing Ni; Peng Li; Le Wang; Kaili Zhu; Wujiao Deng; Haimei Wu; et al. (Theoretical and Applied Genetics, 2024)

Evolution of Permeability and Gas Seepage in Deep Coal Under 3D Stress - Tenglong Rong; Pengju Liu; Jiawei Wang; Xiaojian Ren; Xianzhong Li; Guoying Wang (Natural Resources Research, 2024)

Modulation of plasmacytoid dendritic cell and CD4+ T cell differentiation accompanied by upregulation of the cholinergic anti-inflammatory pathway induced by enterovirus 71 - Li Li; Rong-Wei Huang; Xiao-Ning Liu; Xiao-Yi Xiang; Yuan-Tao Zhou; Xing-Xing Feng; Lv-Yuan Tao; Jia Yu; Qin Yi; Yan-Chun Wang; Xiao-Mei Liu (Archives of Virology, 2024)

Copper-doped Lanthanide Coordination Polymers as Luminescent Nanoenzyme for Ratiometric Sensing of H2O2 and Glutathione - Xinru Wu; Chen Ruan; Xinyue Zhu; Lina Zou; Rong Wang; Gaiping Li (Journal of Fluorescence, 2024)

Adsorption characteristics of Ag+ on sphalerite surface: a combined experimental and first-principle study - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Environmental Science and Pollution Research, 2024)

Damming-associated landscape change benefits a wind-dispersed pioneer plant species - Hang Ji; Yong-Rong He; Hong-Yue Li; Ling Lu; Jia-Hui Li; Jie Zou; Rong Wang; Jun-Yin Deng; Xiao-Yong Chen (New Forests, 2024)

Soil Carbon Mineralization and Aggregate Distribution in Various Tillage Practices of Rice–Wheat Cropping System: A Field and Laboratory Study - Naeem Ahmad; Ahmad Latif Virk; Muhammad Bilal Hafeez; Zheng-Rong Kan; Zujiao Shi; Rui Wang; Hafiz Muhammad Waleed Iqbal; Muhammad Ishaq Asif Rehmani; Xiaoli Wang; Rattan Lal; Jun Li (Journal of Soil Science and Plant Nutrition, 2024)

New materials of Pliorhinus ringstroemi from the Linxia Basin (Late Miocene, eastern Asia) and their taxonomical and evolutionary implications - Shijie Li; Oscar Sanisidro; Shiqi Wang; Rong Yang; Tao Deng (Journal of Mammalian Evolution, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Ferroptosis: underlying mechanisms and involvement in neurodegenerative diseases - Yi Wang; HongJing Li; QianXiong He; Rong Zou; JinRui Cai; Lin Zhang (Apoptosis, 2024)

Disclosing phototransformation mechanisms of decabromodiphenyl ether (BDE-209) in different media by simulated sunlight: Implication by compound-specific stable isotope analysis - Guoguang Wang; Chuanyuan Li; Shuaihao Liu; Ziao Xing; Pengxu Guo; Zixuan Hao; Maojiao Li; Haixia Wang; Guangzhi Rong; Yu Liu (Environmental Science and Pollution Research, 2024)

Associations of legacy perfluoroalkyl and polyfluoroalkyl substances, alternatives, and isomers with gestational diabetes mellitus and glucose homeostasis among women conceiving through assisted reproduction in Shanghai, China - Dandan Mao; Guodong Ding; Zixia Wang; Jiuru Zhao; Hong Li; Xiaoning Lei; Jiaqi Zheng; Yan Zhang; Rong Shi; Tao Yuan; Zhiwei Liu; Yu Gao; et al. (Environmental Science and Pollution Research, 2024)

RETRACTED ARTICLE: Liquiritin reduces ferroptosis in doxorubicin-induced cardiotoxicity through targeting SLC7A11/GPX4 pathway - Mei Wang; Meng Liu; Lijing Tang; Lixian Shen; Junhui Xiao; Rong Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Driving model of land use change on the evolution of carbon stock: a case study of Chongqing, China - Luoshan Zheng; Yangbing Li; Yan Chen; Rong Wang; Shijie Yan; Chunhua Xia; Bing Zhang; Jing’an Shao (Environmental Science and Pollution Research, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Characterization of the Oral Microbiota in Captive Sichuan Golden Snub-nosed Monkeys (Rhinopithecus roxellana) of Different Ages - Rong Chen; Xinyi Liu; Meirong Li; Xiaojuan Xu; Ran Lv; Yuanyuan Chen; Guodong Wang; Changlin Deng; Nan Chen; Ting Jia; Siteng Wang; Guangjin Liu (International Journal of Primatology, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Synergistic leaching process for ion-exchange ammonium from weathered crust elution deposited rare earth tailings with potassium magnesium compound eluent - Xiaoju Li; Junxia Yu; Xiaodi Li; Guoping Song; Ze Ouyang; Rong Wang; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi (Environmental Science and Pollution Research, 2023)

Application of Induced Pluripotent Stem Cells in Malignant Solid Tumors - Rong He; Zhijie Weng; Yunkun Liu; Bingzhi Li; Wenxuan Wang; Wanrong Meng; Bo Li; Longjiang Li (Stem Cell Reviews and Reports, 2023)
In the past decade, induced pluripotent stem cells (iPSCs) technology has significantly progressed in studying malignant solid tumors. This technically feasible reprogramming techniques can reawaken sequestered dormant regions that regulate the fate of differentiated cells. Despite the evolving therapeutic modalities for malignant solid tumors, treatment outcomes have not been satisfactory. Recently, scientists attempted to apply induced pluripotent stem cell technology to cancer research, from modeling to treatment. Induced pluripotent stem cells derived from somatic cells, cancer cell lines, primary tumors, and individuals with an inherited propensity to develop cancer have shown great potential in cancer modeling, cell therapy, immunotherapy, and understanding tumor progression. This review summarizes the evolution of induced pluripotent stem cells technology and its applications in malignant solid tumor. Additionally, we discuss potential obstacles to induced pluripotent stem cell technology. Graphical Abstract

Failure Modes of Jointed Granite Subjected to Weak Dynamic Disturbance Under True-Triaxial Compression - Ben-Guo He; Lei Wang; Xia-Ting Feng; Rong-Li Zhen (Rock Mechanics and Rock Engineering, 2023)

Positive relationships between species diversity and genetic diversity on a local scale at Mt. Wu Yi, China - Lei Xie; YueYao Feng; Rong Zhao; Ting Lv; NingJie Wang; Yao Li; Xiao Zheng; ShuiFei Chen; Hui Ding; YanMing Fang (Biodiversity and Conservation, 2023)

How does green credit policy affect innovation efficiency of heavily polluting firms? Evidence from a quasi-natural experiment in China - Rong Wang; Li Ye; Ying Fang (Environment, Development and Sustainability, 2023)

Citrus medica var. Sarcodactylus (Siebold ex Hoola van Nooten) Swingle: an insight into its botany, traditional uses, phytochemistry, and pharmacological properties - Qin-Ge Ma; Jie Chen; Li-Hua Chen; Guang Wu; Mei-Ning Zhu; Neng-Xin He; Qin-Yuan Wang; Zhi-Pei Sang; Cai-Qing Zhu; Yong-Zhong Wu; Rong-Rui Wei (Phytochemistry Reviews, 2023)

Characterization of the fragmented mitochondrial genome of domestic pig louse Haematopinus suis (Insecta: Haematopinidae) from China - Rong Li; Yu Nie; Yi-Tian Fu; Yuan-Ping Deng; Wei Wang; Ping-Ping Ma; Guo-Hua Liu (Systematic Parasitology, 2023)

Which molecular marker is better? Comparative analyses of COI and ITS2 in molecular identification of Trichogramma (Hymenoptera: Trichogrammatidae) - Ao-Kai Wang; Fang-Yi Li; De-Sen Wang; Yu-Rong He; Yuan-Xi Li; Zhi-Chao Yan (BioControl, 2023)

Moderately delayed maturation of composting promotes the reduction of guild-plant pathogenic fungi within vegetable waste - Zijian Lv; Chengyuan Tao; Jiawei Zhang; Zongzhuan Shen; Dongsheng Wang; Bei Wang; Hongjun Liu; Rong Li (Environmental Science and Pollution Research, 2023)

Transcriptome and Metabolome Integrated Analysis Reveals the Mechanism of Cinnamomum bodinieri Root Response to Alkali Stress - Haozhang Han; Lihua Zhang; Suhua Li; Rong Zhao; Fang Wang; Rong Dong; Xiaoli Wang (Plant Molecular Biology Reporter, 2023)

Correction to: Increasing net ecosystem carbon budget and mitigating global warming potential with improved irrigation and nitrogen fertilization management of a spring wheat farmland system in arid Northwest China - Yue Li; Rong Wang; Zhijun Chen; Yunwu Xiong; Quanzhong Huang; Guanhua Huang (Plant and Soil, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Spautin-1 Protects Against Mild TBI-Induced Anxiety-Like Behavior in Mice via Immunologically Silent Apoptosis - Hui-Tao Miao; Rong-Xin Song; Yue Xin; Lu-Ying Wang; Jin-Meng Lv; Na-Na Liu; Zhi-You Wu; Wei Zhang; Yan Li; Dong-Xue Zhang; Li-Min Zhang (NeuroMolecular Medicine, 2023)

Soil-water characteristic surface model of soil-rock mixture - Kui Wang; Ying Hui; Chuan Zhou; Xue Li; Yao Rong (Journal of Mountain Science, 2023)

The association between greenery type and gut microbiome in schizophrenia: did all greenspaces play the equivalent role? - Ning Wei; Shusi Wang; Xuanxuan Li; Rubing Pan; Weizhuo Yi; Jian Song; Li Liu; Jintao Liu; Jiajun Yuan; Rong Song; Jian Cheng; Hong Su (Environmental Science and Pollution Research, 2023)

Geochemical behaviors of uranium and thorium during weathering and pedogenesis of carbonate rock: constraint from their speciation - Qiang Ma; Bing-jie Zhou; Zhi-gang Feng; Xiao-long Wang; Rong Chen; Pei-shan Li; Chong Huang (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Increasing net ecosystem carbon budget and mitigating global warming potential with improved irrigation and nitrogen fertilization management of a spring wheat farmland system in arid Northwest China - Yue Li; Rong Wang; Zhijun Chen; Yunwu Xiong; Quanzhong Huang; Guanhua Huang (Plant and Soil, 2023)

Involvement of Abnormal p-α-syn Accumulation and TLR2-Mediated Inflammation of Schwann Cells in Enteric Autonomic Nerve Dysfunction of Parkinson’s Disease: an Animal Model Study - Wenwen Jiang; Yue Cheng; Ye Wang; Jing Wu; Zhe Rong; Li Sun; Yan Zhou; Kezhong Zhang (Molecular Neurobiology, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

CORM-3 alleviates the intestinal injury in a rodent model of hemorrhage shock and resuscitation: roles of GFAP-positive glia - Li-Min Zhang; Yue Xin; Rong-Xin Song; Wei-Chao Zheng; Jin-Shu Hu; Jie-Xia Wang; Zhi-You Wu; Dong-Xue Zhang (Journal of Molecular Histology, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Synergistic effect of elevated glucose levels with SARS-CoV-2 spike protein induced NOX-dependent ROS production in endothelial cells - Jiahao Zhang; Li He; Rong Huang; Juan Felipe Alvarez; David H. Yang; Qihao Sun; Fengqin Wang; Zhiyong Peng; Nanhui Jiang; Lianjiu Su (Molecular Biology Reports, 2023)

SHP2: its association and roles in systemic lupus erythematosus - Chan Yang; Rong Li; Lin-Chong Su; You-Yu Lan; You-Qiang Wang; Wang-Dong Xu; An-Fang Huang (Inflammation Research, 2023)

QTL mapping and candidate gene prediction for the sensitivity of flag leaf angle to exogenous GA3 in rice (Oryza sativa L.) - Yulong Li; Siqi Chen; Xing Wang; Ze Liu; Xiyong Zhao; Weiwen Li; Zhuannan Chu; Delin Hong; Songbai Rong (Euphytica, 2023)

HSPA12A was identified as a key driver in colorectal cancer GWAS loci 10q26.12 and modulated by an enhancer–promoter interaction - Zequn Lu; Linyun Fan; Fuwei Zhang; Chaoqun Huang; Yimin Cai; Can Chen; Gaoyuan Li; Ming Zhang; Jinyu Huang; Caibo Ning; Yanmin Li; Wenzhuo Wang; et al. (Archives of Toxicology, 2023)

Characteristics of PM2.5 and Its Reactive Oxygen Species in Heating Energy Transition and Estimation of Its Impact on the Environment and Health in China—A Case Study in the Fenwei Plain - Zexuan Wang; Hongmei Xu; Rong Feng; Yunxuan Gu; Jian Sun; Suixin Liu; Ningning Zhang; Dan Li; Tao Wang; Linli Qu; Steven Sai Hang Ho; Zhenxing Shen; et al. (Advances in Atmospheric Sciences, 2023)

Effects of saline immersion on the physiological alterations of grass goldfish (Carassius auratus) during subsequent recovery in freshwater - Xiaowen Wang; Huijuan Li; Rong Zhang; Lili Liu; Hua Zhu (Fish Physiology and Biochemistry, 2023)

Lithium extraction from salt lake brines with high magnesium/lithium ratio: a review - Rong Zhu; Shixin Wang; C. Srinivasakannan; Shiwei Li; Shaohua Yin; Libo Zhang; Xiaobin Jiang; Guoli Zhou; Ning Zhang (Environmental Chemistry Letters, 2023)

Proteomics Analysis of Lipid Metabolism and Inflammatory Response in the Liver of Rabbits fed on a High Cholesterol Diet - Jing Wu; Wei-Hua Li; Wei-Rong Wang; Xue-Qin Jin; En-Qi Liu (Cell Biochemistry and Biophysics, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Molecular detection and characterization of three novel parvoviruses belonging to two different subfamilies in zoo birds - Yan Wang; Yijie Sun; Xin Li; Rong Chen; Wang Li; Li Ji; Qifan Zhao; Likai Ji; Shixing Yang; Wen Zhang (Archives of Virology, 2023)

Chinese version of the auditory verbal learning test: normative study and clinical applications in Chinese-speaking population in Shijiazhuang city - Fang-Ming Dong; Wei Wang; Shang-Zun Guo; Kai Shao; Ya-Xue Song; Ning Han; Yan-Li Jia; Rong-Fang Feng; Jian-Hua Wang (Acta Neurologica Belgica, 2023)

Extracellular Vesicles from NMN Preconditioned Mesenchymal Stem Cells Ameliorated Myocardial Infarction via miR-210-3p Promoted Angiogenesis - Yanan Pu; Chunyu Li; Xin Qi; Rui Xu; Liyang Dong; Yi Jiang; Qingyun Gong; Di Wang; Rong Cheng; Cheng Zhang; Yan Chen (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cell-derived extracellular vesicles (MSCs-EVs) possess cardioprotection in acute myocardial infarction. Nevertheless, the therapeutic intervention potential and the molecular mechanism of EVs from NMN (Nicotinamide mononucleotide) preconditioned hUCMSCs (N-EVs) in acute myocardial infarction remains unknown. In the present study, EVs from hUCMSCs (M-EVs) and N-EVs were identified by electron microscopy, immunoblotting and nanoparticle tracking analysis. Compared with M-EVs, N-EVs significantly increased the proliferation, migration, and angiogenesis of HUVECs. Meanwhile, N-EVs markedly reduced apoptosis and cardiac fibrosis and promoted angiogenesis in the peri-infarct region in the MI rats. A high-throughput miRNA sequencing and qPCR methods analysis revealed that miR-210-3p was abundant in N-EVs and the expression of miR-210-3p was obviously upregulated in HUVECs after N-EVs treated. Overexpression of miR-210-3p in HUVECs significantly enhanced the tube formation, migration and proliferative capacities of HUVECs. However, downregulation of miR-210-3p in HUVECs markedly decreased the tube formation, migration and proliferative capacities of HUVECs. Furthermore, bioinformatics analysis and luciferase assays revealed that EphrinA3 (EFNA3) was a direct target of miR-210-3p. Knockdown of miR-210-3p in N-EVs significantly impaired its ability to protect the heart after myocardial infarction. Altogether, these results indicated that N-EVs promoted the infarct healing through improvement of angiogenesis by miR-210-3p via targeting the EFNA3. Graphical Abstract Created with Biorender.com.

Phytotoxicity and the molecular response in yttrium oxide nanoparticle–treated Arabidopsis thaliana seedlings - Jin Wang; Shifeng Zhao; Zhuoxuan Li; Jianxiang Chai; Jinlin Feng; Rong Han (Protoplasma, 2023)

Identification of Heterophilic Epitopes of H1N1 Influenza Virus Hemagglutinin - Jing-ying Sun; Chun-yan Guo; Guo-rong Wang; Li-ting Yan; Qing Feng; Yan Li; Xue-ping Huo; Xin Xie; Jun Hu; Li-jun Sun (Current Microbiology, 2023)

Essential Trace Element Status in Systemic Lupus Erythematosus: a Meta-analysis Based on Case-Control Studies - Hua Wang; Xian-Bao Li; Rong-Gui Huang; Nv-Wei Cao; Hong Wu; Kai-Di Li; Yi-Yu Wang; Bao-Zhu Li (Biological Trace Element Research, 2023)

Research on the evolution and the driving forces of land use classification for production, living, and ecological space in China’s Qilian Mountains Nature Reserve from 2000 to 2020 - Yaobin Wang; Ruitao Zhao; Ying Li; Rong Yao; Ruoxue Wu; Wenlin Li (Environmental Science and Pollution Research, 2023)
With the rapid development of the economy, problems such as resource depletion, environmental degradation, and increasingly strained human-land relations have become increasingly prominent. The rational layout of the production, living, and ecological spaces is the basis for solving the contradiction between economic development and environmental protection. This paper analyzed the spatial distribution pattern and evolution characteristics of the Qilian Mountains Nature Reserve based on the theory of production, living, and ecological space. The results show that the production and living function indexes are rising. The most advantaged areas are in the northern part of the research area, where the terrain is flat and transportation is convenient. The ecological function index rises, falls, then rises again. The high-value area is located in the south of the study area, and its ecological function is intact. The study area is dominated by ecological space. During the study period, the area of production space increased by 858.5 km 2 and the living space area increased by 341.12 km 2 . The intensification of human activities has separated the continuity of ecological space. The area of ecological space has decreased by 233.68 km 2 . Among geographical factors, altitude has a significant impact on the evolution of living space. Population density is the main socioeconomic factor in changing the areas of production space and ecological space. This study is expected to provide a reference basis for land use planning and sustainable development of resources and environment in nature reserves.

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Assessing the Coordinate Development Between Economy and Ecological Environment in China’s 30 Provinces from 2013 to 2019 - Bing Rong; Cheng-jun Chu; Zhen Zhang; Ya-ting Li; Shu-hao Yang; Qian Wang (Environmental Modeling & Assessment, 2023)

Kuroshio Intrusion Combined with Coastal Currents Affects Phytoplankton in the Northern South China Sea Revealed by Lipid Biomarkers - Yaoyao Wang; Rong Bi; Jiawei Gao; Hailong Zhang; Li Li; Yang Ding; Gui’e Jin; Meixun Zhao (Journal of Ocean University of China, 2023)

Experimental evaluation of a hybrid solar dryer with flexible open sorption thermal energy storage unit on demand for burdock root drying - Rong Zhu; Qiongfen Yu; Ming Li; Yiping Xia; Aimin Li; Danya Zhan; Yinning Li; Yunfeng Wang (Environmental Science and Pollution Research, 2023)

First report of fruit rot caused by Paramyrothecium foliicola on muskmelon in China - Jian Fei Huo; Yong Xia Ren; Yu Rong Yao; Hai Yan Ben; Xiu Yun Wen; Wen Lai Ren; Li Juan Yang; Wan Li Wang; Yong Juan Hao (Journal of Plant Pathology, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Effects of long-term grazing exclusion on vegetation structure, soil water holding capacity, carbon and nitrogen sequestration capacity in an alpine meadow on the Tibetan Plateau - Yong-sheng Yang; Fa-wei Zhang; Xian-rong Xie; Jun-bang Wang; Ying-nian Li; Xiao-tao Huang; Hui-ting Li; Hua-kun Zhou (Journal of Mountain Science, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Radon exhalation from cement-based materials under accelerated carbonation - Rong Yang; Jie Wang; Xiaowen Zhang; Jie Li; Mianbiao Chen (Environmental Science and Pollution Research, 2023)

Structures of the xyloglucans in the monocotyledon family Araceae (aroids) - Shih-Yi Hsiung; Jing Li; Balazs Imre; Mu-Rong Kao; Hsien-Chun Liao; Damao Wang; Chih-Hui Chen; Pi-Hui Liang; Philip J. Harris; Yves S. Y. Hsieh (Planta, 2023)
Main conclusion The xyloglucans of all aquatic Araceae species examined had unusual structures compared with those of other non-commelinid monocotyledon families previously examined. Abstract The aquatic Araceae species Lemna minor was earlier shown to have xyloglucans with a different structure from the fucogalactoxyloglucans of other non-commelinid monocotyledons. We investigated 26 Araceae species (including L. minor ), from five of the seven subfamilies. All seven aquatic species examined had xyloglucans that were unusual in having one or two of three features: < 77% XXXG core motif [ L. minor (Lemnoideae) and Orontium aquaticum (Orontioideae)]; no fucosylation [ L. minor (Lemnoideae), Cryptocoryne aponogetonifolia , and Lagenandra ovata (Aroideae, Rheophytes clade)]; and > 14% oligosaccharide units with S or D side chains [ Spirodela polyrhiza and Landoltia punctata (Lemnoideae) and Pistia stratiotes (Aroideae, Dracunculus clade)]. Orontioideae and Lemnoideae are the two most basal subfamilies, with all species being aquatic, and Aroideae is the most derived. Two terrestrial species [ Dieffenbachia seguine and Spathicarpa hastifolia (Aroideae, Zantedeschia clade)] also had xyloglucans without fucose indicating this feature was not unique to aquatic species.

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

DNA Methylation Alterations and Their Association with High Temperature Tolerance in Rice Anthesis - Bo Li; Haiya Cai; Ke Liu; Bingzhuang An; Rong Wang; Fang Yang; Changli Zeng; Chunhai Jiao; Yanhao Xu (Journal of Plant Growth Regulation, 2023)
DNA methylation is an important epigenetic mechanism involved in gene regulation under environmental stresses in plants. However, little information is available regarding its responses to high temperature (HT) and association with HT tolerance in rice. In this study, fourteen rice genotypes were classified into the susceptible, moderate, and tolerant groups by the high temperature susceptibility index (HTSI) after HT treatment. The changes of DNA methylation in rice anthesis under normal and HT30 conditions were investigated using methylation-sensitive amplified polymorphism31 (MSAP). The MSAP results showed that the DNA methylation level significantly increased in the susceptible rice group and decreased in the tolerant rice group under HT treatment, while no significant difference was observed in the moderate rice group. More hypomethylation events were detected in the tolerant rice group, while more hypermethylation was detected in the susceptible rice group. Forty-four differentially methylated epiloci (DME) were generated under both control and HT conditions, which can clearly distinguish the susceptible, moderate, and tolerant genotypes via PCoA analysis. Approximately 43.18% of DMEs were determined to be tolerance-associated epiloci (TAEs). 63.15% TAEs were sequenced and annotated into 12 genes. Quantitative RT-PCR analysis showed that 12 TAE genes were mainly upregulated in 14 rice genotypes, and their expression levels were related to the HT tolerance of rice. Here, DEGs, generated from a number of genotypes, indicate higher probabilities for association with stress tolerance. Overall, these results suggest that DNA methylation regulation might play a key role in adaptation to HT stress in rice.

Spatial distributions of intra-community tree species under topographically variable conditions - Ting Lv; Rong Zhao; Ning-jie Wang; Lei Xie; Yue-yao Feng; Yao Li; Hui Ding; Yan-ming Fang (Journal of Mountain Science, 2023)

Evaluation of deep learning algorithms for landslide susceptibility mapping in an alpine-gorge area: a case study in Jiuzhaigou County - Di Wang; Rong-hao Yang; Xiao Wang; Shao-da Li; Jun-xiang Tan; Shi-qi Zhang; Shuo-you Wei; Zhang-ye Wu; Chao Chen; Xiao-xia Yang (Journal of Mountain Science, 2023)

Accidental acquisition of a rescued Japanese encephalitis virus with unspliced introns in the viral genome when using an intron-based stabilization approach - Ying Huang; Hongshan Xu; Shan Liu; Jiansheng Lu; Lili Jia; Yuhua Li; Rong Wang; Peng Yang; Yongxin Yu; Zhixin Yang (Archives of Virology, 2023)
The intron-based stabilization approach is a very useful strategy for construction of stable flavivirus infectious clones. SA 14 -14-2 is a highly attenuated Japanese encephalitis (JE) live vaccine strain that has been widely used in China since 1989. To develop safe and effective recombinant vaccines with SA 14 -14-2 as a backbone vector, we constructed the DNA-based infectious clone pCMW-JEV of SA 14 -14-2 using the intron-based stabilization approach and acquired the rescued virus rDJEV, which retained the biological properties of the parental virus. Unexpectedly, a rescued virus strain with altered virulence, designated rHV-DJEV, was accidentally acquired in one of the transfection experiments. rHV-DJEV showed up to 10 5 -fold increased neurovirulence compared with the SA 14 -14-2 parental strain. Genome sequencing showed that the inserted introns were still present in the genome of rHV-DJEV. Therefore, we think that the intron-based stabilization approach should be used with caution in vaccine development and direct iDNA immunization.

Proactive therapeutic drug monitoring of vincristine in pediatric and adult cancer patients: current supporting evidence and future efforts - Chun-Ying Wu; Guan-Ting Li; Chen-Chao Chu; Hong-Li Guo; Wei-Rong Fang; Tao Li; Yong-Ren Wang; Jing Xu; Ya-Hui Hu; Li Zhou; Feng Chen (Archives of Toxicology, 2023)

Transmission of NLRP3-IL-1β Signals in Cerebral Ischemia and Reperfusion Injury: from Microglia to Adjacent Neuron and Endothelial Cells via IL-1β/IL-1R1/TRAF6 - Jingrui Pan; Jialing Peng; Xiangpen Li; Hongxuan Wang; Xiaoming Rong; Ying Peng (Molecular Neurobiology, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

IL-18BP Alleviates Anxiety-Like Behavior Induced by Traumatic Stress via Inhibition of the IL-18R-NLRP3 Signaling Pathway in a Mouse Model of Hemorrhagic Shock and Resuscitation - Li-Min Zhang; Dong-Xue Zhang; Rong-Xin Song; Jin-Meng Lv; Lu-Ying Wang; Zhi-You Wu; Hui-Tao Miao; Yan-Bo Zhou; Wei Zhang; Yue Xin; Yan Li (Molecular Neurobiology, 2023)

Nitric Oxide Enhances Salt Tolerance in Tomato Seedlings by Regulating Endogenous S-nitrosylation Levels - Chunlei Wang; Lijuan Wei; Jing Zhang; Dongliang Hu; Rong Gao; Yayu Liu; Li Feng; Wenting Gong; Weibiao Liao (Journal of Plant Growth Regulation, 2023)

Hominibacterium faecale gen. nov., sp. nov., an anaerobic l-arginine-degrading bacterium isolated from human feces - Noori Borhanudin; Min Yang; Andrei V. Chaplin; Jiang Li; Qiong Wang; Li-rong Dai; Ke-jia Wu; Shi-chun Ma; Boris A. Efimov; Lei Cheng (Archives of Microbiology, 2023)

The coupling effect of socio-economic and eco-environment and land use transformation in mountainous areas—a case of the Fengjie County in the Three Gorges Reservoir Area, China - Chunhua Xia; Yangbing Li; Jingan Shao; Shijie Yan; Yan Chen; Luoshan Zheng; Rong Wang (Environmental Science and Pollution Research, 2022)

Extracellular Mitochondria Activate Microglia and Contribute to Neuroinflammation in Traumatic Brain Injury - Chaonan Zhang; Chuan Liu; Fanjian Li; Mutian Zheng; Yafan Liu; Lei Li; Huaijin Yang; Shu Zhang; Chongjin Wang; Hongtao Rong; Hui Guo; Ying Li; et al. (Neurotoxicity Research, 2022)

Study on the Relationship Between Diet, Physical Health and Gut Microflora of Chinese College Students - Xiafen Hu; Jiaqi Guo; Jiadun Wang; Wanxin Liu; Xiaochen Xiang; Siyang Chen; Xinquan Li; Jinhan Tang; Wei Zhang; Hui Chen; Rong Shu; Qingming Wu; et al. (Current Microbiology, 2022)

Integration of transcriptomics and metabolomics reveals pathways involved in MDSC supernatant attenuation of TGF-β1-induced myofibroblastic differentiation of mesenchymal stem cells - Yin Celeste Cheuk; Xinhao Niu; Yongxin Mao; Jiawei Li; Jiyan Wang; Shihao Xu; Yongsheng Luo; Weixi Wang; Xuanchuan Wang; Yi Zhang; Ruiming Rong (Cell and Tissue Research, 2022)

Radiomics based on readout-segmented echo-planar imaging (RS-EPI) diffusion-weighted imaging (DWI) for prognostic risk stratification of patients with rectal cancer: a two-centre, machine learning study using the framework of predictive, preventive, and personalized medicine - Zonglin Liu; Yueming Wang; Fu Shen; Zhiyuan Zhang; Jing Gong; Caixia Fu; Changqing Shen; Rong Li; Guodong Jing; Sanjun Cai; Zhen Zhang; Yiqun Sun; et al. (EPMA Journal, 2022)
Background Currently, the rate of recurrence or metastasis (ROM) remains high in rectal cancer (RC) patients treated with the standard regimen. The potential of diffusion-weighted imaging (DWI) in predicting ROM risk has been reported, but the efficacy is insufficient. Aims This study investigated the potential of a new sequence called readout-segmented echo-planar imaging (RS-EPI) DWI in predicting the ROM risk of patients with RC using machine learning methods to achieve the principle of predictive, preventive, and personalized medicine (PPPM) application in RC treatment. Methods A total of 195 RC patients from two centres who directly received total mesorectal excision were retrospectively enrolled in our study. Machine learning methods, including recursive feature elimination (RFE), the synthetic minority oversampling technique (SMOTE), and the support vector machine (SVM) classifier, were used to construct models based on clinical-pathological factors (clinical model), radiomic features from RS-EPI DWI (radiomics model), and their combination (merged model). The Harrell concordance index (C-index) and the area under the time-dependent receiver operating characteristic curve (AUC) were calculated to evaluate the predictive performance at 1 year, 3 years, and 5 years. Kaplan‒Meier analysis was performed to evaluate the ability to stratify patients according to the risk of ROM. Findings The merged model performed well in predicting tumour ROM in patients with RC at 1 year, 3 years, and 5 years in both cohorts (AUC = 0.887/0.813/0.794; 0.819/0.795/0.783) and was significantly superior to the clinical model (AUC = 0.87 [95% CI: 0.80–0.93] vs. 0.71 [95% CI: 0.59–0.81], p = 0.009; C-index = 0.83 [95% CI: 0.76–0.90] vs. 0.68 [95% CI: 0.56–0.79], p = 0.002). It also had a significant ability to differentiate patients with a high and low risk of ROM (HR = 12.189 [95% CI: 4.976–29.853], p < 0.001; HR = 6.427 [95% CI: 2.265–13.036], p = 0.002). Conclusion Our developed merged model based on RS-EPI DWI accurately predicted and effectively stratified patients with RC according to the ROM risk at an early stage with an individualized profile, which may be able to assist physicians in individualizing the treatment protocols and promote a meaningful paradigm shift in RC treatment from traditional reactive medicine to PPPM.

Plasma Exo-miRNAs Correlated with AD-Related Factors of Chinese Individuals Involved in Aβ Accumulation and Cognition Decline - Lifang Wang; Hefu Zhen; Yuzhe Sun; Shuang Rong; Benchao Li; Zhijie Song; Zhili Liu; Zhiming Li; Jiahong Ding; Huanming Yang; Xiuqing Zhang; Haixi Sun; et al. (Molecular Neurobiology, 2022)
Numerous studies have investigated the risk factors of Alzheimer’s disease (AD); however, AD-risk factors related miRNAs were rarely reported. In this study, AD-risk factor related miRNAs of 105 Chinese individuals (45 AD patients and 60 cognitively normal controls) were investigated. The results showed that Hsa-miR-185-5p, Hsa-miR-20a-5p, and Hsa-miR-497-5p were related to AD and education, Hsa-miR-185-5p, Hsa-miR-181c-5p, Hsa-miR-664a-3p, Hsa-miR-27a-3p, Hsa-miR-451a, and Hsa-miR-320a were related to AD and depression. Target prediction of above miRNAs showed that these miRNAs were involved in the generation and clearance of amyloid-beta (Aβ), important molecules related to cognition, and disease-activated microglia response to AD. It is worth noting that Hsa-miR-185-5p was related to both education and depression, whose decreased expression pattern in AD patients was alleviated by education and enhanced by depression, and participates in Aβ generation and accumulation. Our results indicated that certain education and depression factors can contribute to AD progression by modulating miRNA expression, implying that preventive interventions might alter AD progression in Chinese patients.

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Homozygous missense mutation in CCDC155 disrupts the transmembrane distribution of CCDC155 and SUN1, resulting in non-obstructive azoospermia and premature ovarian insufficiency in humans - Huan Wu; Xin Zhang; Rong Hua; Yuqian Li; Li Cheng; Kuokuo Li; Yiyuan Liu; Yang Gao; Qunshan Shen; Guanxiong Wang; Mingrong Lv; Yuping Xu; et al. (Human Genetics, 2022)

Occurrence and damage of epidemic fungal diseases in middle and late stages of sugarcane growth in Yunnan Province of China - Wen-Feng Li; Xiao-Yan Wang; Hong-Li Shan; Rong-Yue Zhang; Yin-Hu Li; Wen-Jie Lu; Ying-Kun Huang (European Journal of Plant Pathology, 2022)

Design strategy of self-assembled BC@MIL-100(Fe) composite membrane for the efficient removal of diclofenac sodium from water - Rong Cheng; Weilong Li; Jinlin Wang; Jie Li; Jianzhong Zheng; Xiang Zheng (Environmental Science and Pollution Research, 2022)

Preparation of Pinocembrin-Loaded F127/MPEG-PDLLA Polymer Micelles and Anti-Osteoporotic Activity - Xia Cao; Qing He; Michael Adu-Frimpong; Xinyi Shen; Wanjing Rong; Xiaoxiao Li; Jian Zhang; Xiaoli Xia; Feng Shi; Hao Ji; Elmurat Toreniyazov; Qilong Wang; et al. (AAPS PharmSciTech, 2022)

Phosphorylation of Truncated Tau Promotes Abnormal Native Tau Pathology and Neurodegeneration - Longfei Li; Yanli Jiang; Gang Wu; Yacoubou Abdoul Razak Mahaman; Dan Ke; Qun Wang; Bin Zhang; Jian-Zhi Wang; Hong-Lian Li; Rong Liu; Xiaochuan Wang (Molecular Neurobiology, 2022)

Tetramethylpyrazine protects neural stem cells against sevoflurane-induced toxicity through Akt/GSK-3β pathway - Yan Feng; Kui Wang; Ning Wang; Pengyu Jia; Lei Zhang; Haozheng Yuan; Pan Lu; Yang Lu; Hong Zhang; Rong Li; Yan Zhang; Qianqian Li; et al. (Metabolic Brain Disease, 2022)

Expression patterns and correlation analyses of muscle-specific genes in the process of sheep myoblast differentiation - Hejie Wang; Minmin Dou; Jun Li; Peng Cao; Junling Li; Tianyan Guo; Dipeng Zhao; Ajab Khan; Yingliang Li; Baojun Li; Jian Qin; Rong Du (In Vitro Cellular & Developmental Biology - Animal, 2022)

Potential therapeutic strategies for myocardial infarction: the role of Toll-like receptors - Sumra Komal; Nimrah Komal; Ali Mujtaba; Shu-Hui Wang; Li-Rong Zhang; Sheng-Na Han (Immunologic Research, 2022)

Identification of resistance of Guangxi (Oryza rufipogon Griff.) to white-backed planthopper with stem evaluation method - Xin-ying Guo; Xuan Wang; Liang Luo; Yao-yu Fang; Kai-chong Teng; Neng Zhao; Jin-lian Yang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Genetic Resources and Crop Evolution, 2022)

Screening of microRNA and mRNA related to secondary hair follicle morphogenesis and development and functional analysis in cashmere goats - Fangzheng Shang; Yu Wang; Rong Ma; Youjun Rong; Min Wang; Zhihong Wu; Erhan Hai; Jianfeng Pan; Lili Liang; Zhiying Wang; Ruijun Wang; Rui Su; et al. (Functional & Integrative Genomics, 2022)
microRNA (miRNA) is a type of endogenous short-chain non-coding RNA with regulatory function found in eukaryotes, which is involved in the regulation of a variety of cellular and biological processes. However, the research on the development of cashmere goat secondary hair follicles is still relatively scarce. In this study, small RNA libraries and mRNA libraries of 45 days, 55 days, 65 days, and 75 days of fetal skin of cashmere goats were constructed, and the constructed libraries were sequenced using Illumina Hiseq4000, and the expression profiles of miRNA and mRNA in cashmere goat fetal skin were obtained. The differentially expressed miRNAs and mRNAs in six control groups were identified and the qRT-PCR experiment shows that the sequencing results are accurate. Sixty-six miRNAs related to secondary hair follicle development were screened, and used TargetScan and miRanda to predict 33 highly expressed miRNA target genes. At the same time, 664 mRNAs related to the development of secondary hair follicles were screened, and GO enrichment and KEGG pathway analysis were performed. It was found that some miRNA target genes were consistent with the screening results of mRNAs related to secondary hair follicle development and were enriched in Notch signaling pathway, TGF-β signaling pathway. Therefore, miR-145-5p-DLL4, miR-27b-3p-DLL4, miR-30e-5p-DLL4, miR-193b-3p-TGF-β1, miR-181b-5p-NOTCH2, and miR-103-3p-NOTCH2 regulatory network related to the development of secondary hair follicles were constructed and the results of dual-luciferase reporter gene assay indicated that there is a targeted relationship between chi-miR-30e-5p and DLL4, which will provide a basis for molecular mechanism of miRNA-mRNA in the development of the hair follicles in cashmere goats.

Prediction model for disc cutter wear during hard rock breaking based on plastic removal abrasiveness mechanism - Lei She; She-rong Zhang; Chao Wang; Zheng-qiao Wu; Lun-chuang Yu; Li-xin Wang (Bulletin of Engineering Geology and the Environment, 2022)

Mechanism of progressive failure of a slope with a steep joint under the action of freezing and thawing: model test - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Bo Lu; Xiao-ke Shen; Xiao-wei Wang; Jie-sheng Liu; Liang-liang Wu; Xin-zhou Zhang (Journal of Mountain Science, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Sugar Product Diversification and Its Opportunities in China - Qi Wang; Cai-Feng Xie; Chang-Rong Shi; Yuan Li; Yu-Hao Shang; Chu-Xuan Hou; Fang-Xue Hang; Jian-Bin Li; Kai Li (Sugar Tech, 2022)

Functional divergence of oligoadenylate synthetase 1 (OAS1) proteins in Tetrapods - Xiaoxue Wang; Jiaxiang Hu; Linfei Song; Enguang Rong; Chenghuai Yang; Xiaoyun Chen; Juan Pu; Honglei Sun; Chuze Gao; David W. Burt; Jinhua Liu; Ning Li; et al. (Science China Life Sciences, 2022)

Roles of PTEN inactivation and PD-1/PD-L1 activation in esophageal squamous cell carcinoma - Rong Qiu; Wenxi Wang; Juan Li; Yuxiang Wang (Molecular Biology Reports, 2022)

Ambient air pollutants increase the risk of immunoglobulin E–mediated allergic diseases: a systematic review and meta-analysis - Hua Wang; Xian-Bao Li; Xiu-Jie Chu; Nv-Wei Cao; Hong Wu; Rong-Gui Huang; Bao-Zhu Li; Dong-Qing Ye (Environmental Science and Pollution Research, 2022)

Increases in temperature response to CO2 emissions in biochar-amended vegetable field soil - Rong Huang; Zifang Wang; Yi Xiao; Luo Yu; Xuesong Gao; Changquan Wang; Bing Li; Qi Tao; Qiang Xu; Ming Gao (Environmental Science and Pollution Research, 2022)

Prediction of the sea buckthorn AQP gene structure and its spatiotemporal expression pattern under drought stress - Dan Zhang; Nanxiang Yang; Jiawei Dong; Cheng Wang; Qiangfeng Li; Rong Wang; Zhipeng Feng; Dejuan Xie; Guisheng Ye; Yuhua Ma (Journal of Plant Biochemistry and Biotechnology, 2022)

Asymmetric changes of photosynthetically active radiation and light utilization efficiency during the maize growing season in North China - Huayun He; Qi Hu; Jing Wang; Mengyuan Xing; Yuanyuan Liu; Xiaochen Wang; Rong Li; Xuebiao Pan; Zhihua Pan; Binxiang Huang; Qijin He (Theoretical and Applied Climatology, 2022)

Ventromedial Thalamus-Projecting DCN Neurons Modulate Associative Sensorimotor Responses in Mice - Jie Zhang; Hao Chen; Li-Bin Zhang; Rong-Rong Li; Bin Wang; Qian-Hui Zhang; Liu-Xia Tong; Wei-Wei Zhang; Zhong-Xiang Yao; Bo Hu (Neuroscience Bulletin, 2022)

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

HucMSC-Ex alleviates inflammatory bowel disease via the lnc78583-mediated miR3202/HOXB13 pathway - Yuting Xu; Li Zhang; Dickson Kofi Wiredu Ocansey; Bo Wang; Yilin Hou; Rong Mei; Yongmin Yan; Xu Zhang; Zhaoyang Zhang; Fei Mao (Journal of Zhejiang University-SCIENCE B, 2022)

The comparative landscape of Chinese and foreign articles on the carbon footprint using bibliometric analysis - Rong Wu; Yundong Xie; Yezhu Wang; Zhi Li; Li Hou (Environmental Science and Pollution Research, 2022)

Phytoremediation of uranium-contaminated soil by perennial ryegrass (Lolium perenne L.) enhanced with citric acid application - Lishan Rong; Shiqi Zhang; Jiali Wang; Shiyou Li; Shuibo Xie; Guohua Wang (Environmental Science and Pollution Research, 2022)

γ-Cyclodextrin metal–organic framework as a carrier to deliver triptolide for the treatment of hepatocellular carcinoma - Zhe Li; Gang Yang; Rong Wang; Yuanyuan Wang; Jing Wang; Meng Yang; Chunai Gong; Yongfang Yuan (Drug Delivery and Translational Research, 2022)

Genetic Diversity Analysis of Sugarcane (Saccharum spp. hybrids) Among High-Sucrose Clones of GT Series and Commonly Used Parents by Using Microsatellite Markers in Guangxi, China - Hai-Rong Huang; Yi-Jing Gao; Mukesh Kumar Malviya; Krishan K. Verma; Manoj Kumar Solanki; Yu-Xin Huang; Xiang Li; Yuchi Deng; Jing Yan; Shi-Yun Tang; Lun-Wang Wang; Lin Xu (Sugar Tech, 2022)

The solar wind plasma upstream of Mars observed by Tianwen-1: Comparison with Mars Express and MAVEN - Kai Fan; Limei Yan; Yong Wei; Aibing Zhang; Linggao Kong; Markus Fränz; Fei He; Lihui Chai; Chongjing Yuan; Yuqi Wang; Jun Zhong; Zhaojin Rong; et al. (Science China Earth Sciences, 2022)

Cassiterite oxygen isotopes in magmatic-hydrothermal systems: in situ microanalysis, fractionation factor, and applications - Yang Li; Sheng He; Rong-Qing Zhang; Xian-Wu Bi; Lian-Jun Feng; Guo-Qiang Tang; Wen-Zhong Wang; Fang Huang; Xian-Hua Li (Mineralium Deposita, 2022)

The Predictability of Ocean Environments that Contributed to the 2020/21 Extreme Cold Events in China: 2020/21 La Niña and 2020 Arctic Sea Ice Loss - Fei Zheng; Ji-Ping Liu; Xiang-Hui Fang; Mi-Rong Song; Chao-Yuan Yang; Yuan Yuan; Ke-Xin Li; Ji Wang; Jiang Zhu (Advances in Atmospheric Sciences, 2022)
Several consecutive extreme cold events impacted China during the first half of winter 2020/21, breaking the low-temperature records in many cities. How to make accurate climate predictions of extreme cold events is still an urgent issue. The synergistic effect of the warm Arctic and cold tropical Pacific has been demonstrated to intensify the intrusions of cold air from polar regions into middle-high latitudes, further influencing the cold conditions in China. However, climate models failed to predict these two ocean environments at expected lead times. Most seasonal climate forecasts only predicted the 2020/21 La Niña after the signal had already become apparent and significantly underestimated the observed Arctic sea ice loss in autumn 2020 with a 1–2 month advancement. In this work, the corresponding physical factors that may help improve the accuracy of seasonal climate predictions are further explored. For the 2020/21 La Niña prediction, through sensitivity experiments involving different atmospheric–oceanic initial conditions, the predominant southeasterly wind anomalies over the equatorial Pacific in spring of 2020 are diagnosed to play an irreplaceable role in triggering this cold event. A reasonable inclusion of atmospheric surface winds into the initialization will help the model predict La Niña development from the early spring of 2020. For predicting the Arctic sea ice loss in autumn 2020, an anomalously cyclonic circulation from the central Arctic Ocean predicted by the model, which swept abnormally hot air over Siberia into the Arctic Ocean, is recognized as an important contributor to successfully predicting the minimum Arctic sea ice extent.

Spatially explicit reconstruction of the population distribution in the Tuojiang River Basin during 1911–2010 using random forest regression - Qi Wang; Xuesong Gao; Qiquan Li; Ting Lan; Rong Huang; Ouping Deng (Regional Environmental Change, 2022)

Salicylic acid alleviates selenium stress and promotes selenium uptake of grapevine - Zhiyu Li; Rong Fan; Xuemei Peng; Junjiang Shu; Lei Liu; Jin Wang; Lijin Lin (Physiology and Molecular Biology of Plants, 2022)

The establishment of giant panda (Ailuropoda melanoleuca) fibroblast cell line - Yuliang Liu; Jiasong Chen; Tongying Feng; Rong Hou; Zhigang Cai; Donghui Wang; Mingyue Zhang; Yuan Li; Yijiao Chen; Junhui An (In Vitro Cellular & Developmental Biology - Animal, 2022)

QTL mapping integrated with BSA-Seq analysis identifies a novel gene conferring resistance to brown planthopper from common wild rice (Oryza rufipogon Griff.) - Xuan Wang; Yue Han; Yue-xiong Zhang; Biao Deng; Bi-qiu Wu; Xin-ying Guo; Yu-fen Qin; Yao-yu Fang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Euphytica, 2022)

Synchronous removal of tetracycline and copper (II) over Z‑scheme BiVO4/rGO/g-C3N4 photocatalyst under visible-light irradiation - Jiangli Sun; Yiyuan Rong; Yanping Hou; Lingli Tu; Qingyu Wang; Yuying Mo; Shuxuan Zheng; Zan Li; Zuji Li; Zebin Yu (Environmental Science and Pollution Research, 2022)

Medium and Long-term Precipitation Prediction Using Wavelet Decomposition-prediction-reconstruction Model - Yongtao Wang; Jian Liu; Rong Li; Xinyu Suo; EnHui Lu (Water Resources Management, 2022)

Activation of Autophagy Ameliorates Age-Related Neurogenesis Decline and Neurodysfunction in Adult Mice - Na Yang; Xueqin Liu; Xiaojie Niu; Xiaoqiang Wang; Rong Jiang; Na Yuan; Jianrong Wang; Chengwu Zhang; Kah-Leong Lim; Li Lu (Stem Cell Reviews and Reports, 2022)

Digoxin Ameliorates Glymphatic Transport and Cognitive Impairment in a Mouse Model of Chronic Cerebral Hypoperfusion - Jie Cao; Di Yao; Rong Li; Xuequn Guo; Jiahuan Hao; Minjie Xie; Jia Li; Dengji Pan; Xiang Luo; Zhiyuan Yu; Minghuan Wang; Wei Wang (Neuroscience Bulletin, 2022)

Mass cultivation of conidia of Pyricularia oryzae - Zhong-na Hao; Hai-ping Qiu; Zhen Zhang; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2022)

Do driving restriction policies effectively alleviate smog pollution in China? - Lan Yi; Zhi-rong Kang; Li Yang; Mohammad Musa; Fei Wang (Environmental Science and Pollution Research, 2022)

Association Between Essential Metal Elements and the Risk of Autism in Chinese Han Population - Jiahui Ma; Jing Wu; Haibin Li; Jingyu Wang; Jisheng Han; Rong Zhang (Biological Trace Element Research, 2022)

Complete genome sequence of a novel partitivirus infecting the phytopathogenic fungus Alternaria tenuissima - Xiangyu Wang; Zhihao Ma; Rong Li; Tao Zhou; Can Zhao; Xuehong Wu (Archives of Virology, 2022)

Serum- and Feeder-Free Culture of Juvenile Monkey Female Germline Stem Cells and Testosterone Regulation of their Self-Renewal - Xiaoyong Li; Xiaoying Yao; Chunlan Mu; Zhaoxia Wang; Rong Hu; Yan Chang; Ji Wu (Stem Cell Reviews and Reports, 2022)

Genetic diversity of Lathyrus sp collected from different geographical regions - Md. Mosiur Rahman; Md. Ruhul Quddus; Md. Omar Ali; Rong Liu; Mengwei Li; Xin Yan; Guan Li; Yishan Ji; Md. Monoar Hossain; Chenyu Wang; Ashutosh Sarker; Tao Yang; et al. (Molecular Biology Reports, 2022)

Clinical characteristics of 967 children with pertussis: a single-center analysis over an 8-year period in Beijing, China - Limin Kang; Xiaodai Cui; Jin Fu; Wenpeng Wang; Li Li; Tiegeng Li; Xiaoying Wang; Fei Xiao; Huixue Jia; Rong Mi; Xinlin Hou (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Promotional effect of ZrO2 and WO3 on bimetallic Pt-Pd diesel oxidation catalyst - Rongrong Fan; Zhaoqiang Li; Yu Wang; Yan Wang; Zhiyong Ding; Cheng Zhang; Na Kang; Xin Guo; Rong Wang (Environmental Science and Pollution Research, 2022)

Stress response mechanisms and description of three novel species Shewanella avicenniae sp. nov., Shewanella sedimentimangrovi sp. nov. and Shewanella yunxiaonensis sp. nov., isolated from mangrove ecosystem - Guo-Hong Liu; Qi Zhang; Manik Prabhu Narsing Rao; Shang Yang; Rong Tang; Huai Shi; Jie-Ping Wang; Guan-Min Huang; Bo Liu; Shun-Gui Zhou; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

miR-125-5p inhibits thyroid cancer growth and metastasis by suppressing the ERK/PI3K/AKT signal pathway - Rong Wang; Chen Wang; Xian-Jie Meng; Li Wei (Molecular & Cellular Toxicology, 2021)

A drug–biomarker interaction model to predict the key targets of Scutellaria barbata D. Don in adverse-risk acute myeloid leukaemia - Teng Wang; Chun-yi Lyu; Yue-hua Jiang; Xue-yan Dong; Yan Wang; Zong-hong Li; Jin-xin Wang; Rui-rong Xu (Molecular Diversity, 2021)

Differences in pathogenicity and physiologic races between Pyricularia oryzae isolates from indica and japonica rice varieties - Zhong-na Hao; Zhen Zhang; Hai-ping Qiu; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2021)

Motor Circuit and Superior Temporal Sulcus Activities Linked to Individual Differences in Multisensory Speech Perception - Liyuan Li; Rong Li; Xinju Huang; Fei Shen; Hongyu Wang; Xuyang Wang; Chijun Deng; Chong Wang; Jiale Yang; Leiyao Zhang; Jiyi Li; Ting Zou; et al. (Brain Topography, 2021)

Promoting soil microbial-mediated suppressiveness against Fusarium wilt disease by the enrichment of specific fungal taxa via crop rotation - Xianfu Yuan; Beibei Wang; Shan Hong; Wu Xiong; Zongzhuan Shen; Yunze Ruan; Rong Li; Qirong Shen; Francisco Dini-Andreote (Biology and Fertility of Soils, 2021)

Development and application of the Faba_bean_130K targeted next-generation sequencing SNP genotyping platform based on transcriptome sequencing - Chenyu Wang; Rong Liu; Yujiao Liu; Wanwei Hou; Xuejun Wang; Yamei Miao; Yuhua He; Yu Ma; Guan Li; Dong Wang; Yishan Ji; Hongyan Zhang; et al. (Theoretical and Applied Genetics, 2021)

AsTal1 from Aquilaria sinensis regulates ABA signaling-mediated seed germination and root growth in Nicotiana benthamiana - Yuqing Rong; Tiezheng Li; Xiao Liu; Shepo Shi; Xiaohui Wang; Pengfei Tu (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

CARMA1 is required for Notch1-induced NF-κB activation in SIL-TAL1-negative T cell acute lymphoblastic leukemia - Ninghan Zhang; Jiawen Xu; Rong Wang; Ting Pan; Huanxin Zhang; Lingling Yin; Yao Yao; Linyan Xu; Shengyun Zhu; Qingyun Wu; Zhenyu Li; Xuejiao Liu; et al. (Journal of Molecular Medicine, 2021)

Emerging role of air pollution in chronic kidney disease - Yue Chen; Fan Cao; Jian-Ping Xiao; Xin-Yu Fang; Xue-Rong Wang; Li-Hong Ding; De-Guang Wang; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

A comprehensive review on green buildings research: bibliometric analysis during 1998–2018 - Ying Li; Yanyu Rong; Umme Marium Ahmad; Xiaotong Wang; Jian Zuo; Guozhu Mao (Environmental Science and Pollution Research, 2021)

Recombinant L-HN Fusion Antigen Derived from the L and HN Domains of Botulinum Neurotoxin B Stimulates a Protective Antibody Response Against Active Neurotoxin - Zhen Li; Jian-Sheng Lu; Shan Liu; Rong Wang; Qing Xu; Yun-Zhou Yu; Zhi-Xin Yang (Neurotoxicity Research, 2021)

Hydrated halloysite: the pesky stuff responsible for a cascade of landslides triggered by the 2018 Iburi earthquake, Japan - Fawu Wang; Shuai Zhang; Ran Li; Rong Zhou; Andreas Auer; Hiroto Ohira; Zili Dai; Tetsuya Inui (Landslides, 2021)

Evaluation of field resistance to brown stripe disease in novel and major cultivated sugarcane varieties in China - Xiao-Yan Wang; Xiao-Yan Cang; Wei Qin; Hong-Li Shan; Rong-Yue Zhang; Chang-Mi Wang; Wen-Feng Li; Ying-Kun Huang (Journal of Plant Pathology, 2021)

Effects of Mn2+ on neutral lipid content, C4 pathway, and related gene expression in Phaeodactylum tricornutum - Rong-Shi Chen; Li Zhang; Feng-Juan Wei; Lan-Ying Yuan; Pu Zhao; He-Yu Wang; Yi-Fu Gong (Journal of Applied Phycology, 2021)

Activation of autophagy reverses gemcitabine-induced immune inhibition of RAW264.7 macrophages by promoting TNF-α, IL-6 and MHC-II expression - Shanshan Jiang; Rong Wang; Lu Han; Kudelaidi Kuerban; Li Ye; Shu Pan; Shengnan Li; Yongfang Yuan (Immunologic Research, 2021)
This research aims to investigate the effect of gemcitabine (GEM) on various activities and functions of macrophages. Phagocytosis, cell autophagy and reactive oxygen species (ROS) were analysed by laser scanning confocal microscope. The cell cycle status and major histocompatibility complex II (MHC-II) expression were examined by flow cytometry. Inflammatory cytokine secretion such as tumour necrosis factor α (TNF-α) and interleukin 6 (IL-6) was detected by Elisa assay. The expression of proteins was analysed by western blot method. The results revealed that GEM-induced immune inhibition of M1-type RAW264.7 macrophages activated by interferon-γ (IFN-γ) and lipopolysaccharide (LPS). We also found that GEM inhibited autophagy, as evidenced by the reduced formation of autophagosome-like vacuoles and autophagosomes. Further study showed that incubation of activated macrophages with the autophagy inhibitor 3-MA induced immune suppression. In contrast, treatment with the autophagy inducer trehalose (Tre) restored phagocytosis, TNF-α and IL-6 secretion, and MHC-II expression in GEM-induced immune-inhibited macrophages. GEM reduced immune effect of M1-type RAW264.7 macrophages via inhibiting TNF-α, IL-6 and MHC-II expression. Furthermore, activation of autophagy by Tre reversed GEM-induced immune inhibition of RAW264.7 macrophages.

Removal of phosphorus and ammonium from municipal wastewater treatment plant effluent by manganese ore in a simulated constructed wetland - Yungui Li; Xueying Bai; Ruonan Ding; Wenxuan Lv; Ying Long; Liang Wei; Fachun Xiang; Rong Wang (Environmental Science and Pollution Research, 2021)

Exposure to antibiotics and mental disorders in children: a community-based cross-sectional study - Jingjing Zhang; Kaiyong Liu; Liang Sun; Linsheng Yang; Xinji Liu; Yitian Zhu; Rong Wei; Zhongxiu Jin; Li Wang; Ying Ma; Sufang Wang; Annuo Liu; et al. (Environmental Geochemistry and Health, 2021)

A temperature-induced chitosanase bacterial cell-surface display system for the efficient production of chitooligosaccharides - Qianqian Li; Tuantuan Wang; Yangzhi Ye; Shimin Guan; Baoguo Cai; Shuo Zhang; Shaofeng Rong (Biotechnology Letters, 2021)

Oceanobacillus salinisoli sp. nov., a bacterium isolated from saline soil of Turpan city in Xinjiang province, north–west China - Wen-Yong Zhu; Li Yang; Zhou-Tian-Le Zhang; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Gang-Qiang Jiang; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2021)

Retrospective surveillance of porcine circovirus 4 in pigs in Inner Mongolia, China, from 2016 to 2018 - Zhuo Ha; Chengdong Yu; Changzhan Xie; Guanyu Wang; Ying Zhang; Pengfei Hao; Jinfeng Li; Zhuoxin Li; Yanwei Li; Fulong Rong; Fulong Nan; He Zhang; et al. (Archives of Virology, 2021)

Distinctive distributions of halophilic Archaea across hypersaline environments within the Qaidam Basin of China - Derui Zhu; Guoping Shen; Zhibo Wang; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Yongzhen Li; Rong Wang (Archives of Microbiology, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

MiR-146a Negatively Regulates Aspergillus fumigatus-Induced TNF-α and IL-6 Secretion in THP-1 Macrophages - Jianbo Tong; Zhimin Duan; Rong Zeng; Leilei Du; Song Xu; Liwei Wang; Yuzhen Liu; Qing Chen; Xu Chen; Min Li (Mycopathologia, 2021)

Syntheses and anticancer activities of novel glucosylated (−)-epigallocatechin-3-gallate derivatives linked via triazole rings - Bo-Ya Shi; Ze-Hao Wang; Ning Zhang; Yin-Rong Xie; Xiu-Li Sun; Hao-Nan Yang; Yi-Long Wu; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Medicinal Chemistry Research, 2021)

Dietary Supplementation with Sea Cucumber Saponins and Exercise Can Significantly Suppress Adipose Accumulation in Mice Fed with High-Fat Diet - Rong Li; Jing Meng; Haohao Shi; Chengcheng Wang; Zhaojie Li; Changhu Xue; Yuming Wang; Tiantian Zhang (Journal of Ocean University of China, 2021)

Clinical study on empirical and diagnostic-driven (pre-emptive) therapy of voriconazole in severe aplastic anaemia patients with invasive fungal disease after intensive immunosuppressive therapy - Yuhong Wu; Li Yan; Huaquan Wang; Hong Liu; Limin Xing; Rong Fu; Zonghong Shao (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Isolation and Identification of Pseudomonas sp. Strain DY-1 from Agricultural Soil and Its Degradation Effect on Prometryne - Dong Liang; Ming-yue Ding; Chang-yixin Xiao; Ya-wen Shen; Yin-yue Wang; Hai-tao Li; Rong-mei Liu; Ji-guo Gao (Current Microbiology, 2021)

MiR-150-5p regulate T cell activation in severe aplastic anemia by targeting Bach2 - Yingmei Li; Jifeng Yu; Fang Wang; Rong Guo; Haizhou Xing; Yali Chen; Dandan Chen; Xinsheng Xie; Dingming Wan; Zhongxing Jiang (Cell and Tissue Research, 2021)

Complete nucleotide sequence of a new carlavirus infecting Aconitum carmichaelii in China - Rong Wang; Bingwei Chen; Yong Li; Mengji Cao; Wanlong Ding (Archives of Virology, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

Isolation, culture, and characterization of cells derived from giant panda (Ailuropoda melanoleuca) semen - Yuliang Liu; Yuan Li; Rong Hou; Zhigang Cai; Donghui Wang; Jiasong Chen; Feiping Li; Yijiao Chen; Junhui An (In Vitro Cellular & Developmental Biology - Animal, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Comparative Transcriptomic Analyses of Haemophilus parasuis Reveal Differently Expressed Genes among Strains with Different Virulence Degrees - Yuan Y. Zhou; Chao Wang; Jing Yuan; Rong L. Yin; Xin Chen; Rui Li; Xue L. Zhang; Jing Wang; Chen Huang; Rong H. Yin (Current Microbiology, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

Effects of simulated drought stress on carotenoid contents and expression of related genes in carrot taproots - Rong-Rong Zhang; Ya-Hui Wang; Tong Li; Guo-Fei Tan; Jian-Ping Tao; Xiao-Jun Su; Zhi-Sheng Xu; Yong-Sheng Tian; Ai-Sheng Xiong (Protoplasma, 2021)

Identification of genetic variants in m6A modification genes associated with pancreatic cancer risk in the Chinese population - Pingting Ying; Yao Li; Nan Yang; Xiaoyang Wang; Haoxue Wang; Heng He; Bin Li; Xiating Peng; Danyi Zou; Ying Zhu; Rong Zhong; Xiaoping Miao; et al. (Archives of Toxicology, 2021)

Knockdown of Arginyl-tRNA Synthetase Attenuates Ischemia-Induced Cerebral Cortex Injury in Rats After Middle Cerebral Artery Occlusion - Yang Liu; Xue-Bin Hu; Li-Zhi Zhang; Zi Wang; Rong Fu (Translational Stroke Research, 2021)
Some researchers have previously shown that RNAi knockdown of arginyl-tRNA synthetase (ArgRS) before or after a hypoxic injury can rescue animals from death, based on the model organism, C. elegans . However, there has been no study on the application of arginyl-tRNA synthetase knockdown in treating mammalian ischemic stroke, and its potential mechanism and effect on ischemic brain damage are still unknown. Here, we focused on the Rars gene, which encodes an arginyl-tRNA synthetase, and examined the effects of Rars knockdown in a permanent middle cerebral artery occlusion model in rats. To achieve this aim, adult male Sprague-Dawley (SD) rats were given right cerebral cortex injections of short hairpin RNA (shRNA) adenovirus (AV) particles to knock down arginyl-tRNA synthetase, and a non-targeting control (NTC) vector or phosphate-buffered solution served as the controls. After 4 days, the rats were exposed to permanent middle cerebral artery occlusion (pMCAO). Then, the right cerebral cortex level of arginyl-tRNA synthetase was examined, and the effects of the Rars knockdown were evaluated by differences in infarction volume, oxidative stress, blood-brain barrier, mitochondrial function, and glucose metabolism at 1 day and 3 days after MCAO. The injection of shRNA adenovirus particles successfully suppressed the expression of arginyl-tRNA synthetase in the cerebral cortex. We observed an improvement in oxidative stress, mitochondrial function, and glucose utilization and a reduction in brain edema compared with the non-targeting control rats with suppressed expression of arginyl-tRNA synthetase mRNA in the ipsilateral ischemic cortex of the brain. Our findings indicate that knockdown of arginyl-tRNA synthetase in the cerebral cortex exerted neuroprotective effects, which were achieved not only by the improvement of oxidative stress and glucose utilization but also by the maintenance of mitochondrial morphological integrity and the preservation of mitochondrial function. Knockdown of ArgRS administration could be a promising approach to protect ischemic stroke.

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Carnosic acid alleviates depression-like behaviors on chronic mild stressed mice via PPAR-γ-dependent regulation of ADPN/FGF9 pathway - Xiao-qing Wang; Ya-hui Tang; Gui-rong Zeng; Li-feng Wu; Ying-jun Zhou; Ze-neng Cheng; De-Jian Jiang (Psychopharmacology, 2021)

Discovery of new small-molecule cyclin-dependent kinase 6 inhibitors through computational approaches - Xiaojiao Luo; Yu Zhao; Pan Tang; Xingkai Du; Feng Li; Qingying Wang; Rong Li; Jun He (Molecular Diversity, 2021)

Paeonol ameliorates CFA-induced inflammatory pain by inhibiting HMGB1/TLR4/NF-κB p65 pathway - Chen Qiu; Liu-Di Yang; Wen Yu; Dan-Dan Tian; Mei-Rong Gao; Wen-Ju Wang; Xu-Bo Li; Yu-Mei Wu; Min Wang (Metabolic Brain Disease, 2021)

Soil alkaline phosphatase activity and bacterial phoD gene abundance and diversity under regimes of inorganic fertilizer reduction with straw - Yingyan Wang; Rong Huang; Guoxing Xu; Jiacheng Li; Zifang Wang; En Ci; Ming Gao (Journal of Soils and Sediments, 2021)

Geochemical characteristics and geological significance of chert nodules in Qixia formation, Pingding Mountain, lower Yangtze Plate - Jun Li; Lu-wang Chen; Chun-ming Hao; Jie Zhang; Song Chen; He-rong Gui (Journal of Mountain Science, 2021)

Paenibacillus turpanensis sp. nov., isolated from a salt lake of Turpan city in Xinjiang province, north-west China - Li Yang; Hua-Wei Huang; Yun Wang; Ya-Rong Kou; Min Yin; Yu Li; Xue-Qian Wang; Gui-Fang Zhao; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

Mapping quantitative trait loci associated with stem-related traits in maize (Zea mays L.) - Qiqi Shang; Degui Zhang; Rong Li; Kaixin Wang; Zimeng Cheng; Zhiqiang Zhou; Zhuanfang Hao; Jinbao Pan; Xinhai Li; Liyu Shi (Plant Molecular Biology, 2020)

Natural products development under epigenetic modulation in fungi - Chi-Ying Li; Yu-Ming Chung; Yang-Chang Wu; Attila Hunyadi; Clay C. C. Wang; Fang-Rong Chang (Phytochemistry Reviews, 2020)

Lycium barbarum polysaccharide protects against Homocysteine-induced Vascular smooth muscle cell proliferation and phenotypic transformation via PI3K/Akt pathway - Minghao Zhang; Fan Li; Smritee Pokharel; Ting Ma; Xiuyu Wang; Yiyong Wang; Weirong Wang; Rong Lin (Journal of Molecular Histology, 2020)

Patterns of intrinsic brain activity in essential tremor with resting tremor and tremor-dominant Parkinson’s disease - Jun-ying Li; Zhong-jiao Lu; Xue-ling Suo; Nan-nan Li; Du Lei; Ling Wang; Jia-xin Peng; Li-ren Duan; Jing Xi; Yi Jiang; Qi-yong Gong; Rong Peng (Brain Imaging and Behavior, 2020)

Prenatal diagnosis and neonatal phenotype of a de novo microdeletion of 17p11.2p12 associated with Smith‒Magenis syndrome and external genital defects - Pingping Zhang; Yanmei Sun; Haishen Tian; Limin Rong; Fangna Wang; Xiaoping Yu; Yali Li; Jian Gao (Journal of Genetics, 2020)

High-frequency compensation for seismic data based on adaptive generalized S transform - Hui-Feng Li; Jin Wang; Zheng-Rong Wei; Fei-Long Yang (Applied Geophysics, 2020)

Multiple metal(loid)s bioaccessibility from cooked seafood and health risk assessment - Wen Liao; Wenbo Zhao; Ye Wu; Nan Rong; Xiaowei Liu; Kaiming Li; Guang Wang (Environmental Geochemistry and Health, 2020)

Quantitative Angiographic Hemodynamic Evaluation After Revascularization Surgery for Moyamoya Disease - Yu Chen; Li Ma; Shuo Yang; Jan-Karl Burkhardt; Junlin Lu; Xun Ye; Weijian Jiang; Zeguang Ren; Rong Wang; Xiaolin Chen; Yuanli Zhao (Translational Stroke Research, 2020)
The corresponding hemodynamic changes of the internal carotid artery (ICA) after the revascularization surgery for moyamoya disease (MMD) remain unclear. The aim of this study was to analyze the hemodynamic changes of the ipsilateral ICA after the combined direct and indirect extracranial-intracranial (EC-IC) bypass. MMD patients undergoing combined EC-IC bypass were retrospectively reviewed. The mean transit time (MTT) of ICA was evaluated by color-coding angiography before revascularization and at follow-up. The MTT defined as the blood transit time between the end of cervical portion (C1) and the C7 segment of ICA. The clinical prognosis was assessed with Matsushima grading system, moyamoya vessel reduction system, and modified Rankin Scale (mRS). The correlation between hemodynamic parameter and prognosis was analyzed. Subgroup analysis was conducted between different presentations and different ages. Fifty-one patients were identified and the mean imaging follow-up interval was 5.5 months. The ICA-MTT was increased after the combined revascularization ( P < 0.001) compared with contralateral ICA. Faster preoperative ICA-MTT was significantly associated with improved mRS in the ischemic group ( P = 0.05). The increased ICA-MTT was significantly associated with favorable neoangiogenesis ( P = 0.04), moyamoya vessel reduction (> 50%) ( P = 0.023), and improved mRS score ( P = 0.008). In subgroup analysis, the correlation in the ischemic subgroup and adult subgroup remained significant. In this cohort, the ICA-MTT increased after the combined EC-IC bypass, and there was a positive correlation between the increased blood transit time and favorable outcomes. Color-coding DSA proved to be useful as a quantitative and serial method to monitor postoperative courses after revascularization in MMD.

Leptin promotes endothelial dysfunction in chronic kidney disease by modulating the MTA1-mediated WNT/β-catenin pathway - Bing Liu; Jiao Qiao; Jinxiu Hu; Minghua Fan; Yanfang Zhao; Hong Su; Ziyang Wang; Qun Yu; Qiqi Ma; Yanmei Li; Zhimei Lv; Rong Wang (Molecular and Cellular Biochemistry, 2020)

Identification, functional characterization, and estrogen regulation on gonadotropin-releasing hormone in the spotted scat, Scatophagus argus - Hua-pu Chen; Xue-fan Cui; Yao-rong Wang; Zhi-yuan Li; Chang-xu Tian; Dong-neng Jiang; Chun-Hua Zhu; Yong Zhang; Shui-sheng Li; Guang-li Li (Fish Physiology and Biochemistry, 2020)

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

An evaluation of the core bacterial communities associated with hypersaline environments in the Qaidam Basin, China - Derui Zhu; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Guoping Shen; Yongzhen Li; Rong Wang (Archives of Microbiology, 2020)

Retraction Note to: Ambient air pollution and adverse birth outcomes: a systematic review and meta-analysis - Le-qian Guo; Yu Chen; Bai-bing Mi; Shao-nong Dang; Dou-dou Zhao; Rong Liu; Hong-li Wang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2020)

Water and salt stresses do not trigger bottom-up effects on plant-mediated indirect interactions between a leaf chewer and a sap-feeder - Yong-Cheng Dong; Zhi-Jian Wang; Rong-Yan Bu; Hui-Jie Dai; Li-Jun Zhou; Peng Han; Edwige Amiens-Desneux; Philippe Bearez; Nicolas Desneux (Journal of Pest Science, 2020)

NLRP6 contributes to inflammation and brain injury following intracerebral haemorrhage by activating autophagy - Han Xiao; Hui Chen; Rong Jiang; Li Zhang; Lu Wang; Hui Gan; Ning Jiang; Jing Zhao; Xuan Zhai; Ping Liang (Journal of Molecular Medicine, 2020)

Heat-air-moisture coupled model for radon migration in a porous media - Yu Cui; Shengyang Feng; Puxin Chen; Yongjun Ye; Yurong Wu; Ce Li; Rong Yang; Hong Wang (Environmental Science and Pollution Research, 2020)

Changes in leaf vein traits among vein types of alpine grassland plants on the Tibetan Plateau - Chang-shun Wang; Wang-wang Lyu; Li-li Jiang; Shi-ping Wang; Qi Wang; Fan-dong Meng; Li-rong Zhang (Journal of Mountain Science, 2020)

Brief report of the first cured 2019-nCoV pneumonia patient in West China Hospital - En-Qiang Chen; Li-Chun Wang; Guang-Min Tang; Yao Yang; Min-Jin Wang; Rong Deng; Fang Chen; Meng-Lan Wang; Ya-Chao Tao; Ping Feng; Hong Tang (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Fluoride-Induced Alteration in the Diversity and Composition of Bacterial Microbiota in Mice Colon - Rong Fu; Ruiyan Niu; Rui Li; Baijuan Yue; Xuhua Zhang; Qiqi Cao; Jundong Wang; Zilong Sun (Biological Trace Element Research, 2020)

Oceanobacillus halotolerans sp. nov., a bacterium isolated from salt lake in Xinjiang province, north-west China - Wen-Yong Zhu; Li Yang; Yong-Jiang Shi; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2020)

Genetic diversity analysis for narrow-leafed lupin (Lupinus angustifolius L.) by SSR markers - Yishan Ji; Rong Liu; Jinguo Hu; Yuning Huang; Dong Wang; Guan Li; Md. Mosiur Rahman; Hongyan Zhang; Chenyu Wang; Mengwei Li; Tao Yang; Xuxiao Zong (Molecular Biology Reports, 2020)

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

Bergaptol, a mechanism-based inactivator of CYP2C9 - Tingting Jiang; Ting Cheng; Jing Li; Mengyue Zhou; Rong Tan; Xiaojing Yang; Yang Wang; Weiwei Li; Jiang Zheng (Medicinal Chemistry Research, 2020)

A review of progress in coupled ocean-atmosphere model developments for ENSO studies in China - Rong-Hua Zhang; Yongqiang Yu; Zhenya Song; Hong-Li Ren; Youmin Tang; Fangli Qiao; Tongwen Wu; Chuan Gao; Junya Hu; Feng Tian; Yuchao Zhu; Lin Chen; et al. (Journal of Oceanology and Limnology, 2020)

Crosstalk between PKC and MAPK pathway activation in cardiac fibroblasts in a rat model of atrial fibrillation - Wei-hua Guo; Xian Wang; Mei-sheng Shang; Zhe Chen; Qi Guo; Li Li; Hai-ying Wang; Rong-hui Yu; Chang-sheng Ma (Biotechnology Letters, 2020)

A study on the effects of salinity and pH on PSII function in mulberry seedling leaves under saline–alkali mixed stress - Zhang Huihui; Li Xin; Che Yan-hui; Wang Yue; Li Ma-bo; Yang Rong-yi; Xu Nan; Sun Guang-yu (Trees, 2020)

Synthesis, pharmacological evaluation and molecular docking of novel R-/S-2-(2-hydroxypropanamido)-5-trifluoromethyl benzoic acid as dual anti-inflammatory anti-platelet aggregation agents - Rong Rong; Rui-zhen Zhang; Xin Wang; Yu-han Dan; Yun-li Zhao; Zhi-guo Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

The isolation and culture of giant panda (Ailuropoda melanoleuca) breast milk cells - Chen Yijiao; Wang Donghui; Liu Yuliang; Li Feiping; He Ping; Cai Zhigang; Zhang Hao; Chen Min; Hou Rong; An Junhui (In Vitro Cellular & Developmental Biology - Animal, 2020)

Sugar transporter genes in grass carp (Ctenopharyngodon idellus): molecular cloning, characterization, and expression in response to different stocking densities - Xiao Liang; Fengying Yan; Yu Gao; Mei Xiong; Haishan Wang; Kommaly Onxayvieng; Rong Tang; Li Li; Xi Zhang; Wei Chi; Marina Piria; Mirna Mrkonjić Fuka; et al. (Fish Physiology and Biochemistry, 2020)

Disruption of functional connectivity among subcortical arousal system and cortical networks in temporal lobe epilepsy - Rong Li; Chongyu Hu; Liangcheng Wang; Ding Liu; Dingyang Liu; Wei Liao; Bo Xiao; Huafu Chen; Li Feng (Brain Imaging and Behavior, 2020)

Molecular evolution of GII.P17-GII.17 norovirus associated with sporadic acute gastroenteritis cases during 2013–2018 in Zhoushan Islands, China - Can Chen; Bing Wu; Hui Zhang; Ke-Feng Li; Rong Liu; Hong-Ling Wang; Jian-Bo Yan (Virus Genes, 2020)

Method for obtaining high-resolution velocity spectrum based on weighted similarity - Xing-Rong Xu; Qin Su; Jun-Fa Xie; Jing Wang; Long-Jiang Kou; Meng-Li Liu (Applied Geophysics, 2020)

Transcript profiling of genes involved in carotenoid biosynthesis among three carrot cultivars with various taproot colors - Ya-Hui Wang; Tong Li; Rong-Rong Zhang; Ahmed Khadr; Yong-Sheng Tian; Zhi-Sheng Xu; Ai-Sheng Xiong (Protoplasma, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Prevalence of RNF213 variants in symptomatic intracranial arterial stenosis/occlusion in China - Xunsha Sun; Man Luo; Jiaoxing Li; Rong Lai; Jing Lin; Yufang Wang; Xiaowei Xu; Shaoqing Wu; Wenli Sheng (Molecular Genetics and Genomics, 2020)

First report of cucumber mosaic virus infecting bahizi (Angelica dahurica) in China - Ruo-Fan Wei; Wan-Long Ding; Yong Li; Rong Wang (Journal of Plant Pathology, 2020)

MiR-145 alleviates Hcy-induced VSMC proliferation, migration, and phenotypic switch through repression of the PI3K/Akt/mTOR pathway - Minghao Zhang; Fan Li; Xiuyu Wang; Jian Gong; Yushan Xian; Guan Wang; Zihan Zheng; Chenxu Shang; Bo Wang; Yanhao He; Weirong Wang; Rong Lin (Histochemistry and Cell Biology, 2020)

The Diversity of Associated Microorganisms in Different Organs and Rhizospheric Soil of Arctium lappa L. - Yanping Xing; Yanyun Yang; Liang Xu; Ning Hao; Rong Zhao; Jiahao Wang; Shengnan Li; Dachuan Zhang; Tingting Zhang; Tingguo Kang (Current Microbiology, 2020)

Decrypting the crosstalk of noncoding RNAs in the progression of IPF - Yujuan Wang; Han Xiao; Fenglian Zhao; Han Li; Rong Gao; Bingdi Yan; Jin Ren; Junling Yang (Molecular Biology Reports, 2020)
Idiopathic pulmonary fibrosis (IPF) is an agnogenic, rare, and lethal disease, with high mortality and poor prognosis and a median survival time as short as 3 to 5 years after diagnosis. No effective therapeutic drugs are still not available not only in clinical practice, but also in preclinical phases. To better and deeper understand pulmonary fibrosis will provide more effective strategies for therapy. Mounting evidence suggests that noncoding RNAs (ncRNAs) and their interactions may contribute to lung fibrosis; however, the mechanisms underlying their roles are largely unknown. In this review, we systematically summarized the recent advances regarding the crucial roles of long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and circular RNAs (circRNAs) and crosstalk among them in the development of IPF. The perspective for related genes was well highlighted. In summary, ncRNA and their interactions play a key regulatory part in the progression of IPF and are bound to provide us with new diagnostic and therapeutic targets.

Novel 28 microsatellite loci using high-throughput sequencing for an endangered species on Metasequoia glyptostroboides (Cupressaceae) - Jing-Wen Wang; Tong-Lei Xu; Ghenet Weldegebriel Sereke; Rong Wang; Yuan-Yuan Li (Molecular Biology Reports, 2020)

Circadian gene Clock participates in mitochondrial apoptosis pathways by regulating mitochondrial membrane potential, mitochondria out membrane permeablization and apoptosis factors in AML12 hepatocytes - Shuhong Yang; Yanyou Liu; Yimei Guo; Rong Liu; Fang Qi; Xiaoxue Li; Hang Yu; Shuting Cheng; Zhengrong Wang (Molecular and Cellular Biochemistry, 2020)

Predictors of nasal bacterial culture rates in patients with chronic rhinosinusitis - Jing-Jie Wang; Chih-Yi Chen; Kai-Li Liang; Rong-San Jiang (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Looking back over the past two decades on the nexus between air pollution, energy consumption, and agricultural productivity in China: a qualitative analysis based on the ARDL bounds testing model - Mansoor Ahmed Koondhar; Houjian Li; Huiling Wang; Sanchir Bold; Rong Kong (Environmental Science and Pollution Research, 2020)

Cell membrane damage induced by continuous stress of artemisinin sustained-release microspheres (ASMs) on Microcystis aeruginosa at different physiological stages - Lixiao Ni; Feifei Yue; Jianhua Zhang; Shiyi Rong; Xuanyu Liu; Yifei Wang; Peifang Wang; Danye Li; Na Wang; Hanqi Wu; Shiyin Li (Environmental Science and Pollution Research, 2020)

Functional Analysis of Sheep POU2F3 Isoforms - Guang-Wei Ma; Yan-Kai Chu; Hua Yang; Xiao-Hong Yan; En-Guang Rong; Hui Li; Ning Wang (Biochemical Genetics, 2020)
POU domain class 2 transcription factor 3 (POU2F3) plays an important role in keratinocyte proliferation and differentiation. Our previous study identified four sheep POU2F3 transcript variants ( POU2F3-1 , POU2F3-2 , POU2F3-3 , and POU2F3-4 ), encoding three POU2F3 protein isoforms (POU2F3-1, POU2F3-2, and POU2F3-3). However, the functional differences among the three POU2F3 isoforms remain unknown. The objective of this study was to determine the tissue expression pattern of the four POU2F3 transcript variants in sheep and to investigate the functional differences in cell proliferation among the three POU2F3 isoforms. Quantitative RT-PCR analysis showed that the four POU2F3 transcripts were ubiquitously expressed in all tested adult sheep tissues, and POU2F3-1 exhibited higher expression level than the other three POU2F3 transcript variants in skin ( P P P P > 0.05). Dual luciferase reporter assays demonstrated that overexpression of any one of the three POU2F3 isoforms significantly inhibited the promoter activities of keratin 14 ( KRT14 ) and matrix metalloproteinase 19 ( MMP19 ) genes ( P KRT14 and MMP19 genes than POU2F3-1 and POU2F3-2 ( P P > 0.05). These results suggest three sheep POU2F3 isoforms have similar functional effects, but to a different extent.

Community structure of Anaeromyxobacter in Fe(III) reducing enriched cultures of paddy soils - Kun Wang; Rong Jia; Lina Li; Rui Jiang; Dong Qu (Journal of Soils and Sediments, 2020)

Effect of different seasons (spring vs summer) on the microbiota diversity in the feces of dairy cows - Han Li; Rong Li; Huijun Chen; Jing Gao; Yu Wang; Yifeng Zhang; Zhili Qi (International Journal of Biometeorology, 2020)

Reference Point Based Multi-Objective Optimization of Reservoir Operation: a Comparison of Three Algorithms - Rong Tang; Ke Li; Wei Ding; Yuntao Wang; Huicheng Zhou; Guangtao Fu (Water Resources Management, 2020)

Utilization of pre-existing competent and barren quartz veins as hosts to later orogenic gold ores at Huangjindong gold deposit, Jiangnan Orogen, southern China - Liang Zhang; David I. Groves; Li-Qiang Yang; Si-Chen Sun; Roberto F. Weinberg; Jiu-Yi Wang; Sheng-Gang Wu; Lei Gao; Lan-Ling Yuan; Rong-Hua Li (Mineralium Deposita, 2020)

Analysis of nicotine-induced metabolic changes in Blakeslea trispora by GC-MS - Yang Liu; You-ran Shao; Xiang-yu Li; Zhi-ming Wang; Li-rong Yang; Yu-zhou Zhang; Mian-bin Wu; Jian-ming Yao (Journal of Zhejiang University-SCIENCE B, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Developing stripe rust resistant wheat (Triticum aestivum L.) lines with gene pyramiding strategy and marker-assisted selection - Rong Liu; Jing Lu; Min Zhou; Shigang Zheng; Zehou Liu; Chihong Zhang; Mei Du; Minxiu Wang; Yunfang Li; Yu Wu; Lei Zhang (Genetic Resources and Crop Evolution, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Complete genomic sequence of crow-dipper mosaic-associated virus, a novel macluravirus infecting Pinellia ternata - Rong Wang; Bingwei Chen; Yong Li; Tianyou Wang; Wanlong Ding (Archives of Virology, 2020)

Antler stem cells as a novel stem cell source for reducing liver fibrosis - Xiaoli Rong; Yanyan Yang; Guokun Zhang; Haiying Zhang; Chunyi Li; Yimin Wang (Cell and Tissue Research, 2020)
Liver fibrosis results from collagen fiber deposition. Antler stem cells (ASCs) naturally in vivo differentiate into cartilage, which is only made of Col II in collagen component; whereas liver fibrosis is caused by over-abundance of Col I and III. In addition, ASCs can effectively promote regenerative wound healing in which tissue contains very few collagen fibers (Col I). In this study, we investigate the therapeutic effects of ASCs in a rat model of CCl 4 -induced liver fibrosis. Rats were treated with ASCs for 4 weeks in vivo, then biochemical and histopathological analyses were performed. Furthermore, we established cell co-culture systems of hepatic stellate cells (HSCs) and ASCs and of M1 macrophages and ASCs in vitro. Mesenchymal stem cells (MSCs) were used as a positive control. The results showed that ASC transplantation alleviated liver fibrosis effectively as evidenced by reduced collagen accumulation, decreased fatty degeneration, increased hepatocyte regeneration, decreased inflammation and significantly enhanced liver function; moreover, ASCs decreased the expression of pro-fibrogenic factors including TGF-β and α-SMA. Additionally, our study showed that ASCs inhibit HSC activation and proliferation by controlling the expression of MMPs, TIMP1, TGF-β, α-SMA and COL1A2 involved in these processes. Our results suggested that ASCs alleviate liver fibrosis effectively and inhibit HSC activation. Thus, ASCs may serve as a novel stem cell source for the treatment of liver fibrosis in the clinic.

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

DNA methylation levels in different tissues in tea plant via an optimized HPLC method - Ying Gao; Jia-Li Hao; Zhen Wang; Kwan-Jeong Song; Jian-Hui Ye; Xin-Qiang Zheng; Yue-Rong Liang; Jian-Liang Lu (Horticulture, Environment, and Biotechnology, 2019)

Effects of cyanobacteria decomposition on the remobilization and ecological risk of heavy metals in Taihu Lake - Lixiao Ni; Guoxiu Gu; Shiyi Rong; Lingling Hu; Peifang Wang; Shiyin Li; Dandan Li; Xuanyu Liu; Yifei Wang; Kumud Acharya (Environmental Science and Pollution Research, 2019)

Effects of Different Preservation Methods on Physicochemical Property of Marine Pathogen Vibrio anguillarum - Yongxiang Yu; Zheng Zhang; Yingeng Wang; Meijie Liao; Xiaojun Rong; Bin Li; Hao Zhang (Journal of Ocean University of China, 2019)

Interaction Between Planetary Boundary Layer and PM2.5 Pollution in Megacities in China: a Review - Yucong Miao; Jing Li; Shiguang Miao; Huizheng Che; Yaqiang Wang; Xiaoye Zhang; Rong Zhu; Shuhua Liu (Current Pollution Reports, 2019)
Purpose of Review During the past decades, the number and size of megacities have been growing dramatically in China. Most of Chinese megacities are suffering from heavy PM 2.5 pollution. In the pollution formation, the planetary boundary layer (PBL) plays an important role. This review is aimed at presenting the current state of understanding of the PBL-PM 2.5 interaction in megacities, as well as to identify the main gaps in current knowledge and further research needs. Recent Findings The PBL is critical to the formation of urban PM 2.5 pollution at multiple temporal scales, ranging from diurnal change to seasonal variation. For the essential PBL structure/process in pollution, the coastal megacities have different concerns from the mountainous or land-locked megacities. In the coastal cities, the recirculation induced by sea-land breeze can accumulate pollutants, whereas in the valley/basin, the blocking effects of terrains can lead to stagnant conditions and thermal inversion. Within a megacity, although the urbanization-induced land use change can cause thermodynamic perturbations and facilitate the development of PBL, the increases in emissions outweigh this impact, resulting in a net increase of aerosol concentration. Moreover, the aerosol radiative effects can modify the PBL by heating the upper layers and reducing the surface heat flux, suppressing the PBL and exacerbating the pollution. Summary This review presented the PBL-PM 2.5 interaction in 13 Chinese megacities with various geographic conditions and elucidated the critical influencing processes. To further understand the complicated interactions, long-term observations of meteorology and aerosol properties with multi-layers in the PBL need to be implemented.

Root diversity in sesame (Sesamum indicum L.): insights into the morphological, anatomical and gene expression profiles - Ruqi Su; Rong Zhou; Marie Ali Mmadi; Donghua Li; Lu Qin; Aili Liu; Jianqiang Wang; Yuan Gao; Mengyuan Wei; Lisong Shi; Ziming Wu; Jun You; et al. (Planta, 2019)

Effects of demethylating reagent 5-aza-2′-deoxycytidine on the growth and cephalotaxine production in Cephalotaxus mannii suspension cells - Li-Rong Wei; Wang-Yan Qin; Yong-Cheng Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Engagement of MicroRNA-155 in Exaggerated Oxidative Stress Signal and TRPA1 in the Dorsal Horn of the Spinal Cord and Neuropathic Pain During Chemotherapeutic Oxaliplatin - Fenghua Miao; Rong Wang; Guozhen Cui; Xiaoguang Li; Ting Wang; Xue Li (Neurotoxicity Research, 2019)

Microencapsulated β-carotene preparation using different drying treatments - Xiang-yu Li; Mian-bin Wu; Min Xiao; Shu-huan Lu; Zhi-ming Wang; Jian-ming Yao; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2019)

Development, Optimization, and Evaluation In Vitro/In Vivo of Oral Liquid System for Synchronized Sustained Release of Levodopa/Benserazide - Yang Qu; Wen-Long Lai; Yuan-Rong Xin; Fei-Qin Zhu; Yuan Zhu; Li Wang; Yue-ping Ding; Ying Xu; Hong-Fei Liu (AAPS PharmSciTech, 2019)

Identification and Phylogenetic Analysis of Xanthomonas albilineans (Ashby) Dowson Based on Multiple Gene Sequences in Yunnan Province, China - Rong-Yue Zhang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Wen-Feng Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin; Ying-Kun Huang (Sugar Tech, 2019)

Molecular Identification of Sugarcane White Leaf in Puer, Yunnan Province, China - Rong-Yue Zhang; Wen-Feng Li; Ying-Kun Huang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Sugar Tech, 2019)

Developing genetically segregating populations for localization of novel sugarcane brown rust resistance genes - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Hong-Li Shan; Rong-Yue Zhang; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Euphytica, 2019)

Convectively Coupled Equatorial Waves Simulated by CAMS-CSM - Lu Wang; Tianjun Zhou; Jian Li; Xinyao Rong; Haoming Chen; Yufei Xin; Jingzhi Su (Journal of Meteorological Research, 2019)

Interseismic Coupling in the Central Nepalese Himalaya: Spatial Correlation with the 2015 Mw 7.9 Gorkha Earthquake - Shuiping Li; Qi Wang; Gang Chen; Ping He; Kaihua Ding; Yunguo Chen; Rong Zou (Pure and Applied Geophysics, 2019)

Salvianolic acid B protects against ANIT-induced cholestatic liver injury through regulating bile acid transporters and enzymes, and NF-κB/IκB and MAPK pathways - Shengnan Li; Rong Wang; Bin Wu; Yuanyuan Wang; Fuxing Song; Yanqiu Gu; Yongfang Yuan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Development of a loop-mediated isothermal amplification for rapid diagnosis of Aphelenchoides ritzemabosi - Dong-Wei Wang; Chun-Ling Xu; Zong-Shi Bai; Jun-Yi Li; Yu-Chun Han; Li-Rong Zhao; Hui Xie (European Journal of Plant Pathology, 2019)

Identification of cis-regulatory regions responsible for developmental and hormonal regulation of HbHMGS1 in transgenic Arabidopsis thaliana - Xiao-Xiao Gong; Bing-Yu Yan; Yu-Rong Tan; Xuan Gao; Dan Wang; Heng Zhang; Peng Wang; Shuang-Jiang Li; Yi Wang; Lu-Yao Zhou; Jin-Ping Liu (Biotechnology Letters, 2019)

Molecular cloning and functional characterization of a seed-specific VvβVPE gene promoter from Vitis vinifera - Peijie Gong; Rong Wei; Yan Li; Ruipu Wang; Yujin Tang; Ling Wang; Huijun Zhu; Yuejin Wang; Chaohong Zhang (Planta, 2019)

Effect of Apolipoprotein E Genotypes on Huntington’s Disease Phenotypes in a Han Chinese Population - Xiao-Yan Li; Yan-Bin Zhang; Miao Xu; Hong-Rong Cheng; Yi Dong; Wang Ni; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2019)

Numerical Study of Damage Evolution Law of Coal Mine Roadway by Particle Flow Code (PFC) Model - Wan-rong Liu; Xiao Wang; Chuan-ming Li (Geotechnical and Geological Engineering, 2019)

Correction to: Cellular distribution of cadmium in two amaranth (Amaranthus mangostanus L.) cultivars differing in cadmium accumulation - Keyu Chi; Rong Zou; Li Wang; Wenmin Huo; Hongli Fan (Environmental Science and Pollution Research, 2019)

Cellular distribution of cadmium in two amaranth (Amaranthus mangostanus L.) cultivars differing in cadmium accumulation - Keyu Chi; Rong Zou; Li Wang; Wenmin Huo; Hongli Fan (Environmental Science and Pollution Research, 2019)

Abnormal dynamics of functional connectivity density in children with benign epilepsy with centrotemporal spikes - Rong Li; Liangcheng Wang; Heng Chen; Xiaonan Guo; Wei Liao; Ye-Lei Tang; Huafu Chen (Brain Imaging and Behavior, 2019)

Cloud Radiative Feedbacks during the ENSO Cycle Simulated by CAMS-CSM - Lin Chen; Lijuan Hua; Xinyao Rong; Jian Li; Lu Wang; Guo Zhang; Ming Sun; Zi’an Ge (Journal of Meteorological Research, 2019)

Geological and geochemical characteristics of the Baogudi Carlin-type gold district (Southwest Guizhou, China) and their geological implications - Songtao Li; Yong Xia; Jianzhong Liu; Zhuojun Xie; Qinping Tan; Yimeng Zhao; Minghua Meng; Lijin Tan; Rong Nie; Zepeng Wang; Guanghong Zhou; Haiyan Guo (Acta Geochimica, 2019)

The potential growth and lipid accumulation in Coccomyxa subellipsoidea triggered by glucose combining with sodium acetate - Zhenyao Wang; Fei Luo; Ziting Wang; Rong Zhou; Yufang Tang; Yuqin Li (World Journal of Microbiology and Biotechnology, 2019)

Influences of immersion bathing in Bacillus velezensis DY-6 on growth performance, non-specific immune enzyme activities and gut microbiota of Apostichopus japonicus - Jinyan Wang; Bin Li; Yingeng Wang; Meijie Liao; Xiaojun Rong; Zheng Zhang (Journal of Oceanology and Limnology, 2019)

Fluorescence “Off-On” Probe for L-Cysteine Detection Based on Nitrogen Doped Carbon Dots - Yin-long Xu; Rong-biao Bai; Cai-yu Qi; Zeng Ren; Xiu-zhi Jia; Zi-gui Kan; Cao-long Li; Fei Wang (Journal of Fluorescence, 2019)

Identification and Evaluation of Resistance to Sugarcane Streak Mosaic Virus (SCSMV) and Sorghum Mosaic Virus (SrMV) in Excellent Sugarcane Innovation Germplasms in China - Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Xin Lu; Rong-Yue Zhang; Xiao-Yan Wang; Jiong Yin; Zhi-Ming Luo; Ying-Kun Huang (Sugar Tech, 2019)

Field Resistance of Different Sugarcane Varieties to Sugarcane Thrips (Fulmekiola serratus) in China - Zhi-Ming Luo; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Jie Li; Jiong Yin (Sugar Tech, 2019)

EEG-based mild depression recognition using convolutional neural network - Xiaowei Li; Rong La; Ying Wang; Junhong Niu; Shuai Zeng; Shuting Sun; Jing Zhu (Medical & Biological Engineering & Computing, 2019)

Calcium intake and colon cancer risk subtypes by tumor molecular characteristics - NaNa Keum; Li Liu; Tsuyoshi Hamada; Zhi Rong Qian; Jonathan A. Nowak; Yin Cao; Annacarolina da Silva; Keisuke Kosumi; Mingyang Song; Daniel Nevo; Molin Wang; Andrew T. Chan; et al. (Cancer Causes & Control, 2019)

Effects of NaCl stress on growth of Portulaca oleracea and underlying mechanisms - Jin-Cheng Xing; Jing Dong; Mao-Wen Wang; Chong Liu; Bao-Quan Zhao; Zhu-Gui Wen; Xiao-Mei Zhu; Hai-Rong Ding; Xiao-Hui Zhao; Li-Zhou Hong (Brazilian Journal of Botany, 2019)

The relationship between surface spectral albedo and soil moisture in an arid Gobi area - Zhenchao Li; Jiaxi Yang; Xiaoqing Gao; Ye Yu; Zhiyuan Zheng; Rong Liu; Chao Wang; Xuhong Hou; Zhigang Wei (Theoretical and Applied Climatology, 2019)

A facile extraction of keratin from pig hair and its properties - Quan-Fang Li; Yufeng He; Rong-Min Wang (Biologia, 2019)

Chronic stress impairs the aquaporin-4-mediated glymphatic transport through glucocorticoid signaling - Fang Wei; Jian Song; Cui Zhang; Jun Lin; Rong Xue; Li-Dong Shan; Shan Gong; Guo-Xing Zhang; Zheng-Hong Qin; Guang-Yin Xu; Lin-Hui Wang (Psychopharmacology, 2019)

Genetic diversity of 324 cultivated tomato germplasm resources using agronomic traits and InDel markers - Lan Jin; Liping Zhao; Yinlei Wang; Rong Zhou; Liuxia Song; Liping Xu; Xia Cui; Ren Li; Wengui Yu; Tongmin Zhao (Euphytica, 2019)

A B-box zinc finger protein, MdBBX10, enhanced salt and drought stresses tolerance in Arabidopsis - Xin Liu; Rong Li; Yaqing Dai; Li Yuan; Qinghua Sun; Shizhong Zhang; Xiaoyun Wang (Plant Molecular Biology, 2019)

RETRACTED ARTICLE: Ambient air pollution and adverse birth outcomes: a systematic review and meta-analysis - Le-Qian Guo; Yu Chen; Bai-Bing Mi; Shao-Nong Dang; Dou-Dou Zhao; Rong Liu; Hong-Li Wang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2019)

Relationship between polymorphisms of the lipid metabolism-related gene PLA2G16 and risk of colorectal cancer in the Chinese population - Xiao-Nv Xie; Jing Yu; Li-Hua Zhang; Zhi-Ying Luo; Dong-Sheng Ouyang; Ling-Jie Zheng; Chun-Yang Wang; Li Yang; Ling Chen; Zhi-Rong Tan (Functional & Integrative Genomics, 2019)

Chloroplast proteomic analysis of Triticum aestivum L. seedlings responses to low levels of UV-B stress reveals novel molecular mechanism associated with UV-B tolerance - Limei Gao; Xiaofei Wang; Yongfeng Li; Rong Han (Environmental Science and Pollution Research, 2019)

A CkDREB1 gene isolated from Caragana korshinskii Kom. enhances Arabidopsis drought and cold tolerance - Ziyi Zhang; Qi Yang; Chunlin Zhang; Lili Wei; Rong Yue; Guojing Li; Xiaofei Lin; Ruigang Wang (Brazilian Journal of Botany, 2019)

Genomewide analysis of homeobox gene family in apple (Malus domestica Borkh.) and their response to abiotic stress - Rong Li; Hongjuan Ge; Yaqing Dai; Li Yuan; Xin Liu; Qinghua Sun; Xiaoyun Wang (Journal of Genetics, 2019)

Effects of the arterial radius and the center-line velocity on the conductivity and electrical impedance of pulsatile flow in the human common carotid artery - Hua Shen; Siqi Li; Yu Wang; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2019)

The response of metabolically active Clostridium community to initial pH shift is closely correlated with microbial Fe(III) reduction in flooded paddy soils - Lina Li; Zhi Qu; Baoli Wang; Rong Jia; Dong Qu (Journal of Soils and Sediments, 2019)

Topical delivery of 3,5,4′-trimethoxy-trans-stilbene-loaded microemulsion-based hydrogel for the treatment of osteoarthritis in a rabbit model - Xiong-Bin Hu; Rong-Rong Kang; Tian-Tian Tang; Yong-Jiang Li; Jun-Yong Wu; Jie-Min Wang; Xin-Yi Liu; Da-Xiong Xiang (Drug Delivery and Translational Research, 2019)

An Assessment of ENSO Stability in CAMS Climate System Model Simulations - Lijuan Hua; Lin Chen; Xinyao Rong; Jian Li; Guo Zhang; Lu Wang (Journal of Meteorological Research, 2019)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

Establishment and application of distant hybridization technology in fish - Shi Wang; Chenchen Tang; Min Tao; Qinbo Qin; Chun Zhang; Kaikun Luo; Rurong Zhao; Jing Wang; Li Ren; Jun Xiao; Fangzhou Hu; Rong Zhou; et al. (Science China Life Sciences, 2019)

Silurian integrative stratigraphy and timescale of China - Jiayu Rong; Yi Wang; Renbin Zhan; Junxuan Fan; Bing Huang; Peng Tang; Yue Li; Xiaole Zhang; Rongchang Wu; Guangxu Wang; Xin Wei (Science China Earth Sciences, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Hyperspectral discrimination of foliar biotic damages in rice using principal component analysis and probabilistic neural network - Zhan-Yu Liu; Jia-Guo Qi; Nan-Nan Wang; Zeng-Rong Zhu; Ju Luo; Li-Juan Liu; Jian Tang; Jia-An Cheng (Precision Agriculture, 2018)

Nutrient Balancing by Captive Golden Snub-Nosed Monkeys (Rhinopithecus roxellana) - Stephanie T. Chen; Xi Luo; Rong Hou; David Raubenheimer; Weihong Ji; Xuelin Jin; Zhi Jiang; Xuewei Yu; Jiajia Wang; Min Li; Songtao Guo; Baoguo Li (International Journal of Primatology, 2018)

Application of Bacillus velezensis NJAU-Z9 Enhanced Plant Growth Associated with Efficient Rhizospheric Colonization Monitored by qPCR with Primers Designed from the Whole Genome Sequence - Yang Zhang; Xu Gao; Shuai Wang; Chengzhi Zhu; Rong Li; Qirong Shen (Current Microbiology, 2018)

Increased productivity of l-2-aminobutyric acid and total turnover number of NAD+/NADH in a one-pot system through enhanced thermostability of l-threonine deaminase - Ying Wang; Guo-Si Li; Pei Qiao; Ling Lin; Hai-Long Xue; Li Zhu; Mian-Bin Wu; Jian-Ping Lin; Li-Rong Yang (Biotechnology Letters, 2018)

Construction and Application of a Climate Risk Index for China - Yujie Wang; Lianchun Song; Dianxiu Ye; Zhe Wang; Rong Gao; Xiucang Li; Yizhou Yin; Zunya Wang; Yaoming Liao (Journal of Meteorological Research, 2018)

The jasmonate-responsive transcription factor CbWRKY24 regulates terpenoid biosynthetic genes to promote saponin biosynthesis in Conyza blinii H. Lév. - Wen-Jun Sun; Jun-Yi Zhan; Tian-Run Zheng; Rong Sun; Tao Wang; Zi-Zhong Tang; Tong-Liang Bu; Cheng-Lei Li; Qi Wu; Hui Chen (Journal of Genetics, 2018)

Evaluating tacrolimus pharmacokinetic models in adult renal transplant recipients with different CYP3A5 genotypes - Can Hu; Wen-jun Yin; Dai-yang Li; Jun-jie Ding; Ling-yun Zhou; Jiang-lin Wang; Rong-rong Ma; Kun Liu; Ge Zhou; Xiao-cong Zuo (European Journal of Clinical Pharmacology, 2018)

Development of an Autism Subtyping Questionnaire Based on Social Behaviors - Fan-Chao Meng; Xin-Jie Xu; Tian-Jia Song; Xiao-Jing Shou; Xiao-Li Wang; Song-Ping Han; Ji-Sheng Han; Rong Zhang (Neuroscience Bulletin, 2018)

Synthesis, antitumor evaluation and molecular docking study of a novel podophyllotoxin-lonidamine hybrid - Lei Zhang; Jie Zheng; Ying Rong; Chengli Yang; Li Long; Yingshu Xu; Yongzheng Chen; Jing Wang; Qizheng Yao (Medicinal Chemistry Research, 2018)

First report of tomato yellow Leaf curl virus and cucumber mosaic virus infecting Huoxiang (Agastache rugosa) in CHINA - Rong Wang; Yong Li; Jia-Li Dong; Wan-Long Ding (Journal of Plant Pathology, 2018)

Impact of atmospheric model resolution on simulation of ENSO feedback processes: a coupled model study - Lijuan Hua; Lin Chen; Xinyao Rong; Jingzhi Su; Lu Wang; Tim Li; Yongqiang Yu (Climate Dynamics, 2018)

Soil pre-fumigation could effectively improve the disease suppressiveness of biofertilizer to banana Fusarium wilt disease by reshaping the soil microbiome - Zongzhuan Shen; Chao Xue; Paul W. J. Taylor; Yannan Ou; Beibei Wang; Yan Zhao; Yunze Ruan; Rong Li; Qirong Shen (Biology and Fertility of Soils, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Seasonal Variation and Exposure Risks of Perchlorate in Soil, Indoor Dust, and Outdoor Dust in China - Yiwen Li; Ruoying Liao; Zhiwei Gan; Bing Qu; Rong Wang; Mengqin Chen; Sanglan Ding; Shijun Su (Archives of Environmental Contamination and Toxicology, 2018)

Oral Intake of Lactobacillus helveticus NS8 Alleviates Ovalbumin-Induced Atopic Dermatitis in SKH-1 Hairless Mice - Jingjing Rong; Shuzhan Liu; Chao Hu; Feng Jin; Li Wang (Indian Journal of Microbiology, 2018)

Comparison of gene co-networks reveals the molecular mechanisms of the rice (Oryza sativa L.) response to Rhizoctonia solani AG1 IA infection - Jinfeng Zhang; Wenjuan Zhao; Rong Fu; Chenglin Fu; Lingxia Wang; Huainian Liu; Shuangcheng Li; Qiming Deng; Shiquan Wang; Jun Zhu; Yueyang Liang; Ping Li; et al. (Functional & Integrative Genomics, 2018)

Preparation and evaluation of decellularized porcine carotid arteries cross-linked by genipin: the preliminary results - Yongquan Gu; Fei Wang; Rong Wang; Jianxin Li; Cong Wang; Liqiang Li; Zeqin Xu; Jian Zhang (Cell and Tissue Banking, 2018)

Regulation of myostatin expression is associated with growth and muscle development in commercial broiler and DMC muscle - Tengfei Dou; Zhengtian Li; Kun Wang; Lixian Liu; Hua Rong; Zhiqiang Xu; Ying Huang; Dahai Gu; Xiaobo Chen; Wenyuan Hu; Jiarong Zhang; Sumei Zhao; et al. (Molecular Biology Reports, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Autophagic Modulation by Trehalose Reduces Accumulation of TDP-43 in a Cell Model of Amyotrophic Lateral Sclerosis via TFEB Activation - Ying Wang; Feng-Tao Liu; Yi-Xuan Wang; Rong-Yuan Guan; Chen Chen; Da-Ke Li; Lu-Lu Bu; Jie Song; Yu-Jie Yang; Yi Dong; Yan Chen; Jian Wang (Neurotoxicity Research, 2018)

Selection of growth-related genes and dominant genotypes in transgenic Yellow River carp Cyprinus carpio L. - Lifei Luo; Rong Huang; Aidi Zhang; Cheng Yang; Liangming Chen; Denghui Zhu; Yongming Li; Libo He; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Functional & Integrative Genomics, 2018)

Transcriptome analysis of differentially expressed genes in rabbits’ ovaries by digital gene-expression profiling - Tao Huang; Ya-dong Wang; Ming-ming Xue; Xue Feng; Cai-Xia Sun; An-si Wang; Shu-yu Xie; Meng Zhang; Gui-Rong Sun; Ming Li (Genes & Genomics, 2018)

Complete nucleotide sequence of a new carlavirus in chrysanthemums in China - Rong Wang; Jiali Dong; Zhen Wang; Tao Zhou; Yong Li; Wanlong Ding (Archives of Virology, 2018)

Atlas of the Striatum and Globus Pallidus in the Tree Shrew: Comparison with Rat and Mouse - Rong-Jun Ni; Zhao-Huan Huang; Yu-Mian Shu; Yu Wang; Tao Li; Jiang-Ning Zhou (Neuroscience Bulletin, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Selective and novel cyclin-dependent kinases 4 inhibitor: synthesis and biological evaluation - Qingxiang Guo; Yongtao Li; Chao Zhang; Zhi Huang; Xin Wang; Yongwei Nie; Yao Li; Yanhua Liu; Shengyong Yang; Rong Xiang; Yan Fan (Medicinal Chemistry Research, 2018)

De novo transcriptome analysis of an albino mutant Pasphiopedilum pacific shamrock reveals reduced expression of genes related to chloroplast biosynthesis and division - Han Li; Hua Cao; Rong-pei Yu; Zhen Miao; Ji-hua Wang; Su-Ping Qu; Qiang Yuan; Shen-chong Li (Horticulture, Environment, and Biotechnology, 2018)

Agrobacterium tumefaciens-mediated transformation system for the important medicinal plant Dendrobium catenatum Lindl - Ji Chen; Li Wang; Jianbin Chen; Jin Huang; Fan Liu; Rong Guo; Li Yang; Aby Grabon; Ke Zhao; Fanlei Kong; Chen Liu; Mengliang Tian (In Vitro Cellular & Developmental Biology - Plant, 2018)

In vitro prebiotic effects of seaweed polysaccharides - Xiaolin Chen; Yuhao Sun; Linfeng Hu; Song Liu; Huahua Yu; Rong’e Xing; Rongfeng Li; Xueqin Wang; Pengcheng Li (Journal of Oceanology and Limnology, 2018)

Effects of probiotic on microfloral structure of live feed used in larval breeding of turbot Scophthalmus maximus - Yan Jiang; Zheng Zhang; Yingeng Wang; Yayun Jing; Meijie Liao; Xiaojun Rong; Bin Li; Guiping Chen; Hesen Zhang (Journal of Oceanology and Limnology, 2018)

Effects of enhanced ultraviolet-B radiation, water deficit, and their combination on UV-absorbing compounds and osmotic adjustment substances in two different moss species - Rong Hui; Ruiming Zhao; Guang Song; Yixuan Li; Yang Zhao; Yanli Wang (Environmental Science and Pollution Research, 2018)

Genome-wide identification and expression analysis of the B-box gene family in the Apple (Malus domestica Borkh.) genome - Xin Liu; Rong Li; Yaqing Dai; Xuesen Chen; Xiaoyun Wang (Molecular Genetics and Genomics, 2018)

Linking intraspecific trait variability and spatial patterns of subtropical trees - En-Rong Yan; Liu-Li Zhou; Han Y. H. Chen; Xi-Hua Wang; Xiang-Yu Liu (Oecologia, 2018)

Supplementation with turmeric residue increased survival of the Chinese soft-shelled turtle (Pelodiscus sinensis) under high ambient temperatures - Yong Chen; Yi-fan Zhang; Hao-cheng Qian; Jing-liang Wang; Zhe Chen; Jose M. Ordovas; Chao-qiang Lai; Li-rong Shen (Journal of Zhejiang University-SCIENCE B, 2018)

Anti-oral common pathogenic bacterial active acetylenic acids from Thesium chinense Turcz - Chang Liu; Xiao-Tian Li; Rong-Rong Cheng; Zhu-Zhen Han; Li Yang; Zhong-Chen Song; Zheng-Tao Wang (Journal of Natural Medicines, 2018)

Agricultural non-point source pollution management in a reservoir watershed based on ecological network analysis of soil nitrogen cycling - Wen Xu; Yanpeng Cai; Qiangqiang Rong; Zhifeng Yang; Chunhui Li; Xuan Wang (Environmental Science and Pollution Research, 2018)

Uhrf2 deletion impairs the formation of hippocampus-dependent memory by changing the structure of the dentate gyrus - Xiao-Rong Chen; Shi-Cheng Sun; Shuai-Wen Teng; Liang Li; Yi-Fan Bie; Hui Yu; Da-Li Li; Zhe-Yu Chen; Yue Wang (Brain Structure and Function, 2018)

Continuous application of different organic additives can suppress tomato disease by inducing the healthy rhizospheric microbiota through alterations to the bulk soil microflora - Hongjun Liu; Wu Xiong; Ruifu Zhang; Xinnan Hang; Dongsheng Wang; Rong Li; Qirong Shen (Plant and Soil, 2018)

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Ionizing Radiation Blocks Hair Cell Regeneration in Zebrafish Lateral Line Neuromasts by Preventing Wnt Signaling - Rong Li; Guixiang Liao; Guo Yin; Baiyao Wang; Miaohong Yan; Xiaoshan Lin; Wenqing Zhang; Xiaohui Chen; Shasha Du; Yawei Yuan (Molecular Neurobiology, 2018)

Maternal doubled haploid production in interploidy hybridization between Brassica napus and Brassica allooctaploids - Shaohong Fu; Liqin Yin; Mingchao Xu; Yun Li; Maolin Wang; Jin Yang; Tingdong Fu; Jisheng Wang; Jinxiong Shen; Asif Ali; Qiong Zou; Bin Yi; et al. (Planta, 2018)

Arg913Gln of SLC12A3 gene promotes development and progression of end-stage renal disease in Chinese type 2 diabetes mellitus - Rong Zhang; Langen Zhuang; Ming Li; Juan zhang; Weijing Zhao; Xiaoxu Ge; Yating Chen; Feng Wang; Niansong Wang; Yuqian Bao; Limei Liu; Yanjun Liu; et al. (Molecular and Cellular Biochemistry, 2018)

β-Arrestin-1 deficiency ameliorates renal interstitial fibrosis by blocking Wnt1/β-catenin signaling in mice - Huiyan Xu; Quanxin Li; Jiang Liu; Jiaqing Zhu; Liang Li; Ziying Wang; Yan Zhang; Yu Sun; Jinpeng Sun; Rong Wang; Fan Yi (Journal of Molecular Medicine, 2018)

Concentrations and Exposure Evaluation of Metals in Diverse Food Items from Chengdu, China - Rong Wang; Bifeng Zhong; Lu Pi; Fuyu Xie; Mengqin Chen; Sanglan Ding; Shijun Su; Zhi Li; Zhiwei Gan (Archives of Environmental Contamination and Toxicology, 2018)

Phytoactinopolyspora halotolerans sp. nov., a halotolerant actinobacterium isolated from a saline soil in Xinjiang, northwest of China - Yang Ji; Wei-Xun Chunyu; En-Yuan Li; Zhang-Gui Ding; Min Yin; Yu-Rong Zhao; Yun Wang; Shu-Kun Tang (Antonie van Leeuwenhoek, 2018)

An efficient and green reaction of isatins, 3-amino-1-phenyl-2-pyrazolin-5-one (3-amine-1H-pyrazole), and β-diketone in aqueous medium - Zhansheng Wang; Hui Xu; Lirong Yan; Qingyang Li; Liangce Rong (Molecular Diversity, 2017)

Improved application of tribenuron-methyl as a chemical hybridizing agent with forchlorfenuron for rapeseed hybrid breeding - Yong-Hong Li; Dian-Rong Li; Wu-Sheng Liang; Jian-Hua Tian; Jian-Chang Li; Hao Wang; Mao-Teng Li; Xu-Peng Guo; Wen-Jie Chen; Zhen-Lan Zhang; Fei Mao; Wei-Guo Zhao (Euphytica, 2017)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

Erratum to: Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Efficacy and safety of probiotic-supplemented triple therapy for eradication of Helicobacter pylori in children: a systematic review and network meta-analysis - Jue-Rong Feng; Fan Wang; Xiao Qiu; Lynne V. McFarland; Peng-Fei Chen; Rui Zhou; Jing Liu; Qiu Zhao; Jin Li (European Journal of Clinical Pharmacology, 2017)

Optimization of the pollen-tube pathway method of plant transformation using the Yellow Cameleon 3.6 calcium sensor in Solanum lycopersicum - Rong Wang; Ruizhen Li; Tao Xu; Tianlai Li (Biologia, 2017)

Characterization of extracellular polymeric substance (EPS) fractions produced by Microcystis aeruginosa under the stress of linoleic acid sustained-release microspheres - Lixiao Ni; Danye Li; Shiyi Rong; Lili Su; Wei Zhou; Peifang Wang; Chao Wang; Shiyin Li; Kumud Acharya (Environmental Science and Pollution Research, 2017)

The levels of DNGR-1 and its ligand-bearing cells were altered after human and simian immunodeficiency virus infection - Wen-Rong Yao; Dong Li; Lei Yu; Feng-Jie Wang; Hui Xing; Gui-Bo Yang (Immunologic Research, 2017)

Molecular detection and phylogenetic analysis of viruses causing mosaic symptoms in new sugarcane varieties in China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Jiong Yin; Zhi-Ming Luo (European Journal of Plant Pathology, 2017)

Responses of soil nitrous oxide production and abundances and composition of associated microbial communities to nitrogen and water amendment - Qing Wang; Yu-Rong Liu; Cui-Jing Zhang; Li-Mei Zhang; Li-Li Han; Ju-Pei Shen; Ji-Zheng He (Biology and Fertility of Soils, 2017)

Reduced weed seed shattering by silencing a cultivated rice gene: strategic mitigation for escaped transgenes - Huanxin Yan; Lei Li; Ping Liu; Xiaoqi Jiang; Lei Wang; Jia Fang; Zhimin Lin; Feng Wang; Jun Su; Bao-Rong Lu (Transgenic Research, 2017)

Response of performance and bacterial community to oligotrophic stress in biofilm systems for raw water pretreatment - Li-juan Feng; Rong Jia; Jing-ya Sun; Jing Wang; Zheng-hui Lv; Jun Mu; Guang-feng Yang (Biodegradation, 2017)

Development of a Time-Resolved Fluorescence Immunoassay for the Diagnosis of Hepatocellular Carcinoma Based on the Detection of Glypican-3 - Juan-Juan Chen; Chun-Mei Xie; Cong-Rong Wang; Yong Wan; Zhi-Ning Dong; Ming Li; Wei-Wen Xu (Journal of Fluorescence, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

Inhalation of Roman chamomile essential oil attenuates depressive-like behaviors in Wistar Kyoto rats - Yingying Kong; Ting Wang; Rong Wang; Yichuan Ma; Shanshan Song; Juan Liu; Weiwei Hu; Shengtian Li (Science China Life Sciences, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

Three-dimensional tomography using high-power induced polarization with the similar central gradient array - Jun-Lu Wang; Pin-Rong Lin; Meng Wang; Dang Li; Jian-Hua Li (Applied Geophysics, 2017)

NaCl stress induces CsSAMs gene expression in Cucumis sativus by mediating the binding of CsGT-3b to the GT-1 element within the CsSAMs promoter - Li-Wei Wang; Mei-Wen He; Shi-Rong Guo; Min Zhong; Sheng Shu; Jin Sun (Planta, 2017)

Characterizing land displacement in complex hydrogeological and geological settings: a case study in the Beijing Plain, China - Yongyong Li; Huili Gong; Lin Zhu; Xiaojuan Li; Rong Wang; Gaoxuan Guo (Natural Hazards, 2017)

Remediation of Petroleum-contaminated Soil Using Bulrush Straw Powder, Biochar and Nutrients - Yanjie Wang; Fayun Li; Xiangmin Rong; Haixing Song; Jiabo Chen (Bulletin of Environmental Contamination and Toxicology, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Molecular Detection of Bru1 Gene and Identification of Brown Rust Resistance in Chinese Sugarcane Germplasm - Wen-Feng Li; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Jiong Yin; Zhi-Ming Luo (Sugar Tech, 2017)

Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

Bioavailability and Bioequivalence Aspects of Oral Modified-Release Drug Products - Rong Wang; Dale P. Conner; Bing V. Li (The AAPS Journal, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Cloning and expression analysis of zygote arrest 1 (Zar1) in New Zealand white rabbits - DAN WANG; SHU-YU XIE; WEI ZHANG; CAI-XIA SUN; TAO HUANG; AN-SI WANG; XUE-LEI HAN; GUI-RONG SUN; MING LI (Journal of Genetics, 2017)

Preconditioned prestack plane-wave least squares reverse time migration with singular spectrum constraint - Chuang Li; Jian-Ping Huang; Zhen-Chun Li; Rong-Rong Wang (Applied Geophysics, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Tenuigenin promotes the osteogenic differentiation of bone mesenchymal stem cells in vitro and in vivo - Hua-ji Jiang; Xing-gui Tian; Shou-bin Huang; Guo-rong Chen; Min-jun Huang; Yu-hui Chen; Bin Yan; Sheng-fa Li; Jia-jun Tang; Hui-yu Zhao; Liang Wang; Zhong-min Zhang (Cell and Tissue Research, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

GWAS-Linked Loci and Neuroimaging Measures in Alzheimer’s Disease - Jie-Qiong Li; Hui-Fu Wang; Xi-Chen Zhu; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Hepatic expression of transcription factors affecting developmental regulation of UGT1A1 in the Han Chinese population - Ya-li Nie; Hang He; Jiang-feng Li; Xiang-guang Meng; Liang Yan; Pei Wang; Shu-jie Wang; Hong-zheng Bi; Li-rong Zhang; Quan-cheng Kan (European Journal of Clinical Pharmacology, 2017)

Stability analysis of slope in strain-softening soils using local arc-length solution scheme - Xiang-rong Wang; Qi-guo Rong; Shu-li Sun; Hui Wang (Journal of Mountain Science, 2017)

Contamination, Fractionation and Biological Risk Related to Metals in Surface Sediments from the Largest Deep Freshwater Lake in China - Hua-Bing Li; Yang-Guang Gu; Rong Wang; Hui-Bin Lu (Archives of Environmental Contamination and Toxicology, 2017)

Genome-wide analysis of Gro/Tup1 family corepressors and their responses to hormones and abiotic stresses in maize - Hongyou Li; Kaifeng Huang; Hanmei Du; Hongling Wang; Xin Chen; Shibin Gao; Hailan Liu; Moju Cao; Yanli Lu; Tingzhao Rong; Suzhi Zhang (Journal of Plant Biology, 2016)

Oral administration of Schisandra chinensis extract suppresses Dnmt1 expression in Kunming mice ovaries - Feng-Rui Wu; Deng-kun Li; Mi-mi Su; Yong Liu; Biao Ding; Rong Wang; Wen-yong Li (Genes & Genomics, 2016)

Neurofibromin Regulates Seizure Attacks in the Rat Pilocarpine-Induced Model of Epilepsy - Min Ren; Kunyi Li; Dan Wang; Jiamei Guo; Jing Li; Guang Yang; Xianghua Long; Wenjing Shen; Rong Hu; Xuefeng Wang; Kebin Zeng (Molecular Neurobiology, 2016)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Syndecan-4 regulates the bFGF-induced chemotactic migration of endothelial cells - Ran Li; Han Wu; Jun Xie; Guannan Li; Rong Gu; Lina Kang; Lian Wang; Biao Xu (Journal of Molecular Histology, 2016)

Cloning and characterization of Bax1 and Bax2 genes of Ctenopharyngodon idellus and evaluation of transcript expression in response to grass carp reovirus infection - Hao Wang; Libo He; Yongyan Pei; Pengfei Chu; Rong Huang; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Fish Physiology and Biochemistry, 2016)

The influence of potassium concentration on epileptic seizures in a coupled neuronal model in the hippocampus - Mengmeng Du; Jiajia Li; Rong Wang; Ying Wu (Cognitive Neurodynamics, 2016)

A Theoretical Explanation for Rock Core Disking in Triaxial Unloading Test by Considering Local Tensile Stress - Houxu Huang; Pengxian Fan; Jie Li; Mingyang Wang; Xiaoli Rong (Acta Geophysica, 2016)

Antidepressant-like effects of standardized gypenosides: involvement of brain-derived neurotrophic factor signaling in hippocampus - Rong-Hao Mu; Xiao-Yan Fang; Shuang-Shuang Wang; Cheng-Fu Li; Shao-Mei Chen; Xue-Mei Chen; Qing Liu; Yu-Cheng Li; Li-Tao Yi (Psychopharmacology, 2016)

The Roles of Genes in the Neuronal Migration and Neurite Outgrowth Network in Developmental Dyslexia: Single- and Multiple-Risk Genetic Variants - Shanshan Shao; Rui Kong; Li Zou; Rong Zhong; Jiao Lou; Jie Zhou; Shengnan Guo; Jia Wang; Xiaohui Zhang; Jiajia Zhang; Ranran Song (Molecular Neurobiology, 2016)

CGRP 8-37 enhances lipopolysaccharide-induced acute lung injury and regulating aquaporin 1 and 5 expressions in rats - Fu Hong-min; Huangfu Chun-rong; Zheng Rui; Su Li-na; Wang Ya-jun; Li Li (Journal of Physiology and Biochemistry, 2016)

A preliminary study on the potential value of a novel integrated aquaculture system on water purification - Li-hong Chen; Rong-lian Xing; Ai-li Jiang; Li Teng; Chang-hai Wang (Aquaculture International, 2016)

The association between the ring finger protein 213 (RNF213) polymorphisms and moyamoya disease susceptibility: a meta-analysis based on case–control studies - Xun-Sha Sun; Jun Wen; Jiao-Xing Li; Rong Lai; Yu-Fang Wang; Hui-Jiao Liu; Wen-Li Sheng (Molecular Genetics and Genomics, 2016)

5-HT7 Receptors Are Not Involved in Neuropeptide Release in Primary Cultured Rat Trigeminal Ganglion Neurons - Xiaojuan Wang; Rong Hu; Jianbo Liang; Ze Li; Weiwen Sun; Xiaoping Pan (Journal of Molecular Neuroscience, 2016)

Heat shock protein 70 inhibits cardiomyocyte necroptosis through repressing autophagy in myocardial ischemia/reperfusion injury - Xiaojuan Liu; Chao Zhang; Chi Zhang; Jingjing Li; Wanwan Guo; Daliang Yan; Chen Yang; Jianhua Zhao; Tian Xia; Yuqing Wang; Rong Xu; Xiang Wu; et al. (In Vitro Cellular & Developmental Biology - Animal, 2016)

The strong El Niño of 2015/16 and its dominant impacts on global and China's climate - Panmao Zhai; Rong Yu; Yanjun Guo; Qingxiang Li; Xuejuan Ren; Yaqiang Wang; Wenhui Xu; Yanju Liu; Yihui Ding (Journal of Meteorological Research, 2016)

Characterization of the life cycle of the tick Haemaphysalis tibetensis under field conditions in Qinghai-Tibet plateau - Ming Liu; Tuo Li; Zhi-Jun Yu; Xiao-He Gao; Chun-Wei Zuo; Rong-Rong Wang; Ning-Xin Li; Hui Wang; Jing-Ze Liu (Experimental and Applied Acarology, 2016)

Effects of light intensity on leaf photosynthetic characteristics, chloroplast structure, and alkaloid content of Mahonia bodinieri (Gagnep.) Laferr. - De-Xin Kong; Yan-Qun Li; Man-Lian Wang; Mei Bai; Rong Zou; Hui Tang; Hong Wu (Acta Physiologiae Plantarum, 2016)

A highly efficient grapevine mesophyll protoplast system for transient gene expression and the study of disease resistance proteins - Feng-Li Zhao; Ya-Juan Li; Yang Hu; Yu-Rong Gao; Xue-Wen Zang; Qin Ding; Yue-Jin Wang; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

MicroRNA-764-3p regulates 17β-estradiol synthesis of mouse ovarian granulosa cells by targeting steroidogenic factor-1 - Lianlian Wang; Cong Li; Rong Li; Youlin Deng; Yixin Tan; Chao Tong; Hongbo Qi (In Vitro Cellular & Developmental Biology - Animal, 2016)

Estimation of soil reinforcement by the roots of four post-dam prevailing grass species in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Xiu-bin He; Yu-hai Bao; Qiang Tang; Jin-zhang Gao; Dan-dan Yan; Ming-feng Wang; Yu Li (Journal of Mountain Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Large-scale comparative phosphoprotein analysis of maize seedling leaves during greening - De-Li Ning; Ke-Hui Liu; Chang-Cai Liu; Jin-Wen Liu; Chun-Rong Qian; Yang Yu; Yue-Feng Wang; Ying-Chun Wang; Bai-Chen Wang (Planta, 2016)

Combination of Estrogen and Immunosuppressive Agents to Establish a Mouse Model of Candidiasis with Concurrent Oral and Vaginal Mucosal Infection - Le Wang; Chong Wang; Huan Mei; Yongnian Shen; Guixia Lv; Rong Zeng; Ping Zhan; Dongmei Li; Weida Liu (Mycopathologia, 2016)

Anthropogenic footprint of climate change in the June 2013 northern India flood - Changrae Cho; Rong Li; S.-Y. Wang; Jin-Ho Yoon; Robert R. Gillies (Climate Dynamics, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

Rapid Identification of Methicillin-Resistant Staphylococcus aureus (MRSA) by the Vitek MS Saramis system - Weiguang Shan; Jiaping Li; Ying Fang; Xuan Wang; Danxia Gu; Rong Zhang (Current Microbiology, 2016)

A Time-Dependent Drought Index for Non-Stationary Precipitation Series - Yixuan Wang; Jianzhu Li; Ping Feng; Rong Hu (Water Resources Management, 2015)

Age-related changes in photosynthesis and water relations of revegetated Caragana korshinskii in the Tengger desert, Northern China - Jing-Ting Bao; Jin Wang; Xin-Rong Li; Zhi-Shan Zhang; Jie-Qiong Su (Trees, 2015)

Induction of follicular luteinization by equine chorionic gonadotropin in cyclic guinea pigs - Jun-rong Li; Wei Wang; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2015)

EGCG induces G-CSF expression and neutrophilia in experimental sepsis - Wei Li; Andrew H. Wu; Shu Zhu; Jianhua Li; Rong Wu; John D’Angelo; Haichao Wang (Immunologic Research, 2015)

Cloning of the A Mating-Type Locus from Lepista nuda and Characterization of Its Genetic Structure - Chengbo Rong; Shuang Zhao; Dengjin Li; Lijuan Wang; Shouxian Wang; Kang Ma; Feng Xu; Yu Liu (Current Microbiology, 2015)

The inward-rectifying K+ channel SsAKT1 is a candidate involved in K+ uptake in the halophyte Suaeda salsa under saline condition - Hui-Rong Duan; Qing Ma; Jin-Lin Zhang; Jing Hu; Ai-Ke Bao; Li Wei; Qian Wang; Sheng Luan; Suo-Min Wang (Plant and Soil, 2015)

Retraction Note to: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2015)

Angiotensin II increases secreted frizzled-related protein 5 (sFRP5) expression through AT1 receptor/Rho/ROCK1/JNK signaling in cardiomyocytes - Xin Jin; Bingyan Guo; Jie Yan; Rong Yang; Liang Chang; Yaling Wang; Chenglong Miao; Suyun Liu; Hui Zhang; Yongjun Li (Molecular and Cellular Biochemistry, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

ATF6 pathway of unfolded protein response mediates advanced oxidation protein product-induced hypertrophy and epithelial-to-mesenchymal transition in HK-2 cells - Xun Tang; Xiujie Liang; Minhui Li; Tingting Guo; Na Duan; Yue Wang; Guang Rong; Lei Yang; Shaojie Zhang; Jun Zhang (Molecular and Cellular Biochemistry, 2015)

Effects of glucose, insulin and triiodothyroxine on leptin and leptin receptor expression and the effects of leptin on activities of enzymes related to glucose metabolism in grass carp (Ctenopharyngodon idella) hepatocytes - Rong-Hua Lu; Yi Zhou; Xiao-Chen Yuan; Xu-Fang Liang; Liu Fang; Xiao-Li Bai; Min Wang; Yu-Hua Zhao (Fish Physiology and Biochemistry, 2015)

Long-term nickel exposure altered the bacterial community composition but not diversity in two contrasting agricultural soils - Jing Li; Hang-Wei Hu; Yi-Bing Ma; Jun-Tao Wang; Yu-Rong Liu; Ji-Zheng He (Environmental Science and Pollution Research, 2015)

Spiculisporic acid analogues of the marine-derived fungus, Aspergillus candidus strain HDf2, and their antibacterial activity - Rong Wang; Zhi Kai Guo; Xiang Min Li; Fu Xiao Chen; Xia Fei Zhan; Ming Hui Shen (Antonie van Leeuwenhoek, 2015)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

The role of Cyclin G1 in cellular proliferation and apoptosis of human epithelial ovarian cancer - Lifei Jiang; Rong Liu; Yingying Wang; Chunmiao Li; Qinghua Xi; Jianxin Zhong; Jian Liu; Shuyun Yang; Juan Wang; Menghui Huang; Chunhui Tang; Zheng Fang (Journal of Molecular Histology, 2015)

Flavobacterium shanxiense sp. nov., Isolated from Soil - Fan Yang; Hong-ming Liu; Rong Zhang; Ding-bin Chen; Xiang Wang; Xin Yan; Qing Hong; Shun-peng Li (Current Microbiology, 2015)

Study on the Mechanisms of Cartilage Tissue Damage Caused by Hydrogen Peroxide - Xiao Ouyang; Bo Wei; Shi Dong Hong; Jing Rong Wang; Feng Xin; Lin Wang; Xiao Wei Yang; Li Ming Wang (Cell Biochemistry and Biophysics, 2015)

Dissipation and Degradation Dynamics of Thifluzamide in Rice Field - Li Na Wei; Ping Wu; Fu Rong Wang; Hong Yang (Water, Air, & Soil Pollution, 2015)

Novel Interactive Partners of Neuroligin 3: New Aspects for Pathogenesis of Autism - Chen Shen; Li-rong Huo; Xin-liang Zhao; Pei-rong Wang; Nanbert Zhong (Journal of Molecular Neuroscience, 2015)

GmPGIP3 enhanced resistance to both take-all and common root rot diseases in transgenic wheat - Aiyun Wang; Xuening Wei; Wei Rong; Liang Dang; Li-Pu Du; Lin Qi; Hui-Jun Xu; Yanjun Shao; Zengyan Zhang (Functional & Integrative Genomics, 2015)

Determination of tumorigenic Agrobacterium density in soil by real-time PCR assay and its effect on crown gall disease severity - Qian Li; Rong-Jun Guo; Shi-Dong Li; Shi-Fang Li; Hong-Qing Wang (European Journal of Plant Pathology, 2015)

Predicting hybrid fertility from maker-based genetic divergence index of parental varieties: implications for utilizing inter-subspecies heterosis in hybrid rice breeding - Ping Liu; Zhiwu Dan; Zhe Wang; Shaoqing Li; Nengwu Li; Huanxin Yan; Xingxing Cai; Bao-Rong Lu (Euphytica, 2015)

Effects on Pharmacokinetics of Propranolol and Other Factors in Rats After Acute Exposure to High Altitude at 4,010 m - Li Wenbin; Wang Rong; Xie Hua; Zhang Juanhong; Wu Xiaoyu; Jia Zhengping (Cell Biochemistry and Biophysics, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

Evaluation of pedotransfer functions for estimating saturated hydraulic conductivity in coastal salt-affected mud farmland - Rong-Jiang Yao; Jing-Song Yang; Dan-Hua Wu; Fu-Rong Li; Peng Gao; Xiang-Ping Wang (Journal of Soils and Sediments, 2015)

Identification of Sugarcane White Leaf Phytoplasma in Fields and Quaratine Sugarcane Samples in Yunnan Province, China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Zhi-Ming Luo; Jiong Yin; Ke Shen (Sugar Tech, 2015)

Protective effects of hydroxysafflor yellow A (HSYA) on alcohol-induced liver injury in rats - Yanhao He; Qiang Liu; Yanxiang Li; Xiaofeng Yang; Weirong Wang; Tingting Li; Wei Zhang; Yuexin Cui; Chaoyun Wang; Rong Lin (Journal of Physiology and Biochemistry, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

The Effect of Continuous Blood Purification on the Prognosis of Cardiorenal Syndrome Patients - Fengyu Jia; Peng Rong; Dandan Li; Suxia Wang; Ying Jing; Yanming Ge; Jianzhong Meng (Cell Biochemistry and Biophysics, 2015)

Optimized Preparation of a 99mTc-Radiolabeled Probe for Tracing MicroRNA - Lei Kang; Xiao-jie Xu; Chao Ma; Rong-fu Wang; Ping Yan; Chun-li Zhang; Hong-wei Sun; Ding Li (Cell Biochemistry and Biophysics, 2015)

Determination of royal jelly freshness by ELISA with a highly specific anti-apalbumin 1, major royal jelly protein 1 antibody - Li-rong Shen; Yi-ran Wang; Liang Zhai; Wen-xiu Zhou; Liang-liang Tan; Mei-lu Li; Dan-dan Liu; Fa Xiao (Journal of Zhejiang University-SCIENCE B, 2015)

The anti-angiogenic role of discoidin domain receptor 2 (DDR2) in laser-induced choroidal neovascularization - Tong Zhu; Jie Zhu; Xin Bu; Hu Zhao; Shuya Zhang; Yuan Chang; Rong Li; Libo Yao; Yusheng Wang; Jin Su (Journal of Molecular Medicine, 2015)

Determination of selected pharmaceuticals in tap water and drinking water treatment plant by high-performance liquid chromatography-triple quadrupole mass spectrometer in Beijing, China - Mei-Quan Cai; Rong Wang; Li Feng; Li-Qiu Zhang (Environmental Science and Pollution Research, 2015)

Effect of anthracene on the interaction between Platymonas helgolandica var. tsingtaoensis and Heterosigma akashiwo in laboratory cultures - Rong Bi; You Wang; Renjun Wang; Wei Li; Xuexi Tang (Journal of Ocean University of China, 2015)

Relationships between heavy metal concentrations in soils and reclamation history in the reclaimed coastal area of Chongming Dongtan of the Yangtze River Estuary, China - Chao Ma; Rong Zheng; Jiale Zhao; Xiumei Han; Li Wang; Xiaojiang Gao; Chaosheng Zhang (Journal of Soils and Sediments, 2015)

Signals induced by exogenous nitric oxide and their role in controlling brown rot disease caused by Monilinia fructicola in postharvest peach fruit - Jing Ying Shi; Na Liu; Rong Xin Gu; Li Qin Zhu; Chang Zhang; Qing Guo Wang; Zhong Hua Lei; Yun Yun Liu; Ji Yun Ren (Journal of General Plant Pathology, 2015)

Humanin attenuates Alzheimer-like cognitive deficits and pathological changes induced by amyloid β-peptide in rats - Gao-Shang Chai; Dong-Xiao Duan; Rong-Hong Ma; Jian-Ying Shen; Hong-Lian Li; Zhi-Wei Ma; Yu Luo; Lu Wang; Xin-Hua Qi; Qun Wang; Jian-Zhi Wang; Zelan Wei; et al. (Neuroscience Bulletin, 2014)

Analysis of DNA methylation of perennial ryegrass under drought using the methylation-sensitive amplification polymorphism (MSAP) technique - Xiao-Mei Tang; Xiang Tao; Yan Wang; Dong-Wei Ma; Dan Li; Hong Yang; Xin-Rong Ma (Molecular Genetics and Genomics, 2014)

Efficient Knockout of Transplanted Green Fluorescent Protein Gene in Medaka Using TALENs - Chao Qiu; Bin Cheng; Yunsheng Zhang; Rong Huang; Lanjie Liao; Yongming Li; Daji Luo; Wei Hu; Yaping Wang (Marine Biotechnology, 2014)

Increased prevalence of hepatitis C virus subtype 6a in China: a comparison between 2004–2007 and 2008–2011 - Xia Rong; Ru Xu; Huaping Xiong; Min Wang; Ke Huang; Qiuyu Chen; Chengyao Li; Qiao Liao; Jieting Huang; Wenjie Xia; Guangping Luo; Xin Ye; et al. (Archives of Virology, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Effect of two-linked mutations of the FMO3 gene on itopride metabolism in Chinese healthy volunteers - Li-Ping Zhou; Zhi-Rong Tan; Hao Chen; Dong Guo; Yao Chen; Wei-Hua Huang; Lian-Sheng Wang; Guo-Gang Zhang (European Journal of Clinical Pharmacology, 2014)

Exogenous hydrogen peroxide enhanced the thermotolerance of Festuca arundinacea and Lolium perenne by increasing the antioxidative capacity - Yan Wang; Jie Zhang; Jian-Long Li; Xin-Rong Ma (Acta Physiologiae Plantarum, 2014)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

Applying support vector regression analysis on grip force level-related corticomuscular coherence - Yao Rong; Xixuan Han; Dongmei Hao; Liu Cao; Qing Wang; Mingai Li; Lijuan Duan; Yanjun Zeng (Journal of Computational Neuroscience, 2014)

Identification of five sea cucumber species through PCR-RFLP analysis - Yingchun Lv; Rong Zheng; Tao Zuo; Yuming Wang; Zhaojie Li; Yong Xue; Changhu Xue; Qingjuan Tang (Journal of Ocean University of China, 2014)

Erratum to: Enhancing the Antitumor Activity of Berberine Hydrochloride by Solid Lipid Nanoparticle Encapsulation - Lu Wang; Hongtao Li; Shengpeng Wang; Rong Liu; Zhisheng Wu; Chunming Wang; Yitao Wang; Meiwan Chen (AAPS PharmSciTech, 2014)

Studies on the analgesic activities of Jia-Yuan-Qing pill and its safety evaluation in mice - Ye Tian; Li-rong Teng; Jing-jing Song; Qing-fan Meng; Jia-hui Lu; Wei-wei Zhang; Kang Wei; Ning Wang; Di Wang; Le-sheng Teng (Protoplasma, 2014)

Anti-apoptosis effect of polysaccharide isolated from the seeds of Cuscuta chinensis Lam on cardiomyocytes in aging rats - Shou-Li Sun; Li Guo; Ya-Chao Ren; Bing Wang; Rong-Hui Li; Yu-Shan Qi; Hui Yu; Nai-Dan Chang; Ming-Hui Li; Hai-Sheng Peng (Molecular Biology Reports, 2014)

The expression and functional role of a FOXC1 related mRNA-lncRNA pair in oral squamous cell carcinoma - Xiang-pan Kong; Jie Yao; Wei Luo; Fu-kui Feng; Jun-tao Ma; Yi-peng Ren; De-li Wang; Rong-fa Bu (Molecular and Cellular Biochemistry, 2014)

Effects of Icotinib on Advanced Non-Small Cell Lung Cancer with Different EGFR Phenotypes - Huiyun Pan; Rong Liu; Shengjie Li; Hui Fang; Ziwei Wang; Sheng Huang; Jianying Zhou (Cell Biochemistry and Biophysics, 2014)

The checkpoint 1 kinase inhibitor LY2603618 induces cell cycle arrest, DNA damage response and autophagy in cancer cells - Feng-Ze Wang; Hong-rong Fei; Ying-Jie Cui; Ying-Kun Sun; Zhao-Mei Li; Xue-Ying Wang; Xiao-Yi Yang; Ji-Guo Zhang; Bao-Liang Sun (Apoptosis, 2014)

The Application of Laser Microdissection in Molecular Detection and Identification of Aspergillus fumigatus from Murine Model of Acute Invasive Pulmonary Aspergillosis - Chong Wang; Ping Zhan; Le Wang; Rong Zeng; Yongnian Shen; Guixia Lv; Dongmei Li; Shuwen Deng; Weida Liu (Mycopathologia, 2014)

Enhancing the Antitumor Activity of Berberine Hydrochloride by Solid Lipid Nanoparticle Encapsulation - Lu Wang; Hongtao Li; Shengpeng Wang; Rong Liu; Zhisheng Wu; Chunming Wang; Yitao Wang; Meiwan Chen (AAPS PharmSciTech, 2014)

Estimate of NOX production in the lightning channel based on three-dimensional lightning locating system - Rong Zhang; GuangShu Zhang; YaJun Li; YanHui Wang; Bin Wu; Hai Yu; YanXiu Liu (Science China Earth Sciences, 2014)

Changes in the transcriptomic profiles of maize roots in response to iron-deficiency stress - Yan Li; Nian Wang; Fengtao Zhao; Xuejiao Song; Zhaohua Yin; Rong Huang; Chunqing Zhang (Plant Molecular Biology, 2014)

RETRACTED ARTICLE: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2014)

Effect of NeuroD Gene Silencing on the Migration and Invasion of Human Pancreatic Cancer Cells PANC-1 - Yang Wang; Dong Wei Su; Li Gao; Gui Ling Ding; Can Rong Ni; Ming Hua Zhu (Cell Biochemistry and Biophysics, 2014)

Vanillin derivatives as the selective small molecule inhibitors of FtsZ - Juan Sun; Ming-Hui Li; Xin-Yi Wang; Yang Zhang; Rong-Ju Yuan; Han-Yu Liu; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

Interval Q inversion based on zero-offset VSP data and applications - Gu-Lan Zhang; Xi-Ming Wang; Zhen-Hua He; Jun-Xing Cao; Ke-En Li; Jiao-Jun Rong (Applied Geophysics, 2014)

A systematic proteomic analysis of NaCl-stressed germinating maize seeds - Ling-Bo Meng; Yi-Bo Chen; Tian-Cong Lu; Yue-Feng Wang; Chun-Rong Qian; Yang Yu; Xuan-Liang Ge; Xiao-Hui Li; Bai-Chen Wang (Molecular Biology Reports, 2014)

Structural modification of an EGFR inhibitor that showed weak off-target activity against RET leading to the discovery of a potent RET inhibitor - Qi-Zheng Sun; Yong Xu; Jing-Jing Liu; Chun-Hui Zhang; Ze-Rong Wang; Ren-Lin Zheng; Wen-Jing Wang; Lin-Li Li; Sheng-Yong Yang (Molecular Diversity, 2014)

Characterization of masson pine (Pinus massoniana Lamb.) microsatellite DNA by 454 genome shotgun sequencing - Tian-Dao Bai; Li-An Xu; Meng Xu; Zhang-Rong Wang (Tree Genetics & Genomes, 2014)

Electrosprayed Microparticles with Loaded pDNA-Calcium Phosphate Nanoparticles to Promote the Regeneration of Mature Blood Vessels - Xueqin Guo; Tian Xia; Huan Wang; Fang Chen; Rong Cheng; Xiaoming Luo; Xiaohong Li (Pharmaceutical Research, 2014)

Overexpression of S100P promotes colorectal cancer metastasis and decreases chemosensitivity to 5-FU in vitro - Lei Dong; Fule Wang; Xiaona Yin; Ling Chen; Gang Li; Feiyan Lin; Wuhua Ni; Jianbo Wu; Rong Jin; Lei Jiang (Molecular and Cellular Biochemistry, 2014)

Dynamic QTL and epistasis analysis on seedling root traits in upland cotton - QINGZHI LIANG; PENGBO LI; CHENG HU; HUA HUA; ZHAOHU LI; YIHUA RONG; KUNBO WANG; JINPING HUA (Journal of Genetics, 2014)

Endothelial Insulin-Like Growth Factor-1 Modulates Proliferation and Phenotype of Smooth Muscle Cells Induced by Low Shear Stress - Lu Wang; Yue Han; Yan Shen; Zhi-Qiang Yan; Ping Zhang; Qing-Ping Yao; Bao-Rong Shen; Li-Zhi Gao; Ying-Xin Qi; Zong-Lai Jiang (Annals of Biomedical Engineering, 2014)

C and N stable isotope analysis of human and animal bones at the Beiqian site - Fen Wang; YanBo Song; BaoShuo Li; Rong Fan; GuiYun Jin; ShiLing Yuan (Science China Earth Sciences, 2014)

Functional analysis on immune deficiency (IMD) homolog gene in Chinese shrimp Fenneropenaeus chinensis - Ningning Feng; Dongdong Wang; Rong Wen; Fuhua Li (Molecular Biology Reports, 2014)

Isolation an Aldehyde Dehydrogenase Gene from Metagenomics Based on Semi-nest Touch-Down PCR - Rong Chen; Chenglu Li; Xiaolin Pei; Qiuyan Wang; Xiaopu Yin; Tian Xie (Indian Journal of Microbiology, 2014)

Characterization of land subsidence induced by groundwater withdrawals in the plain of Beijing city, China - Youquan Zhang; Huili Gong; Zhaoqin Gu; Rong Wang; Xiaojuan Li; Wenji Zhao (Hydrogeology Journal, 2014)

Combined effects of lanthanum(III) and elevated ultraviolet-B radiation on root growth and ion absorption in soybean seedlings - Guang Rong Huang; Li Hong Wang; Qing Zhou (Environmental Science and Pollution Research, 2014)

An improved embryo-rescue protocol for hybrid progeny from seedless Vitis vinifera grapes × wild Chinese Vitis species - Gui Rong Li; Wei Ji; Gang Wang; Jian Xia Zhang; Yue Jin Wang (In Vitro Cellular & Developmental Biology - Plant, 2014)

Cloning and characterization of squalene synthase gene from Poria cocos and its up-regulation by methyl jasmonate - Jian-Rong Wang; Jun-Fang Lin; Li-Qiong Guo; Lin-Feng You; Xian-Lu Zeng; Jia-Ming Wen (World Journal of Microbiology and Biotechnology, 2014)

The Leu72Met polymorphism of the GHRL gene prevents the development of diabetic nephropathy in Chinese patients with type 2 diabetes mellitus - Langen Zhuang; Ming Li; Changhua Yu; Can Li; Mingming Zhao; Ming Lu; Taishan Zheng; Rong Zhang; Weijing Zhao; Yuqian Bao; Kunsan Xiang; Weiping Jia; et al. (Molecular and Cellular Biochemistry, 2014)

Co-expression of the Arabidopsis SOS genes enhances salt tolerance in transgenic tall fescue (Festuca arundinacea Schreb.) - Dong-Mei Ma; Wei-Rong Xu; Hui-Wen Li; Feng-Xia Jin; Ling-Na Guo; Jing Wang; Hong-Jun Dai; Xing Xu (Protoplasma, 2014)

Silencing Pax3 by shRNA inhibits the proliferation and differentiation of duck (Anas platyrhynchos) myoblasts - Rong-Ping Zhang; He-He Liu; Hao-Han Wang; Yan Wang; Chun-Chun Han; Liang Li; Hua He; Heng-Yong Xu; Feng Xu; Ji-Wen Wang (Molecular and Cellular Biochemistry, 2014)

Lithium Chloride Alleviates Neurodegeneration Partly by Inhibiting Activity of GSK3β in a SCA3 Drosophila Model - Dan-Dan Jia; Li Zhang; Zhao Chen; Chun-Rong Wang; Feng-Zhen Huang; Ran-Hui Duan; Kun Xia; Bei-Sha Tang; Hong Jiang (The Cerebellum, 2013)

Cerebral vasculopathy in a Chinese family with neurofibromatosis type I mutation - Jian-Tao Liang; Li-Rong Huo; Yu-Hai Bao; Zhen-Yu Wang; Feng Ling (Neuroscience Bulletin, 2013)

Determination of Concentration of Methotrexate Enantiomers in Intracellular and Extracellular Fluids of HepG2 Cells by Liquid Chromatography–Tandem Mass Spectrometry - Rong Wang; Lifang Guo; Hua Xie; Juanhong Zhang; Xiaoyun Li; Wenbing Li; Jianfeng Wang; Xiaoyu Wu; Zhengping Jia (Cell Biochemistry and Biophysics, 2013)

Effects of Recombinant Human AMH on SCF Expression in Human Granulosa Cells - Rong Hu; Yan Lou; Fei-Miao Wang; Hui-Ming Ma; Xing Wu; Xiao-Mei Zhang; Juan Li; Ying-Pu Sun (Cell Biochemistry and Biophysics, 2013)

A Highly Selective Turn-On Fluorescent Chemosensor for Zinc Ion in Aqueous Media - Zeng-chen Liu; Zheng-yin Yang; Yan-xia Li; Bao-dui Wang; Yong Li; Tian-rong Li; Yong-jie Ding (Journal of Fluorescence, 2013)

Identification and characterization of Pestalotiopsis spp. causing twig blight disease of bayberry (Myrica rubra Sieb. & Zucc) in China - Hai-Ying Ren; Gang Li; Xing-Jiang Qi; Li Fang; Han-Rong Wang; Ji-Guang Wei; Shaobin Zhong (European Journal of Plant Pathology, 2013)

Discovery of a novel esterase subfamily sharing an identified arm sequence (ArmEst) by gene-specific metagenomic PCR - Ao Zhang; Rong Zhao; Peng Jin; Lifang Ma; Xiaolong Xiong; Tian Xie; Xiaolin Pei; Li Yu; Xiaopu Yin; Qiuyan Wang (Biotechnology Letters, 2013)

A chloroplast membrane protein LTO1/AtVKOR involving in redox regulation and ROS homeostasis - Ying Lu; Hua-Rong Wang; Han Li; Hao-Ran Cui; Yue-Guang Feng; Xiao-Yun Wang (Plant Cell Reports, 2013)

Addition of Co2+ to culture medium decides the functional expression of a recombinant nitrile hydratase in Escherichia coli - Xiaolin Pei; Qiuyan Wang; Chenglu Li; Xiaopu Yin; Rong Chen; Tian Xie (Biotechnology Letters, 2013)

Screening of high α-arbutin producing strains and production of α-arbutin by fermentation - Chun-Qiao Liu; Li Deng; Peng Zhang; Shu-Rong Zhang; Luo Liu; Tao Xu; Fang Wang; Tian-Wei Tan (World Journal of Microbiology and Biotechnology, 2013)

Identification of miR-221 and -222 as important regulators in genotype IV swine hepatitis E virus ORF3-expressing HEK 293 cells - Ying Cheng; Li Du; Qiaoyun Shi; Hanwei Jiao; Xiaoru Zhang; Yongchang Hao; Hui Rong; Jianing Zhang; Xiaoxiao Jia; Shiyu Guo; Wenhua Kuang; Hui Zhang; et al. (Virus Genes, 2013)

Engineering geological assessment for route selection of railway line in geologically active area: A case study in China - Run-qiu Huang; Yan-rong Li; Ke Qu; Ke Wang (Journal of Mountain Science, 2013)
The Cheng-Lan railway links Chengdu, a central city in Southwestern China, and Lanzhou, a central city in Northwestern China. The railway passes through the Longmenshan fault zone (Wenchuan earthquake happened there on May 12, 2008), Minjiang fault zone, and Dongkunlun fault zone, which are all active. It runs over the Yangtze River and the Yellow River, and crosses high mountains and deep valleys. There exists, along the railway’s alignment, different kinds of strata of hard granite and soft, weak metamorphic rocks such as carbonaceous slate, schist, and phyllite. It is, therefore, a key issue for such an infrastructure construction to assess the engineering geological conditions and risks, so as to mitigate or avoid possible georisks and to offer optional designs. Geological survey and georisk assessment along the railway corridor are carried out. Special attention is given to active faults, earthquakes and seismic zones. Based on these, discussions about geological aspects for route selection of the railway are conducted and countermeasures for georisk control are proposed accordingly. Main conclusions are achieved as follows: (1) Geohazards such as landslides, rockfalls and debries flows dominate both the route selection of the railway and the engineering structures (e.g., tunnels or bridges) adopted; (2) Tunnel has been proved to be an excellent structure for linear engineering in geologically active area; and (3) In the case where avoiding is impractical, necessary protection measures should be taken to engineering slopes in high earthquake intensity areas, especially the area with earthquake of Ms. 8 or greater.

Halomonas socia sp. nov., isolated from high salt culture of Dunaliella salina - Jiao Cao; Huai-Yuan Ma; Hai-Yu Li; Kui-Rong Wang; Kun Ruan; Lin-Han Bai (Extremophiles, 2013)

Physical characteristics of Chinese Hakka - LianBin Zheng; YongLan Li; ShunHua Lu; JinPing Bao; Yang Wang; XiaoRui Zhang; Hong Xue; WenGuo Rong (Science China Life Sciences, 2013)

Inhibition of formyl peptide-stimulated phospholipase D activation by Fal-002-2 via blockade of the Arf6, RhoA and protein kinase C signaling pathways in rat neutrophils - Ya-Ru Tsai; Li-Jiau Huang; Hui-Yi Lin; Yun-Jie Hung; Miau-Rong Lee; Sheng-Chu Kuo; Mei-Feng Hsu; Jih-Pyang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Exome Sequencing Identified NRG3 as a Novel Susceptible Gene of Hirschsprung’s Disease in a Chinese Population - Jun Yang; Shengyu Duan; Rong Zhong; Jieyun Yin; Jiarui Pu; Juntao Ke; Xuzai Lu; Li Zou; Hongmei Zhang; Zhidong Zhu; Depeng Wang; Huasheng Xiao; et al. (Molecular Neurobiology, 2013)

Prostaglandin E2 receptor EP1 phosphorylate CREB and mediates MMP2 expression in human cholangiocarcinoma cells - Bo Sun; Rong Rong; Hai Jiang; Hai Zhang; YiPin Wang; Xiaoming Bai; Min Zhang; Juan Ma; Shukai Xia; Wei Shu; Li Zhang; Jing Leng (Molecular and Cellular Biochemistry, 2013)

Musca Domestica Larva Lectin Induces Apoptosis in BEL-7402 Cells Through a Ca2+/JNK-mediated Mitochondrial Pathway - Chun-Ling Wang; Yan Xia; Jian-Zeng Nie; Minghui Zhou; Rong-Ping Zhang; Li-Li Niu; Li-Hua Hou; Xiao-Hong Cao (Cell Biochemistry and Biophysics, 2013)

Expression of yeast acyl-CoA-∆9 desaturase leads to accumulation of unusual monounsaturated fatty acids in soybean seeds - Jin-Ai Xue; Xue Mao; Zhi-Rong Yang; Yong-Mei Wu; Xiao-Yun Jia; Li Zhang; Ai-Qin Yue; Ji-Ping Wang; Run-Zhi Li (Biotechnology Letters, 2013)

SIRT1 inhibits TNF-α-induced apoptosis of vascular adventitial fibroblasts partly through the deacetylation of FoxO1 - Weirong Wang; Chunfang Yan; Jiye Zhang; Rong Lin; Qinqin Lin; Lina Yang; Feng Ren; Jianfeng Zhang; Meixi Ji; Yanxiang Li (Apoptosis, 2013)

Persistence and intergenerational transmission of differentially expressed genes in the testes of intracytoplasmic sperm injection conceived mice - Li-ya Wang; Ning Wang; Fang Le; Lei Li; Le-jun Li; Xiao-zhen Liu; Ying-ming Zheng; Hang-ying Lou; Xiang-rong Xu; Xiao-ming Zhu; Yi-min Zhu; He-feng Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Effects of novel bioorganic fertilizer produced by Bacillus amyloliquefaciens W19 on antagonism of Fusarium wilt of banana - Beibei Wang; Jun Yuan; Jian Zhang; Zongzhuan Shen; Maoxing Zhang; Rong Li; Yunze Ruan; Qirong Shen (Biology and Fertility of Soils, 2013)

Cutaneous and Mucosal Phaeohyphomycosis Caused by Exophiala spinifera in a Pregnant Patient: Case Report and Literature Review - Le Wang; Xiaodong She; Guixia Lv; Yongnian Shen; Qing Cai; Rong Zeng; Caixia Li; Yiping Ge; Shuwen Deng; G. S. de Hoog; Min Li; Weida Liu (Mycopathologia, 2013)

Enhancing production of a 24-membered ring macrolide compound by a marine bacterium using response surface methodology - Hua Chen; Mian-bin Wu; Zheng-jie Chen; Ming-lu Wang; Jian-ping Lin; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Lipopolysaccharide-induced failure of the gut barrier is site-specific and inhibitable by growth hormone - Chao Yue; Wei Wang; Wei-Liang Tian; Qian Huang; Ri-Sheng Zhao; Yun-Zhao Zhao; Qiu-Rong Li; Jie-Shou Li (Inflammation Research, 2013)

Lyssavirus surveillance in bats of southern China’s Guangxi Province - Zhuan-Ling Lu; Wen Wang; Wei-Li Yin; Hai-Bo Tang; Yan Pan; Xiang Liang; Qi Liu; Yi Xiong; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Triterpenoid saponins from the root of Anemone tomentosa - Yi Wang; Wei Kang; Liang-jian Hong; Wen-li Hai; Xiao-yang Wang; Hai-feng Tang; Xiang-rong Tian (Journal of Natural Medicines, 2013)

The Diagnostic Value of Treadmill Exercise Test Parameters for Coronary Artery Disease - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2013)

Characterization of a Novel Pollen-Specific Promoter from Wheat (Triticum Aestivum L.) - Ling Chen; Yingjie Miao; Cheng Wang; Peipei Su; Tianheng Li; Rong Wang; Xinglong Hao; Guangxiao Yang; Guangyuan He; Chunbao Gao (Plant Molecular Biology Reporter, 2012)

Methods to measure and analyze ciliary beat activity: Ca2+ influx-mediated cilia mechanosensitivity - Wen-Er Li; Weiwei Chen; Yun-Fei Ma; Qing-Rong Tuo; Xiao-Jing Luo; Ting Zhang; Wen-Bo Sai; Jing Liu; Jinhua Shen; Zhi-Gang Liu; Yun-Min Zheng; Yong-Xiao Wang; et al. (Pflügers Archiv - European Journal of Physiology, 2012)

Advanced glycation end products promote proliferation of cardiac fibroblasts by upregulation of KCa3.1 channels - Li-Mei Zhao; Wei Zhang; Li-Ping Wang; Gui-Rong Li; Xiu-Ling Deng (Pflügers Archiv - European Journal of Physiology, 2012)

A functional polymorphism, rs28493229, in ITPKC and risk of Kawasaki disease: an integrated meta-analysis - Jiao Lou; Sanqing Xu; Li Zou; Rong Zhong; Ti Zhang; Yu Sun; Xuzai Lu; Li Liu; Chuanqi Li; Li Wang; Guanglian Xiong; Wei Wang; et al. (Molecular Biology Reports, 2012)

Rapid odor perception in rat olfactory bulb by microelectrode array - Jun Zhou; Qi Dong; Liu-jing Zhuang; Rong Li; Ping Wang (Journal of Zhejiang University-SCIENCE B, 2012)

The role of leptin in lipid metabolism in fatty degenerated hepatocytes of the grass carp Ctenopharyngodon idellus - Rong-Hua Lu; Xu-Fang Liang; Min Wang; Yi Zhou; Xiao-Li Bai; Yan He (Fish Physiology and Biochemistry, 2012)

Effects of Ibutilide on Canine Cardiac Pacing Threshold and on Induction Rates of Atrial Fibrillation - Jian-ling Sun; Rong Han; Ji-hong Guo; Xiao-ying Li; Xian-lin Ma; Chong-yu Wang (Cell Biochemistry and Biophysics, 2012)

Simple and rapid detection of swine hepatitis E virus by reverse transcription loop-mediated isothermal amplification - Liang-Quan Zhang; Fu-Rong Zhao; Zhi-Gang Liu; Wei-Li Kong; Heng Wang; Yun Ouyang; Huan-Bin Liang; Chao-Yi Zhang; Hai-Tao Qi; Chang-Li Huang; Si-Hu Guo; Gui-Hong Zhang (Archives of Virology, 2012)

Cloning arginine kinase gene and its RNAi in Bursaphelenchus xylophilus causing pine wilt disease - Xin-rong Wang; Xi Cheng; Ya-dong Li; Jin-ai Zhang; Zhi-fen Zhang; Han-rong Wu (European Journal of Plant Pathology, 2012)

Effect of Ibutilide on the Canine Cardiac Conduction System - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2012)

Comparative analysis of water stress-responsive transcriptomes in drought-susceptible and -tolerant wheat (Triticum aestivum L.) - Yong Chun Li; Fan Rong Meng; Chun Yan Zhang; Ning Zhang; Ming Shan Sun; Jiang Ping Ren; Hong Bin Niu; Xiang Wang; Jun Yin (Journal of Plant Biology, 2012)

Perifosine as potential anti-cancer agent inhibits proliferation, migration, and tube formation of human umbilical vein endothelial cells - Feng Ze Wang; Hong Rong Fei; Xiao Qian Li; Renjiu Shi; De Cai Wang (Molecular and Cellular Biochemistry, 2012)

Proteomic analysis of the nuclear phosphorylated proteins in dairy cow mammary epithelial cells treated with estrogen - Jian-guo Huang; Xue-jun Gao; Qing-zhang Li; Li-min Lu; Rong Liu; Chao-chao Luo; Jia-li Wang; Qiao Bin; Xin Jin (In Vitro Cellular & Developmental Biology - Animal, 2012)

Reef types and sedimentation characteristics of Changxing formation in Manyue-Honghua Section of Kaixian, Northeastern Sichuan Basin - Liqun Wu; Yangquan Jiao; Hui Rong; Rui Wang; Rong Li (Journal of Earth Science, 2012)

Synthesis of aspirin eugenol ester and its biological activity - Jian-yong Li; Yuan-guang Yu; Qi-wen Wang; Ji-yu Zhang; Ya-jun Yang; Bing Li; Xu-zheng Zhou; Jian-rong Niu; Xiao-juan Wei; Xi-wang Liu; Zhi-qi Liu (Medicinal Chemistry Research, 2012)

Possible novel roles of poly(rC)-binding protein 1 in SH-SY5Y neurocytes: an analysis using a dynamic Bayesian network - Li-Rong Huo; Jian-Tao Liang; Jun-Hua Zou; Lan-Ying Wang; Qi Li; Xiao-Min Wang (Neuroscience Bulletin, 2012)

One-Step Bulk Preparation of Calcium Carbonate Nanotubes and Its Application in Anticancer Drug Delivery - Jing Tang; Dong-Mei Sun; Wen-Yu Qian; Rong-Rong Zhu; Xiao-Yu Sun; Wen-Rui Wang; Kun Li; Shi-Long Wang (Biological Trace Element Research, 2012)

A precise velocity field of tectonic deformation in China as inferred from intensive GPS observations - Qiang Li; XinZhao You; ShaoMin Yang; RuiLin Du; XueJun Qiao; Rong Zou; Qi Wang (Science China Earth Sciences, 2012)

Molecular cloning and functional characterization of a novel apple MdCIPK6L gene reveals its involvement in multiple abiotic stress tolerance in transgenic plants - Rong-Kai Wang; Ling-Li Li; Zhong-Hui Cao; Qiang Zhao; Ming Li; Ling-Yun Zhang; Yu-Jin Hao (Plant Molecular Biology, 2012)

Clinical characteristics of hepatitis B virus infection in middle school students born after the universal infant vaccination program in Shanghai, China - Wei-Ling Wang; Zhi-Jun Shu; Li-Xia Zhou; Yan-Rong Zhao (Archives of Virology, 2012)

Expansins are involved in cell growth mediated by abscisic acid and indole-3-acetic acid under drought stress in wheat - Mei-rong Zhao; Yang-yang Han; Ya-nan Feng; Feng Li; Wei Wang (Plant Cell Reports, 2012)

The expression level of Rosa Terminal Flower 1 (RTFL1) is related with recurrent flowering in roses - Li-Na Wang; Yun-Feng Liu; Yu-Man Zhang; Rong-Xiang Fang; Qing-Lin Liu (Molecular Biology Reports, 2012)

At-line monitoring of key parameters of nisin fermentation by near infrared spectroscopy, chemometric modeling and model improvement - Wei-Liang Guo; Yi-Ping Du; Yong-Can Zhou; Shuang Yang; Jia-Hui Lu; Hong-Yu Zhao; Yao Wang; Li-Rong Teng (World Journal of Microbiology and Biotechnology, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

Changes in Small Intestinal Morphology and Digestive Enzyme Activity with Oral Administration of Copper-Loaded Chitosan Nanoparticles in Rats - Xin-Yan Han; Wen-Li Du; Qi-Chun Huang; Zi-Rong Xu; Yi-Zheng Wang (Biological Trace Element Research, 2012)

Functional analysis of the HS185 regulatory element in the rice HSP70 promoter - Yu-Man Zhang; Yu-Mei Zheng; Na Xiao; Li-Na Wang; Yao Zhang; Rong-Xiang Fang; Xiao-Ying Chen (Molecular Biology Reports, 2012)

PNAS-4 expression and its relationship to p53 in colorectal cancer - Bin Zhou; Hui Yan; Yuan Li; Rong Wang; Keling Chen; Zongguang Zhou; Xiaofeng Sun (Molecular Biology Reports, 2012)

Decreased expression of Beclin-1 and LC3 in human lung cancer - Zi-Feng Jiang; Li-Jie Shao; Wei-Min Wang; Xue-Bo Yan; Rong-Yu Liu (Molecular Biology Reports, 2012)

The mediating and moderating role of personal strain and coping resource in the relationship between work stressor and quality of life among Chinese nurses - Si-Ying Wu; Huang-Yuan Li; Shu-Juan Yang; Wei Zhu; Xiao-Rong Wang (International Archives of Occupational and Environmental Health, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Effects of Atorvastatin on Pathological Changes in Brain Tissue and Plasma MMP-9 in Rats with Intracerebral Hemorrhage - Jing-Jing Cui; Dong Wang; Fei Gao; Yue-Rong Li (Cell Biochemistry and Biophysics, 2012)

Bioaccessibility and Risk Assessment of Cadmium from Uncooked Rice Using an In Vitro Digestion Model - Lin-Sheng Yang; Xiu-Wu Zhang; Yong-Hua Li; Hai-Rong Li; Ying Wang; Wu-Yi Wang (Biological Trace Element Research, 2012)

Phylogenic analysis of Chinese Leishmania isolates based on small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA) - Wang Guan; De-Ping Cao; Ke sun; Jia-nan Xu; Jun-rong Zhang; Da-Li Chen; Jian-Ping Chen (Acta Parasitologica, 2012)
The leishmaniases are zoonotic diseases caused by protozoan parasites of the genus Leishmania. Leishmaniases are still endemic in China, especially in the west and northwest froniter regions. To revalue the preliminary phylogenetic results of Chinese Leishmania isolates, we amplified partial fragment of small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA), then tested the phylogenetic relationships among Chinese Leishmania isolates and their relatives by analyzing SSU rRNA gene sequences and 7SL RNA gene sequences. 19 SSU RNA sequences and 9 7SL RNA sequences were obtained in our study, then analyzed with 42 SSU RNA sequences and 32 7SL RNA sequences retrieved from Genbank, respectively. In the Bayesian analysis of the SSU RNA gene, the isolate MHOM/CN/93/GS7 and the isolate IPHL/CN/77/XJ771 are members of Leishmania donovani complex, while the isolate MHOM/CN/84/JS1 clustered with Leishmania tropica. The other 11 Chinese Leishmania isolates (MHOM/CN/90/WC, MCAN/CN/90/SC11, MHOM/CN/80/XJ801, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/ 89/GS5) form an unclassified group, defined as Leishmania sp., and the most relative species to this group is L. tarentolae. In the Bayesian analysis of the 7SL RNA gene, 9 Chinese Leishmania isolates also formed an unclassified group with L. tarentolae, including canine isolate 10, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/ CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/89/GS5. We concluded that: (1) Chinese Leishmania isolates are non-monophyly group; (2) an unclassified group may exist in China, and the most relative species to this group is L. tarentolae; (3) MHOM/CN/84/JS1, which was previously assigned as L. donovani, was most genetically related to L. tropica strain MHOM/SU/74/K27.

Human cytomegalovirus RL13 gene transcripts in a clinical strain - Mali Li; Yanping Ma; Yaohua Ji; Rong He; Ying Qi; Zhengrong Sun; Ning Wang; Shuang Gao; Qiang Ruan (Virus Genes, 2011)

Timing, Conditions, and Complications of Post-operative Conception and Pregnancy in Female Renal Transplant Recipients - Long-gen Xu; Shu Han; Yong Liu; Hong-wei Wang; Yi-rong Yang; Feng Qiu; Wan-ling Peng; Li-gong Tang (Cell Biochemistry and Biophysics, 2011)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Analysis of variable sites between two complete South China tiger (Panthera tigris amoyensis) mitochondrial genomes - Wenping Zhang; Bisong Yue; Xiaofang Wang; Xiuyue Zhang; Zhong Xie; Nonglin Liu; Wenyuan Fu; Yaohua Yuan; Daqing Chen; Danghua Fu; Bo Zhao; Yuzhong Yin; et al. (Molecular Biology Reports, 2011)

Normal epigenetic inheritance in mice conceived by in vitro fertilization and embryo transfer - Lei Li; Fang Le; Li-ya Wang; Xiang-rong Xu; Hang-ying Lou; Ying-ming Zheng; Jiang-zhong Sheng; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2011)

Discovering the distinct inhibitory effects between C4-epimeric glycosyl amino acids: new insight into the development of protein tyrosine phosphatase inhibitors - Xiao-Peng He; Cui Li; Zhi-Zhou Wang; Li-Xin Gao; Xiao-Xin Shi; Yun Tang; Juan Xie; Jia Li; Guo-Rong Chen; Kaixian Chen (Glycoconjugate Journal, 2011)

Fluorescence in situ hybridization on plant extended chromatin DNA fibers for single-copy and repetitive DNA sequences - Kun Yang; Hecui Zhang; Richard Converse; Yong Wang; Xiaoying Rong; Zhigang Wu; Bing Luo; Liyan Xue; Li Jian; Liquan Zhu; Xiaojia Wang (Plant Cell Reports, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Trigonella arcuata-associated rhizobia—an Ensifer (Sinorhizobium) meliloti population adapted to a desert environment - Yu Rong He; Jing Yu Wang; En Tao Wang; Gu Feng; Yue Li Chang; Xin Hua Sui; Wen Xin Chen (Plant and Soil, 2011)

Cloning and functions analysis of a pyruvate dehydrogenase kinase in Brassica napus - Rong-Jun Li; Zhi-Yong Hu; Hua-Shan Zhang; Gao-Miao Zhan; Han-Zhong Wang; Wei Hua (Plant Cell Reports, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Increased urinary 8-hydroxy-2′-deoxyguanosine levels in workers exposed to di-(2-ethylhexyl) phthalate in a waste plastic recycling site in China - Qian Wang; Li Wang; Xi Chen; Kai Min Rao; Shao You Lu; Sheng Tao Ma; Pu Jiang; Dan Zheng; Shun Qing Xu; Hong Yan Zheng; Jian Shu Wang; Zhi Qiang Yu; et al. (Environmental Science and Pollution Research, 2011)

Synthesis, Characterization, DNA Binding Properties and Antioxidant Activity of Ln(III) Complexes with Schiff Base Ligand Derived from 3-Carbaldehyde Chromone and Aminophenazone - Yong Li; Zheng-yin Yang; Tian-rong Li; Zeng-chen Liu; Bao-dui Wang (Journal of Fluorescence, 2011)

Expansin-regulated cell elongation is involved in the drought tolerance in wheat - Mei-rong Zhao; Feng Li; Ying Fang; Qiang Gao; Wei Wang (Protoplasma, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Mineral status and mechanical properties of cancellous bone exposed to hydrogen peroxide for various time periods - Dan Li; Long Bi; Guolin Meng; Jun Wang; Rong Lv; Min Liu; Jian Liu; Yunyu Hu (Cell and Tissue Banking, 2011)

Comparison of DNA extraction methods for the PCR-single-strand-conformation polymorphism analysis of kefir - Shu-Jun Chen; Qing Wang; Jian-Rong Han; Yu Wang; Zhi-Wei Li (World Journal of Microbiology and Biotechnology, 2011)

Serum complement C3 has a stronger association with insulin resistance than high sensitive C-reactive protein in non-diabetic Chinese - Bangqiong Wang; Qifu Li; Yuanjuan Jiang; Zhoujun Liu; Li Zhong; Rong Luo; Qingfeng Cheng; Hua Qing (Inflammation Research, 2011)

Analysis of the antibodies anti-Toxoplasma gondii by ELISA based on two diagnostic antigens: rSAG1 and rBAG1 - Min Liu; Tao Wang; Hua Li; Ju-Ying Li; Han Zhong; Chang-Zan Tan; De-Cheng Huang; Liang Zhao; Xiao-Guang Chen; Zhao-Rong Lun (Acta Parasitologica, 2011)
Schizophrenia is a serious neuropsychiatric disease of uncertain etiology. Previous studies have demonstrated that antibodies to Toxoplasma gondii infection are associated with an increased risk of schizophrenia. The objective of this study was to analyze anti-T. gondii antibodies in 477 Chinese schizophrenia patients using an enzyme-linked immunosorbent assay (ELISA) based on recombinant surface antigen 1 (rSAG1), recombinant bradyzoite antigen 1 (rBAG1) and the soluble tachyzoite antigens (STAg) of T. gondii RH strain. Results showed that among the sero-positives (IgG and/or IgM) for T. gondii infection examined in schizophrenia patients, sero-positive samples for rSAG1, rBAG1 and STAg were 20.5% (98/477), 20.5% (98/477) and 23.5% (112/477) respectively, while compared to 210 blood donors, sero-positive (IgG and/or IgM) samples for these antigens (rSAG1, rBAG1 and STAg) were only 5.7% (12/210), 6.2% (13/210) and 5.7% (12/210), respectively. Furthermore, when IgG antibody reaction in the schizophrenia sera was compared with the rBAG1 and rSAG1, results demonstrated that beside the cases which can be detected by both rSAG1 and rBAG1, some sero-positive for T. gondii in schizophrenia sera can only be detected either by rSAG1 or rBAG1. This phenomenon was also observed in the detection of IgM with rSAG1 and rBAG1. 5.9% (28/477) of cases of schizophrenia which are positive for IgG or IgM by rSAG1 are negative for STAg, while 9.2% (44/477) of the schizophrenia cases which are positive for IgG or IgM by rBAG1 are negative for STAg. Although STAg can also be used to diagnose T. gondii infection from schizophrenia patients, it may not actually indicate the infection as some positive samples may be mistakenly considered to be negative. In conclusion, our results demonstrate that the sero-positive rate for T. gondii in the Chinese schizophrenia patients was higher than blood donors. More importantly, our results provide evidence that the combination of rSAG1 and rBAG1 antigens in the diagnosis of T. gondii infection could closely reflect the actual infection of this parasite in schizophrenia patients.

Differential miRNA expression and their target genes between NGX6-positive and negative colon cancer cells - Xiao-Yan Wang; Ming-Hua Wu; Fen Liu; Yu Li; Nan Li; Gui-Yuan Li; Shou-Rong Shen (Molecular and Cellular Biochemistry, 2010)

Prognostic value of serum soluble Fas in patients with locally advanced unresectable rectal cancer receiving concurrent chemoradiotherapy - Qi-lian Liang; Zhou-yu Li; Guo-qiang Chen; Zhen-nan Lai; Bi-rong Wang; Jie Huang (Journal of Zhejiang University-SCIENCE B, 2010)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

Construction and characterization of a full-length infectious clone from a fast-replicating, X4-tropic HIV-1 subtype B′ isolate - Shou-li Wu; Yan-sheng Yan; Ping-ping Yan; Hai-long Huang; Hui-rong Wang (Archives of Virology, 2010)

Seismic analysis of the active character of the Taihang Mountain piedmont fault - Ming-Cai Xu; Jing-Hua Gao; Li-Xin Rong; Guang-Ke Wang; Xiao-Jiang Wang (Applied Geophysics, 2010)

Influence of cell surface properties on adhesion ability of bifidobacteria - Li-Qun Wang; Xiang-Chen Meng; Bai-Rong Zhang; Yan Wang; Yu-Lin Shang (World Journal of Microbiology and Biotechnology, 2010)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Assessment of inheritance pattern and agronomic performance of transgenic rapeseed having harpinXooc-encoding hrf2 Gene - Rong Huo; Yu Wang; Ling-Li Ma; Jun-Qing Qiao; Min Shao; Xue-Wen Gao (Transgenic Research, 2010)

Transcription pattern of UL131A-128 mRNA in clinical strains of human cytomegalovirus - Zhengrong Sun; Gaowei Ren; Yanping Ma; Ning Wang; Yaohua Ji; Ying Qi; Mali Li; Rong He; Qiang Ruan (Journal of Biosciences, 2010)

Comparison of reproductive strategies in two externally ovipositing non-pollinating fig wasps - Zhen-Ji Wang; Feng-Ping Zhang; Yan-Qiong Peng; Li-Fen Bai; Da-Rong Yang (Symbiosis, 2010)

Effect of glycyrrhizin on the activity of CYP3A enzyme in humans - Jiang-Hua Tu; Yi-Jing He; Yao Chen; Lan Fan; Wei Zhang; Zhi-Rong Tan; Yuan-Fei Huang; Dong Guo; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2010)

Differential expression of TRPC channels in the left ventricle of spontaneously hypertensive rats - Fang-fang Liu; Zhi-yong Ma; Duo-ling Li; Jin-bo Feng; Kai Zhang; Rong Wang; Wei Zhang; Li Li; Yun Zhang (Molecular Biology Reports, 2010)

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Fan-Rong Wu; Jian-Ping Li; Cheng-Wan Li; Yu Wang; Teng-Yue Zhang; Wei Hu (Molecular and Cellular Biochemistry, 2010)

Improvement of heat and drought photosynthetic tolerance in wheat by overaccumulation of glycinebetaine - Gui-Ping Wang; Zhen Hui; Feng Li; Mei-Rong Zhao; Jin Zhang; Wei Wang (Plant Biotechnology Reports, 2010)

Efficient production of omega-3 fatty acid desaturase (sFat-1)-transgenic pigs by somatic cell nuclear transfer - DengKe Pan; Li Zhang; YanRong Zhou; Chong Feng; Chuan Long; Xiao Liu; Rong Wan; Jian Zhang; AiXing Lin; EnQiu Dong; ShuChen Wang; HouGang Xu; et al. (Science China Life Sciences, 2010)

Cytological and RAPD data revealed genetic relationships among nine selected populations of the wild bramble species, Rubus parvifolius and R. coreanus (Rosaceae) - Xiao-rong Wang; Yuan Liu; Bi-feng Zhong; Xiao-li Dong; Qing Chen; Wu-feng Xia; Hanwu Zhang; Hao-ru Tang (Genetic Resources and Crop Evolution, 2010)

Association of functional polymorphisms in MMPs genes with gastric cardia adenocarcinoma and esophageal squamous cell carcinoma in high incidence region of North China - Yan Li; Dong-lan Sun; Ya-nan Duan; Xiao-juan Zhang; Na Wang; Rong-miao Zhou; Zhi-feng Chen; Shi-jie Wang (Molecular Biology Reports, 2010)

CYP3A4*1G genetic polymorphism influences CYP3A activity and response to fentanyl in Chinese gynecologic patients - Wei Zhang; Yan-Zi Chang; Quan-Cheng Kan; Li-Rong Zhang; Zhi-Song Li; Hui Lu; Zhong-Yu Wang; Qin-Jun Chu; Jie Zhang (European Journal of Clinical Pharmacology, 2010)

Association of TNFAIP3 polymorphism with rheumatic heart disease in Chinese Han population - Rong Hua; Ji-bin Xu; Jiu-cun Wang; Li Zhu; bing Li; Yang Liu; Sheng-dong Huang; Li Jin; Zhi-yun Xu; Xiao-feng Wang (Immunogenetics, 2009)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Potential role of the TLR4/IRAK-4 signaling pathway in the pathophysiology of acute pancreatitis in mice - Jun-Li Ding; Yuan Li; Xiang-Yu Zhou; Ling Wang; Bin Zhou; Rong Wang; Hong-Xiang Liu; Zong-Guang Zhou (Inflammation Research, 2009)

Combination of newly developed high quality Fuqu with traditional Daqu for Luzhou-flavor liquor brewing - Wen-Xue Zhang; Zheng-Yun Wu; Qi-Sheng Zhang; Rong Wang; Heng Li (World Journal of Microbiology and Biotechnology, 2009)

Isolation and Evolution Mode Analysis of NBS–LRR Resistance Gene Analogs from Hexaploid Wheat - De-Shun Feng; Yan Li; Hong-Gang Wang; Xing-Feng Li; Ju-Rong Gao (Plant Molecular Biology Reporter, 2009)

DcR3 and survivin are highly expressed in colorectal carcinoma and closely correlated to its clinicopathologic parameters - Qi-lian Liang; Bi-rong Wang; Guo-hong Li (Journal of Zhejiang University-SCIENCE B, 2009)

Temporal patterns of net soil N mineralization and nitrification through secondary succession in the subtropical forests of eastern China - En-Rong Yan; Xi-Hua Wang; Ming Guo; Qiang Zhong; Wu Zhou; Yong-Fu Li (Plant and Soil, 2009)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

The Avoidance Responses of Daphnia magna to the Exposure of Organophosphorus Pesticides in an On-Line Biomonitoring System - Zong-Ming Ren; Zhi-Liang Li; Jin-Miao Zha; Kai-feng Rao; Mei Ma; Zijian Wang; Rong-Shu Fu (Environmental Modeling & Assessment, 2009)

Numerical Simulations on the Effect of Sea–Land Breezes on Atmospheric Haze over the Pearl River Delta Region - Chen Xun-lai; Feng Ye-rong; Li Jiang-nan; Lin Wen-shi; Fan Shao-jia; Wang An-yu; Fong Soikun; Lin Hui (Environmental Modeling & Assessment, 2009)

Respiratory face mask: a novel and cost-effective device for use during the application of myocardial ischemia in rats - Yuan Yuan; Fei Li; Yue-min Wang; Rong-qing Zhang; Li-ping Wei; Hai-chang Wang (Journal of Zhejiang University-SCIENCE B, 2009)

Induction of cytochrome P450 2B6 activity by the herbal medicine baicalin as measured by bupropion hydroxylation - Lan Fan; Jin-Chao Wang; Feng Jiang; Zhi-Rong Tan; Yao Chen; Qing Li; Wei Zhang; Guo Wang; He-Ping Lei; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

The sources and seasonal variations of organic compounds in PM2.5 in Beijing and Shanghai - Yilun Jiang; Ximei Hou; Guoshun Zhuang; Juan Li; Qiongzhen Wang; Rong Zhang; Yanfen Lin (Journal of Atmospheric Chemistry, 2009)

Molecular cloning and characterization of twoBrassica napus TTG1 genes reveal genus-specific nucleotide preference, extreme protein-level conservation and fast divergence of organ-specificity - Jun Lu; Jia-Na Li; Bo Lei; San-Gen Wang; You-Rong Chai (Genes & Genomics, 2009)

The CYP2C19 ultra-rapid metabolizer genotype influences the pharmacokinetics of voriconazole in healthy male volunteers - Guo Wang; He-Ping Lei; Zhi Li; Zhi-Rong Tan; Dong Guo; Lan Fan; Yao Chen; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

An investigation on the polymorphisms of two DNA repair genes and susceptibility to ESCC and GCA of high-incidence region in northern China - Na Wang; Xiu-juan Dong; Rong-miao Zhou; Wei Guo; Xiao-juan Zhang; Yan Li (Molecular Biology Reports, 2009)

TRANSPARENT TESTA 12 genes from Brassica napus and parental species: cloning, evolution, and differential involvement in yellow seed trait - You-Rong Chai; Bo Lei; Hua-Lei Huang; Jia-Na Li; Jia-Ming Yin; Zhang-Lin Tang; Rui Wang; Li Chen (Molecular Genetics and Genomics, 2009)

Distribution, biomass, and dynamics of roots in a revegetated stand of Caragana korshinskii in the Tengger Desert, northwestern China - Zhi-Shan Zhang; Xin-Rong Li; Li-Chao Liu; Rong-Liang Jia; Jing-Guang Zhang; Tao Wang (Journal of Plant Research, 2009)

15-HETE suppresses K+ channel activity and inhibits apoptosis in pulmonary artery smooth muscle cells - Yumei Li; Qian Li; Zhigang Wang; Di Liang; Shujun Liang; Xiaobo Tang; Lei Guo; Rong Zhang; Daling Zhu (Apoptosis, 2009)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

Variation of 423G>T in the Agouti Gene Exon 4 in Indigenous Chinese Goat Breeds - Chun-Juan Tang; Rong-Yan Zhou; Xiang-Long Li; Jing-Wen Zhao; Lan-Hui Li; Fu-Jun Feng; Dong-Feng Li; Jian-Tao Wang; Xiu-Li Guo; Jing-Fen Keng (Biochemical Genetics, 2008)

Distribution, sources, and potential risk of polycyclic aromatic hydrocarbons (PAHs) in drinking water resources from Henan Province in middle of China - Ying-ge Ma; Jin-ping Cheng; Fei Jiao; Ke-xin Duo; Zheng Rong; Ming Li; Wen-hua Wang (Environmental Monitoring and Assessment, 2008)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Dysregulation of CREB binding protein triggers thrombin-induced proliferation of vascular smooth muscle cells - Jing Chen; Hong Jiang; Lin Xu; Li-Hua Zhu; Lang Wang; Hua-Zhi Wen; Xiao-Rong Hu (Molecular and Cellular Biochemistry, 2008)

Androgen receptor: a new player associated with apoptosis and proliferation of pancreatic beta-cell in type 1 diabetes mellitus - Ru-Jiang Li; Shu-Dong Qiu; Hai-Xu Wang; Hong Tian; Li-Rong Wang; Yong-Wei Huo (Apoptosis, 2008)

Expression, purification and characterization of a phyA m -phyCs fusion phytase - Li-kou Zou; Hong-ning Wang; Xin Pan; Guo-bao Tian; Zi-wen Xie; Qi Wu; Hui Chen; Tao Xie; Zhi-rong Yang (Journal of Zhejiang University-SCIENCE B, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Sensing Escherichia coli O157:H7 via frequency shift through a self-assembled monolayer based QCM immunosensor - Li-jiang Wang; Chun-sheng Wu; Zhao-ying Hu; Yuan-fan Zhang; Rong Li; Ping Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Involvement of voltage-gated K+ and Na+ channels in gastric epithelial cell migration - William Ka Kei Wu; Gui Rong Li; Tak Ming Wong; Jian Ying Wang; Le Yu; Chi Hin Cho (Molecular and Cellular Biochemistry, 2008)

Increased expression of hLRH-1 in human gastric cancer and its implication in tumorigenesis - Shui-Liang Wang; De-Zhu Zheng; Feng-Hua Lan; Xiao-Jun Deng; Jian Zeng; Cheng-Jin Li; Rong Wang; Zhong-Yong Zhu (Molecular and Cellular Biochemistry, 2008)

Isolation and identification of a non-haemagglutinating strain of rabbit hemorrhagic disease virus from China and sequence analysis for the VP60 Gene - Lang Tian; Juan Liao; Jian-wen Li; Wan-rong Zhou; Xia-lan Zhang; Hong-ning Wang (Virus Genes, 2007)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Phytase expression in transgenic soybeans: stable transformation with a vector-less construct - Xiao Rong Gao; Guo Kun Wang; Qiao Su; Yan Wang; Li Jia An (Biotechnology Letters, 2007)

Knockout of the gene (ste15) encoding a glycosyltransferase and its function in biosynthesis of exopolysaccharide in Streptomyces sp. 139 - Qing-Li Sun; Ling-Yan Wang; Jun-Jie Shan; Rong Jiang; Lian-Hong Guo; Yang Zhang; Ren Zhang; Yuan Li (Archives of Microbiology, 2007)

Morphological changes of cholinergic nerve fibers in the urinary bladder after establishment of artificial somatic-autonomic reflex arc in rats - Han-Zhi Wang; Shu-Rong Li; Can Wen; Chuan-Guo Xiao; Bing-Yin Su (Neuroscience Bulletin, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Intergeneration CAG expansion in a Wuhan juvenile-onset Huntington disease family - Yuan Liu; Yan Shen; He Li; Hui Wang; Zhen-Rong Yang; Yan Chen; Yan-Ping Tang (Neuroscience Bulletin, 2007)

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)

Role of iNOS-derived reactive nitrogen species and resultant nitrative stress in leukocytes-induced cardiomyocyte apoptosis after myocardial ischemia/reperfusion - Xiao-Liang Wang; Hui-Rong Liu; Lin Tao; Feng Liang; Li Yan; Rong-Rui Zhao; Bernard L. Lopez; Theodore A. Christopher; Xin-Liang Ma (Apoptosis, 2007)

Cytological and molecular characterization of a novel monogenic dominant GMS in Brassica napus L. - Dao-Jie Wang; Ai-Guang Guo; Dian-Rong Li; Jian-Hua Tian; Fei Huang; Gen-Lou Sun (Plant Cell Reports, 2007)

Nematicidal Resorcylides from the Aquatic Fungus Caryospora callicarpa YMF1.01026 - Jinyan Dong; Yanhui Zhu; Hongchuan Song; Ru Li; Hongping He; Haiyang Liu; Rong Huang; Yongping Zhou; Le Wang; Yi Cao; Keqin Zhang (Journal of Chemical Ecology, 2007)

Assignment of CCR7 gene to chicken chromosome 27 by radiation hybrid panel mapping - Yong Tian; Li-zhi Lu; Yan Fu; Zheng-rong Tao; Jun-da Shen; De-qian Wang; Ai-ping Yuan; Zhao-zheng Yin (Journal of Zhejiang University-SCIENCE B, 2007)

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)

Passage number affects the pluripotency of mouse embryonic stem cells as judged by tetraploid embryo aggregation - Xiang-yun Li; Qing Jia; Ke-qian Di; Shu-min Gao; Xiao-hui Wen; Rong-yan Zhou; Wei Wei; Li-ze Wang (Cell and Tissue Research, 2007)

Identification of differentially expressed genes in seeds of two near-isogenic Brassica napus lines with different oil content - Rong-Jun Li; Han-Zhong Wang; Han Mao; Ying-Tang Lu; Wei Hua (Planta, 2006)

Crop yield, nitrogen uptake and nitrate-nitrogen accumulation in soil as affected by 23 annual applications of fertilizer and manure in the rainfed region of Northwestern China - Sheng-Mao Yang; S. S. Malhi; Jian-Rong Song; You-Cai Xiong; Wei-Yun Yue; Li Li Lu; Jian-Guo Wang; Tian-Wen Guo (Nutrient Cycling in Agroecosystems, 2006)

Bone marrow mesenchymal stem cell transplantation combined with perindopril treatment attenuates infarction remodelling in a rat model of acute myocardial infarction - Jian-an Wang; Rong-hua Luo; Xing Zhang; Xiao-jie Xie; Xin-yang Hu; Ai-na He; Jie Chen; Jia-hui Li (Journal of Zhejiang University-SCIENCE B, 2006)

Effects of predator-mediated apparent competition on the population dynamics of Tetranychus urticae on apples - Chang-zhong Liu; Lin Yan; Hua-rong Li; Gang Wang (BioControl, 2006)

Cytogenetic Study of a Trigeneric (Triticale × Trileymus) Hybrid - Xing-Feng Li; Zhen-Qiao Song; Shu-Bing Liu; Ju-Rong Gao; Hong-Gang Wang (Euphytica, 2006)

Evaluation of caspase-dependent apoptosis during fluoride-induced liver lesion in pigs - Xiu An Zhan; Min Wang; Zi Rong Xu; Wei Fen Li; Jian Xin Li (Archives of Toxicology, 2006)

Spatial-temporal changes and trends of ageing in China - Wu-yi Wang; Li Zhang; Hai-rong Li; Ri-bang Li; Lin-sheng Yang; Yong-feng Liao (Chinese Geographical Science, 2005)

Abnormal pollen development of bread wheat-Leymus mollis partial amphiploid - Xing-Feng Li; Shu-Bing Liu; Ju-Rong Gao; Wen-Hui Lu; Hong-Gang Wang (Euphytica, 2005)

Molecular Cloning and Expression of IL2 cDNA from the Tibet Pig - Li Hui; Gao Rong; Wu Mei; Wang Li-Huan; Fu Man-Liang; Wu Kai-Yuan (Veterinary Research Communications, 2005)

Molecular Cloning and Characterization of a Novel Human C4orf13 Gene, Tentatively a Member of the Sodium Bile Acid Cotransporter Family - Xianqiong Zou; Dianzuo Wang; Guanzhou Qiu; Chaoneng Ji; Feng Jin; Maoqing Wu; Huarui Zheng; Xin Li; Liyun Sun; Yu Wang; Rong Tang; Robert Chunhua Zhao; et al. (Biochemical Genetics, 2005)

Novel CACNA1S mutation causes autosomal dominant hypokalemic periodic paralysis in a Chinese family - Qiufen Wang; Mugen Liu; Chunsheng Xu; Zhaohui Tang; Yuhua Liao; Rong Du; Wei Li; Xiaoyan Wu; Xu Wang; Ping Liu; Xianqin Zhang; Jianfang Zhu; et al. (Journal of Molecular Medicine, 2005)

Ile118Val genetic polymorphism of CYP3A4 and its effects on lipid-lowering efficacy of simvastatin in Chinese hyperlipidemic patients - An Wang; Bang-Ning Yu; Chen-Hui Luo; Zhi-Rong Tan; Gan Zhou; Lian-Sheng Wang; Wei Zhang; Zhi Li; Jie Liu; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2005)

Residents’ attitudes to tourism development in ancient village resorts - Li Wang; Lin Lu; Shi-rong Tong; Song Lu; Zhao Yang; Yong Wang; Dong-dong Liang (Chinese Geographical Science, 2004)

Conversion rates of surface HOx radicals in Beijing City - Xin-rong Ren; Li-xin Wang; Hui-xiang Wang; Guo-fang Miao (Chinese Geographical Science, 2004)

The Immunoregulation of Mice by Somatic Transgenic Expression of Porcine Interleukin-6 Gene and CpG Sequence - Jiangling Li; Rong Gao; Mei Wu; Mingjie Meng; Manshu Tang; Yi Shen; Lihuan Wang; Xueyan Wu; Xue Yin; Hongguan Xie; Shigui Liu (Veterinary Research Communications, 2004)

Molecular cloning and characterization of betaine aldehyde dehydrogenase gene from Suaeda liaotungensis and its use in improved tolerance to salinity in transgenic tobacco - Qiu-Li Li; Xiao-Rong Gao; Xiao-Hong Yu; Xing-Zhi Wang; Li-Jia An (Biotechnology Letters, 2003)

The heparan sulfate proteoglycan gene polymorphism: Association with type 2 diabetic nephropathy in Chinese - Limei Liu; Kunsan Xiang; Taishan Zheng; Rong Zhang; Ming Li; Yanqing Wang; Huijuan Li; Jie Li (Molecular and Cellular Biochemistry, 2003)

GSTP1 polymorphisms and gastric cancer in a high-risk Chinese population - Veronica Wendy Setiawan; Zuo-Feng Zhang; Guo-Pei Yu; Qing-Yi Lu; Yong-Liang Li; Ming-Lan Lu; Ming-Rong Wang; Chun Hua Guo; Shun-Zhang Yu; Robert C Kurtz; Chung-Cheng Hsieh (Cancer Causes & Control, 2001)

Immobilization of lipase by salts and the transesterification activity in hexane - Wang Pu; Yang Li-rong; Wu Jian-ping (Biotechnology Letters, 2001)

Differential expression of RAB5A in human lung adenocarcinoma cells with different metastasis potential - Li Yu; Feng Hui-chen; Yu Chen; Rong Zou; Song Yan; Liu Chun-xiang; Wang Wu-ru; Pu Li (Clinical & Experimental Metastasis, 1999)

The chirality selectivity in the uptake of platinum (II) complexes with 1,2-cyclohexanediamine isomers as carrier ligand by human erythrocytes - Juan Zou; Xiao Gai Yang; Rong Chang Li; Jing Fen Lu; Kui Wang (BioMetals, 1997)